Combined application of calcium lactate and pectin methylesterase maintains strawberry firmness and extends postharvest shelf life - Alysson Caetano Soares; Vanessa dos Santos Santana Souza; Aline Andrade Reis; Steven Alonso Sargent; Aline de Almeida Vasconcelos; Ângelo Pedro Jacomino; Luiz Fernando Ganassali de Oliveira Junior; Marcelo Augusto Gutierrez Carnelossi (Postharvest Biology and Technology, 2026)

Anti-Candida activity of simplified analogs of curcumin - Carlos R. Polaquini; Paulo T. Costa; Janaina C. O. Sardi; Veridianna C. Pattini; Margarete T. G. Almeida; Pedro L. Rosalen; Luis O. Regasini (Archives of Microbiology, 2026)

Tracking forest carbon and growth in large-scale passive restoration using multi-temporal airborne lidar - Felipe N. Begliomini; Fabian Jörg Fischer; Srinivasan Keshav; Pedro H.S. Brancalion; Paulo G. Molin; Angelica M. Almeyda Zambrano; Angélica Faria de Resende; Cassio Toledo; Catherine Torres de Almeida; Danilo Roberti Alves de Almeida; Davi Ernesto Alvarenga César; Eben N. Broadbent; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

First report of Angiostrongylus vasorum parasitizing lesser grison (Galictis cuja) (Mustelidae) in Brazil - Julia Somavilla Lignon; Maiza Paixão Souza; Natália Büttenbender; Pedro Almeida Rezende; Raqueli Teresinha França; Kauê Rodriguez Martins; Rodrigo Casquero Cunha; Felipe Geraldo Pappen; Diego Moscarelli Pinto (Veterinary Research Communications, 2026)
Angiostrongylus vasorum is a metastrongylid nematode that parasitizes the pulmonary arteries and right heart of canids, being the etiological agent of canine angiostrongylosis, a disease of growing veterinary concern due to its expanding geographic distribution and the involvement of domestic and wild hosts. In Brazil, the parasite has been reported mainly in domestic dogs and some wild canids, and its occurrence in mustelids has been documented only once previously. This study reports the first occurrence of A. vasorum infecting a lesser grison ( Galictis cuja ) in Brazil. The mustelid was found after being accidentally run over by a vehicle on a highway in the south of the country. Clinical, physical, and complementary examinations were performed for clinical screening. In the parasitological examination of feces, nematode larvae were recovered and identified morphometrically and molecularly through conventional PCR targeting to the COX1 gene, followed by sequencing and phylogenetic analysis. The results confirmed the presence of A. vasorum , showing 99–100% identity with sequences of the same species deposited in GenBank. Therefore, we document here the first report of A. vasorum parasitizing G. cuja . Thus, the number of known host species parasitized by this helminth is expanded. Furthermore, we provide a new molecular sequence, contributing to the knowledge of this nematode in South America.

Inhabiting the host: ectoparasites and Vector-Borne pathogens in Phyllostomidae bats within urban forest fragments - Nicolas Colácio; Yasmin C. Silva; Lucas B. S. Oliveira; Pedro G. S. Andrade; Leonardo P. Alcântara; Luiz G. M. Alves; Lis M. C. Vieira; Bruna H. Campos; Gabriel F. Diório; Brenda K. Gomes-Almeida; Marcelo P. N. Carvalho; Érika M. Braga; et al. (Veterinary Research Communications, 2026)
While bats are known to harbor various viruses and bacteria, their role as hosts for hemoparasites has not been extensively studied. This research investigated the presence of ectoparasites and vector-borne pathogens—including Anaplasmataceae agents, hemoplasmas, apicomplexans, and kinetoplastids—in 74 Phyllostomidae bats sampled from an urban forest fragment in southeastern Brazil. Overall, 31.1% of the bats were infested with ectoparasites: 82.6% carried only Streblidae bat flies, 13.0% had only mites, and 4.4% were co-infested with both parasites. No hemoparasites were observed in Giemsa-stained preparations. Furthermore, all samples tested negative for PCR assays targeting the orders Haemosporida and Piroplasmida, as well as for Anaplasma sp., Neorickettsia sp., Trypanosoma cruzi , and Trypanosoma evansi . Molecular analyses revealed that 1.4% of the bats were positive for Ehrlichia sp., 20.3% for hemotropic Mycoplasma spp., and 1.4% for Leishmania infantum . Coinfections were found in 1.4% of the positive samples. Sequence analyses revealed that the detected Ehrlichia sp. is closely related to Ehrlichia canis , and that the Mycoplasma sp. shares high sequence identity with bat-associated hemoplasmas. These findings document the presence of ectoparasites and hemopathogens in the sampled Phyllostomidae bats, indicating that these infectious agents circulate within urban forest fragments. While the specific role of these bats in sustaining the pathogens’ life cycles remains to be fully elucidated, these initial findings underscore the need for expanded eco-epidemiological studies. This highlights the crucial need to study these pathogens in bat populations, underscoring their ecological significance and the potential implications for public health and biodiversity conservation (e.g. zoonotic spillover and population stress).

Natural vegetation types in the landscape and local flower resources shape pollinator network interactions and crop yield in organic agroecosystems - Rafaela Mendes Assunção; Patricia Sanae Sujii; Marina de Almeida Magalhães Pereira; Antonio José Camillo de Aguiar; Luísa Mafalda Gigante Rodrigues Carvalheiro; Carmen Silvia Soares Pires; Pedro Henrique Brum Togni (Agriculture, Ecosystems & Environment, 2026)

Land-use impacts on Amazon and Atlantic rainforest coastal ecosystems revealed by multiple biogeochemical markers - Échily Sartori; Cristiane dos Santos Vergilio; Tassiana S.G. Serafim; Diego Lacerda; Luiza Silva do Nascimento; Pedro Vianna Gatts; Mariana Freitas; Jamile Tamer Nasser; Marcelo Gomes de Almeida; César C. Martins; Nils E. Asp; Carlos Eduardo de Rezende (Marine Pollution Bulletin, 2026)

Enhancing water management in data-scarce watersheds using satellite and reanalysis precipitation: a combined SWAT+ and SMOGN machine learning approach - Manuel Almeida; Narciso Ambrósio; Senlin Zhu; Pedro Coelho (Journal of Hydrology, 2026)

Bloom of Blixaea quinquecornis (Abé) Gottschling (Dinophyceae) with Chaetoceros tenuissimus Meunier in the South Atlantic: Morphology, molecular characterization, and toxins - Marcella Guennes; Amanda Santos Goulart; Fabiano Salgueiro; Priscila Kienteca Lange; Rodrigo Barcellos Hoff; Luana Souza Futigami; Rodrigo Almeida Ferreira da Silva; Andréa Shirley Xavier da Silva; Pedro Augusto Mendes de Castro Melo; Mauro de Melo Júnior; Silvia Mattos Nascimento (Journal of Environmental Sciences, 2026)

Large-scale toxic bloom of Dinophysis acuminata complex following a major flood disaster in southern Brazil - Luiz L. Mafra; Bruna Fernanda Sobrinho; Ana Martínez; Karoline Magalhães F. Lubiana; Regiane Valejo Maciel; José Guilherme F. Bersano; Luciano F. Fernandes; Fabiola Kaviatkovski; Pedro Almeida Rodrigo; Rafaela Cristine Zem; Carlos E.J.de Azevedo Tibiriçá; Mathias Alberto Schramm; et al. (Harmful Algae, 2026)

Parental history and social context shape offspring survival in captive jaguars (Pantera onca) - Leandro Silveira; Anah Tereza de Almeida Jácomo; Tiago Jácomo Silveira; Gediendson Ribeiro de Araujo; Ian Figueiredo Navarezi; Maitê Cardoso Coelho da Silva; Pedro Nacib Jorge-Neto; Marcia de Almeida Monteiro Melo Ferraz; Thyara de Deco-Souza (Animal Reproduction Science, 2026)

Inclusion of microalga Dunaliella salina in the diet of laying hens: effects on egg quality and sensory traits - Obete Madacussengua; Cátia Falcão Martins; Ana Beatriz Rodrigues Tavares; Daniela Filipa Pires Carvalho; Ana Rita Mendes; Tiago Guerra; António Pagarete; Suzana Ferreira-Dias; Miguel Pedro Mourato; José António Mestre Prates; André Martinho de Almeida; Madalena Lordelo (Algal Research, 2026)

A mechanistic approach about oxidative, mutagenic, and cytotoxic effects of an organotellurane - Felipe Emannuel Alvino de Jesus; Octávio Augusto de Carvalho Maia; Antonielly Campinho dos Reis; Audinei de Sousa Moura; Anderson Nogueira Mendes; Glissia Lysandra dos Santos Marciel; Jefferson da Cruz Esteves; Shamya Gabriella Corrêa Coêlho; Isabela Ribeiro de Sá Guimarães Nolêto; Maria Luísa Lima Barreto do Nascimento; Adriana Maria Viana Nunes; Débora Caroline do Nascimento Rodrigues; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Organotellurium (OTe) compounds have pharmacological properties, including leishmanicidal, antimalarial, and antifungal activities. Herein, we assessed cytotoxicity effects of OTe RF07 in a panel of tumor cell lines, as well as its oxidative, toxicity, and hemolytic actions. The toxicity was evaluated on Allium cepa and Artemia salina larvae. Cell viability was also assessed by resazurin in murine cells (Sarcoma 180), human cells (HL-60, leukemia; AGP01, gastric adenocarcinoma; SKMEL-28, human melanoma; MRC-5, normal fibroblasts), and dog erythrocytes. The oxidative capacity of RF07 was evaluated by wild-type and antioxidant-mutated enzyme strains of Saccharomyces cerevisiae . RF07 presented cytotoxic action on all normal and tumor cells, whose IC 50 ranged from 0.07 μg/mL (HL-60) to 73.45 μg/mL (Sarcoma 180) and toxicological activity on A. salina nauplii in a concentration-dependent manner after exposure for 24 h and 48 h (LC 50 values of 15.02 and 5.43 μg/mL for 24 h and 48 h, respectively). Moreover, RF07 reduced mitotic index of meristematic A. cepa cells at 5, 10 and 20 μg/mL, caused arrest in interphase, and increased chromosomal changes, including micronucleus, c -metaphases, and chromosomal bridges, loss, and delays. In summary, RF07 exhibits antiproliferative action on animal cells, high toxicity on Artemia salina nauplii, as well as clastogenic effects on growing roots. This antimitotic action is not related to direct membrane damage, although it relies on chromosomal injuries and may be related to the induction of oxidative stress as observed in yeast cells.

Pollen Diversity in Bromeliaceae (Poales): A Morphological and Micromorphological Review - Pedro Schwambach de Almeida; Jordano Dorval Tavares Carvalho; Igor Musauer Kessous; Elton Martinez Carvalho Leme; Everton Hilo de Souza; Isabela da Silva Rosa; Cláudia Barbieri Ferreira Mendonça; Jorge Ernesto Araujo Mariath; Vania Gonçalves-Esteves (The Botanical Review, 2026)
Bromeliaceae exhibits significant pollen diversity. Within the family, pollen grains are dispersed either as monads or tetrads and may be monosulcate, bi-, tri-, tetra-, or pantoporate, or even inaperturate. Ornamentation includes reticulate, foveolate, microreticulate, perforate, or psilate patterns. Additional variations are observed in the margins of the apertures and in the exine deposition on the aperture membrane. In general, pollen grains are relatively well-documented in Bromeliaceae. However, there is a lack of systematization and organization to provide a comprehensive and integrated understanding of its pollen structure. This study aims to conduct a general review of pollen morphology in Bromeliaceae, analyze character diversity based on the current phylogeny of the family, and propose the ancestral states of pollen traits. The study sampled 127 species from 47 genera, supplemented by literature data of 220 species (from 14 additional genera). Together, this dataset encompasses over 70% of the genera in the family and includes species from all subfamilies. Ancestral character states were inferred through a maximum parsimony approach. The identified ancestral states include monads as the dispersal unit, heteropolarity, bilateral symmetry, medium size, a basic elliptical shape, monosulcate pollen, a simple sulcus type, margin type III (Puya type), and reticulate ornamentation. Bromelioideae is eurypalynous, with a predominance of biporate pollen grains in Core Bromelioideae. Tillandsioideae is considered stenopalynous, characterized by monosulcate pollen grains. However, the subfamily shows considerable variation in sulcus types. Pitcairnioideae is also stenopalynous and monosulcate but exhibits significant variation in the sulcus and ornamentation. The remaining subfamilies display less variation and are stenopalynous. This study provides a comprehensive overview of pollen diversity in Bromeliaceae and highlights its evolutionary patterns, offering a basis for further research on character evolution and systematics of the family.

Palynological study of species of Bromeliaceae belonging to subfamilies with restricted occurrence (Brocchinioideae, Hechtioideae, Lindmanioideae, Navioideae, and Puyoideae) - Pedro Schwambach de Almeida; Isabela da Silva Rosa; Francis M. Almeida; Cláudia Barbieri Ferreira Mendonça; Jorge Ernesto de Araújo Mariath; Vania Gonçalves-Esteves (Palynology, 2026)

Evaluation of maropitant’s analgesic and tissue relaxation effects during ovariohysterectomy in bitches - Figueirinhas Pedro; Rodríguez Raquel; Almeida Cristian; Iusupova Kseniia; Batista Miguel (The Veterinary Journal, 2026)

Retraction notice to “Spatial and temporal distribution of urban heat islands” [Sci. Total Environ. 605–606 (2017) 946–956] - Alexandre Rosa dos Santos; Felício Santos de Oliveira; Aderbal Gomes da Silva; José Marinaldo Gleriani; Wantuelfer Gonçalves; Giselle Lemos Moreira; Felipe Gimenes Silva; Elvis Ricardo Figueira Branco; Marks Melo Moura; Rosane Gomes da Silva; Ronie Silva Juvanhol; Kaíse Barbosa de Souza; et al. (Science of The Total Environment, 2026)

Promoter Engineering of the Surfactin Operon Enhances Surfactin Production in the Environmental Strain Bacillus subtilis RI4914 - Michelle Fernandes Almeida; Fernanda de Souza Freitas; Bruna Almeida Leão Ayupe; Janine T. Bossé; Denise Mara Soares Bazzolli; Victor Satler Pylro; Pedro Marcus Pereira Vidigal; Humberto Josué de Oliveira Ramos; Edmo Montes Rodrigues; Marcos Rogério Tótola (Current Microbiology, 2026)
This study aimed to enhance surfactin production in Bacillus subtilis by replacing the native promoter of the surfactin synthase operon (P srfA ) with the strong IPTG-inducible promoter Pgrac to address challenges in large-scale biosurfactant production. The engineered strain was developed through homologous recombination, creating an integration cassette fused via overlap extension PCR and transformed into B. subtilis RI4914. Surfactin yields were assessed via oil spreading and UPLC-MS. Results showed that surfactin synthesis in the modified strain was nearly absent without IPTG. With IPTG, however, production surged 8.4-fold compared to the wild type, reaching 4.8 g/L. Productivity and carbon source yield also improved 8-fold and 11-fold, respectively. This promoter engineering strategy significantly enhanced surfactin production, with the observed increase being consistent with the expected behavior of IPTG-inducible Pgrac systems in Bacillus subtilis, suggesting an effective regulatory response associated with the tested expression system.

Meta-analysis of woody plant diversity and aboveground biomass stock co-benefits across Amazon agroforestry systems - Thamires Campos de Almeida; Silvio Nolasco de Oliveira Neto; Arthur da Cruz Silva; Rodrigo Gomes Gorsani; Lorena Evangelista Fernandes; Sebastião Venâncio Martins; Mehdi Heydari; Andrés Iván Prato; Lisandra Mendes Louzada-Camilo; Ana Luiza Rangel; Jamerson Souza da Costa; Alisson Lopes Rodrigues; et al. (Agroforestry Systems, 2026)

Mapping therapeutic alternatives: a systematic review of preclinical drug repurposing for schistosomiasis - Bruna Cristiane Souza França; Demis Ferreira de Melo; Lucas Amadeu Gonzaga da Costa; Maria Lavinya Arruda da Rocha; Vladimir Veloso Almeida; Maria Joanellys dos Santos Lima; Laysa Creusa Paes Barreto Barros Silva; Pedro José Rolim Neto (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Schistosomiasis is an acute and chronic illness caused by parasites of the genus Schistosoma . It is present in 79 countries worldwide and primarily affects socioeconomically vulnerable populations due to exposure to infested water during daily activities. Praziquantel is the primary drug used in international schistosomiasis treatment. However, adverse effects and parasite resistance mechanisms have been reported, ranging from experimentally induced resistance to naturally occurring resistance in real-world populations. New therapeutic targets have been identified to address these issues. Consequently, drug repurposing is often considered a faster alternative that may offer lower development risks and potentially fewer adverse outcomes than newly synthesized drugs. Building on this potential, this study aimed to identify drug repurposing candidates as alternatives for schistosomiasis treatment through a systematic review. Two databases (ScienceDirect and PubMed) were searched. The selection of studies and writing of this systematic review followed the PRISMA guidelines. Of the 313 articles identified, 28 were selected after applying the exclusion criteria. The best results observed were celecoxib (over 90% for egg burden and parasite load), mefenamic acid (92% for parasite load and 82% for egg burden), and chlorambucil (75% parasite load and 85% egg burden). This review highlights the data supporting this strategy as a viable alternative for developing new therapies for schistosomiasis. As these compounds have been used clinically for a long time, substantial preclinical, biosafety, and pharmacovigilance data are already available. Their adverse effects and toxicities are well characterized, which may contribute to a reduction in overall costs and development timelines, although robust clinical validation remains a prerequisite for their use.

Monitoring birds interacting with power lines: a systematic review of detection technologies and the persistent gap in transmission line applications - Ícaro Menezes Pinto; Luiggi Cavalcanti Pessôa; Pedro Ricardo Nery Nunes Silva; Gabriela Gama da Silva Santos; Viviane Spencer Andrade; Benito Rafael Santana de la Torre; Pedro Emanuel Santos Machado; Eduarda Silva Almeida; Larissa Donida Biasotto; Alessandra Schwertner Hoffmann; Michele Ferreira Lima; Ricardo Abranches Felix Cardoso Junior; et al. (Environmental Monitoring and Assessment, 2026)
Bird collisions with transmission lines (TLs) cause significant bird mortality worldwide, yet technological solutions targeting this infrastructure remain critically underdeveloped. This systematic review synthesizes 58 peer-reviewed articles and 86 patents on bird detection and collision mitigation technologies for TL infrastructure, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Although designed to capture the state of the art for TLs, most of the retrieved literature and patents originated from the aviation and wind energy sectors, where economic loss and human safety drive investment rather than biodiversity conservation. This asymmetry constitutes the central finding of the review: among studies directly targeting TL contexts, 73.7% focus exclusively on detection, and only 8.1% of patents are explicitly oriented toward biodiversity conservation outcomes. Among studies addressing detection, deep learning architectures dominate, particularly convolutional neural networks (CNNs); You Only Look Once (YOLO) variants are the most frequently reported, though they are not patentable as open architectures. Patent analysis, restricted to TLs and substations, revealed a sigmoidal growth trajectory, with artificial intelligence and computer vision (AI/CV) patents approaching saturation ( K = 33.53) by 2023 and passive mechanical deterrence patents by 2024 ( K = 44.33), driven predominantly by Chinese filings (95.3% of patents). However, a persistent structural gap remains: TL-specific applications represent a minority of the evidence base, and AI models trained predominantly on aviation and wind-farm datasets exhibit domain-shift limitations that constrain transferability to TL contexts. Addressing this gap requires investment in TL-specific datasets, field validation, and policy frameworks that position bird conservation as a primary driver of innovation.

Population‐specific bycatch risks in two vulnerable anadromous clupeids: Insights from otolith microchemistry - David J. Nachón; Alejandro Pico‐Calvo; Françoise Daverat; Rufino Vieira‐Lanero; Rosa M. Crujeiras; Ana F. Belo; Catarina S. Mateus; Bernardo Quintella; Pedro R. Almeida; Carlos Antunes; Gilles Bareille; Christophe Pécheyran; et al. (Journal of Fish Biology, 2026)
Otolith microchemistry analysis revealed that bycatch of European shads, allis shad Alosa alosa and twaite shad Alosa fallax , in western Iberian commercial fisheries removes individuals from a wide array of natal origins, with the most abundant source rivers suffering the heaviest losses. Spatial variation in bycatch risk was evident: Specific marine areas exhibited high natal origin diversity, reflecting complex dispersal. Alosa alosa showed extensive medium‐ and long‐distance movements, including rare longitudinal displacements along the Cantabrian slope, and greater natal origin diversity than A. fallax , whose dispersal was largely restricted to middle‐distance, latitudinal migrations. In both species, bycatches were dominated by the most abundant continental populations, Mondego and Minho for A. alosa , and Ulla and Minho for A. fallax , suggesting that these rivers function as source populations exporting individuals to sink populations through marine dispersal. Despite their differing dispersal ranges, both species displayed dual resident–dispersive contingents coexisting within the same populations, reflecting an interplay of river proximity, philopatry and resource availability. The stronger philopatry and constrained range of A. fallax imply heightened vulnerability to localized bycatch pressure near natal rivers, whereas A. alosa 's broader dispersal and higher origin diversity expose multiple populations to risk at a regional scale. These species‐specific dispersal capacities and metapopulation structures critically shape bycatch vulnerability. Incorporating natal origin and dispersal data into transnational, ecosystem‐based management, such as targeted temporal or spatial fishing restrictions at mixing hotspots, will be essential to safeguard metapopulation dynamics, mitigate bycatch mortality and maintain ecological connectivity among European shad populations.

Assessing coral nursery performance on reefs in Northeast Brazil under bleaching and anthropogenic pressures - Karina Massei; Maria Cecilia Silva Souza; Larissa Fernandes de Lavor; Carlos Alberto Cavalcanti Soares; Márcia Elisabeth Dementshuk; Amanda de Souza Vasconcelos; Patrícia de Moura Almeida; George Emmanuel Cavalcanti de Miranda; Pablo Riul; Frederico Gustavo Rodrigues França; Pedro Costa Guedes Vianna; Celso Augusto Guimarães Santos; et al. (Marine Pollution Bulletin, 2026)

Development and analytical validation of the first LAMP assays for the detection of Echinococcus vogeli - Leandro Batista das Neves; Tuan Pedro Dias-Correia; Thiago Cordeiro Pereira; Fernanda Bittencourt-Oliveira; Fernanda Barbosa Almeida; Héctor Gabriel Avila; Rosângela Rodrigues-Silva (Veterinary Parasitology, 2026)

Biobased coatings composed of xylans, cellulose nanofibers, and ionic liquids for the fabrication of multifunctional coated papers for food packaging - José M. Silva; William M. Facchinatto; Bernardo L. Tavares; Cátia Vieira; Inês Mendonça; Adelaide Almeida; Carla Vilela; Pedro C. Branco; João Martins; Mara G. Freire; Armando J.D. Silvestre; Carmen S.R. Freire (Food Packaging and Shelf Life, 2026)

Nursery habitat use of juvenile meagre (Argyrosomus regius): findings from acoustic telemetry in the Tagus estuary - João P. Marques; Pedro R. Almeida; Nuno Prista; José Lino Costa; Carlos M. Alexandre; Catarina S. Mateus; Isabel Domingos; Patrick Reis-Santos; Bernardo R. Quintella (Marine Biology, 2026)
We used acoustic telemetry to investigate the nursery habitat use of 33 juvenile meagre Argyrosomus regius (mean size = 581 ± 105.1 mm), recording more than 60,000 detections in the Tagus estuary, located in the North-Eastern Atlantic. All individuals used the nursery area from spring to autumn, and a small number (22.2%) remained in the Tagus estuary during winter. Daily movements averaged 6.2 ± 1.9 km, with maximum daily distances reaching 41.2 ± 17.3 km. Peak movement activity was observed in July-October (average distance = 367.3 ± 240.3 km), and predominantly during the night. Furthermore, larger sized individuals returned to the Tagus estuary in subsequent years, typically using this habitat from May to October for an average of 108.5 ± 43.0 days. Spatial analyses indicated that the lower and middle sections of the Tagus estuary serve as important nursery habitats year-round, whereas the upper estuary functions as a nursery primarily from March through June. Network movement analyses highlighted that specific areas in the middle and lower reaches exhibit higher movement activity. Generalized additive modelling indicated that the occurrence of juvenile meagre in the Tagus estuary was significantly influenced by temporal and environmental variables, including day of the year, salinity, dissolved oxygen, and temperature, measured both in the estuary and in the adjacent coastal area. These findings enhance our understanding of the habitat use in estuarine nursery areas and emphasise the importance of incorporating targeted fisheries management strategies in nursery areas to promote the sustainability of this ecologically and economically important fish.

Embryotoxic effects of diflubenzuron active ingredient and commercial formulations: comparative insights from zebrafish model - Amanda de Azevedo Valle; Rafaella Silva Brito; João Pedro Camargo Mitne; Victoria Marcella Ferreira Almeida; Aline Isabella de Souza; Flavio Kiyoshi Tominaga; Aline Garnevi Fávero; Maria Célia Sanches Oliveira Luz; Anna Virginia Pike; Maysa Zungolo Burrattino; Fábio Kummrow; Bruno Fiorelini Pereira (Ecotoxicology, 2026)

Labeling for Sustainability: Evaluating a Label‐of‐Origin Scheme in Diadromous Small‐Scale Fisheries in Portugal - Maria S. Campoverde; Natasa Bellou; Elisabeth Julien; Inês Oliveira; Silvia Pedro; João Pereira; Pedro R. Almeida; Catarina S. Mateus; Joana Boavida‐Portugal (Fisheries Management and Ecology, 2026)
Diadromous fish such as Petromyzon marinus and Alosa alosa support economically and culturally important small‐scale fisheries in Portugal but face increasing pressures such as habitat degradation, climate change, and overexploitation. In response, a voluntary label‐of‐origin system was introduced in selected river basins to enhance product differentiation and improve traceability. This study evaluates the implementation and performance of this initiative in the Mondego and Vouga river basins. A mixed‐methods approach combined analysis of labeling records with stakeholder interviews and questionnaires, complemented by a multi‐criteria assessment of implementation challenges. Results indicate generally positive stakeholder perceptions regarding trust and market valorization; however, adoption remained inconsistent and highly dependent on institutional facilitation. Key constraints included limited traceability information, operational difficulties in tag application, and fragmented governance responsibilities. The findings suggest that while voluntary labeling initiatives may enhance product transparency and perceived value, their effectiveness depends on operational feasibility, regulatory integration, and sustained institutional support. This case study provides empirical insights into the opportunities and limitations of traceability‐based instruments for governance and management in inland small‐scale fisheries.

Microbial pollution disables the chemical defenses of sea fans - Felipe V. Ribeiro; Henrique F. Santos; Thayssa S.F. Fagundes; Davyson L. Moreira; Gustavo E. de Paula; Pedro Almeida; Bruna M. Saliba; Flávia L. Carmo; Carlos E.L. Ferreira; Renato C. Pereira (Marine Pollution Bulletin, 2026)

Cryptophthalmia, microphthalmia, oronasal malformation, and hydrocephalus in an aborted equine fetus with umbilical torsion in the state of Mato Grosso, Brazil - Daniel Felipe Barrantes Murillo; Gabriela Camillo; Bruna Souza Serrano; Letícia Perri Almeida Luciano; Gabriela Viana Castilho Bichara; Carlos Alberto Chaves Vás; Fernando Henrique Furlan Gouvêa; Pedro Eduardo Brandini Nespoli; Rosa Helena dos Santos Ferraz; Caroline Argenta Pescador (Veterinary Research Communications, 2026)
Facial abnormalities and brain defects in aborted equine fetuses are rarely reported, and the causes that predispose the occurrence of this condition are difficult to identify. This work reports the morphological and tomographic findings of a case of cryptophthalmia, microphthalmia, oronasal malformation, and hydrocephalus in an aborted equine fetus with umbilical cord torsion in the state of Mato Grosso, Brazil, from a primiparous Quarter Horse female, with 7 months of gestational age. The occurrence of miscarriage was associated with compromised maternal-fetal blood flow due to umbilical cord torsion concomitant with fetal malformation. The congenital defects described in this report occurred sporadically, and it was not possible to determine the cause. The concurrent presentation of congenital malformations and umbilical torsion in equine fetuses is exceptionally rare, and this report includes the first description of the use of computer tomography for the characterization of fetal congenital malformation.

Exploring SmDHODH inhibition: natural products with potential anti-schistosomiasis activity - Rafaela Molina de Angelo; Michell de Oliveira Almeida; João Pedro Portilho Encide; Henrique Barbosa; Daniel da Silva De Sousa; Aldineia Pereira da Silva; Marina Sena Mendes; Maria Cristina Nonato; Albérico Borges Ferreira Da Silva; João Henrique Ghilardi Lago; Kathia Maria Honorio (In Silico Pharmacology, 2026)
Schistosomiasis is a parasitic disease affecting millions worldwide, highlighting the urgent need for effective treatments. This study investigated a new potential site on Schistosoma mansoni dihydroorotate dehydrogenase ( Sm DHODH) and identified natural compounds as inhibitors from in silico and experimental techniques. Molecular docking and dynamics simulations revealed significant interactions between Sm DHODH and ent -kaur-16-en-19-oic acid (3) and 15β-senecioil-oxi-ent-kaur-16-en-19-oic acid (4). The complex formed by compound 3 and the biological target showed the lowest free binding energy, indicating greater stability. Experimental assays indicated that compound 3 significantly reduced Sm DHODH activity (40 ± 2% at 250 µM), while compound 4 had minimal effect (90 ± 1%). Structural analyses revealed that hydrophobic interactions at site 1 and conformational changes induced by compound 3 are crucial for effective enzyme inhibition. Therefore, from the computational and experimental approaches employed in this study, we were able to understand a possible mechanism related to the Sm DHODH inhibition and the discovery of a potential bioactive compound against this important target related to schistosomiasis.

Cold plasma as a sustainable strategy for enzyme inhibition in plant diseases and postharvest losses: a review - Thaís Caroline Buttow Rigolon; Gabriel Oliveira Horta; Diego Pádua de Almeida; Paulo Cesar Stringheta; Evandro Martins; Lêda Rita D'Antonino Faroni; Ernandes Rodrigues de Alencar; Pedro Henrique Campelo (Journal of Stored Products Research, 2026)

Enhancing water management and natural resource use in tropical grassland systems under semi-arid conditions: Dual Kc approach - Cleber Pereira Alves; Danielle da Silva Eugenio; Luciana Sandra Bastos de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Carlos André Alves de Souza; Gabriel Italo Novaes da Silva; João Pedro Alves de Souza Santos; Wilma Roberta dos Santos; Álefe Chagas de Lima Costa; Leonardo Francelino de Souza; Jandis Ferreira Nunes de Araujo; Ênio Farias de Franca e Silva; et al. (Biomass and Bioenergy, 2026)

Relationship between Hg accumulation and diet in bats from Atlantic forest reserves - Cristiane dos Santos Vergilio; Diego Borges de Aguiar; Lucas Damásio; Diego Lacerda; Pedro Vianna Gatts; Eduardo de Sá Mendonça; Marcelo Gomes de Almeida; Beatriz Ferreira Araújo; Aureo Banhos; Carlos Eduardo de Rezende (Ecotoxicology, 2026)
Bats are valuable bioindicators of Hg contamination due to their wide representation across food webs, broad distribution, and high species richness worldwide. This study evaluated the influence of feeding habits and stable isotopes (δ¹³C and δ¹⁵N) on Hg concentrations in bats from a protected forest complex in southeastern Brazil. We collected road-killed bats ( n = 100) along a highway crossing protected areas between 2012 and 2017. The mean Hg concentration (5.6 mg/kg; range: <0.003–71.3 mg/kg) found in the present study was higher than values reported for bats from reference sites, comparable to levels observed in the Peruvian Amazon (an area also affected by artisanal small-scale gold mining), and considerably lower than those measured in populations from highly contaminated regions. Hg concentrations did not vary with forearm length or sex but differed among feeding guilds, following the order: carnivorous > insectivorous > omnivorous > nectarivorous > frugivorous. Higher δ¹⁵N values and Hg concentrations observed in insectivorous bats likely reflect their diet of invertebrates, while lower δ¹⁵N values in frugivorous and nectarivorous bats are consistent with primarily plant-based diets. Differences in δ¹³C values among feeding guilds indicate variation in carbon sources and habitat use. In this study, 23% of bats exceeded the sub-clinical threshold of 5 mg/kg, a level associated with potential neurological and neurochemical effects. These findings demonstrate the influence of feeding guilds on δ¹³C, δ¹⁵N, and Hg concentrations in a tropical bat assemblage from the Atlantic Forest, highlighting their potential as sentinels for monitoring Hg contamination. Given their ecological diversity and varied feeding strategies, bats provide valuable insights into Hg sources and pathways within ecosystems. The susceptibility of insectivorous bats underscores the need to prioritize this group in future monitoring programs and conservation strategies, particularly in tropical ecosystems where high bat diversity coincides with intense anthropogenic pressures.

Multi-replicon Architecture Drives the Global Accumulation of Resistance to Antimicrobials, Biocides, and Metals in IncF and IncH Plasmids - Hannay Crystynah Almeida de Souza; Arlen Carvalho de Oliveira Almeida; Carlos Adam ConteJunior; Pedro Panzenhagen (Current Microbiology, 2026)
Plasmids are major vectors driving the environmental dissemination of antimicrobial resistance (AMR) and other stress-resistance traits. The convergence between AMR and tolerance to multiple environmental stressors has become increasingly concerning, as these interactions intensify horizontal gene transfer and enhance plasmid conjugation. In this study, we investigated whether the co-occurrence of resistance determinants against different stressors results from random aggregation or statistically meaningful associations. We analyzed 25,116 complete plasmids from PLSDB and applied multivariate correspondence analysis to examine relationships between incompatibility groups and resistance categories. Pairwise co-occurrence patterns among resistance genes were assessed using Fisher’s exact test to determine whether their distribution deviated from randomness. IncF and IncH plasmids emerged as the incompatibility groups most strongly enriched in multidrug resistance, showing a marked tendency to co-carry genes conferring tolerance to antimicrobials, biocides, and metals-traits highly relevant under environmental co-selection. While pairwise tests did not reveal significant associations between specific gene pairs, the broader patterns of resistance accumulation highlight the structural evolution of plasmids via multireplicon cointegration as a primary mechanism for multi-stressor resistance. Our findings underscore the ecological importance of multireplicon plasmids, particularly those involving IncF and IncH, as high-risk vectors that sustain multi-stressor resistance in microbial communities.

pTJK, a rare Mammaliicoccus lentus phage with broad-host-range, antibiofilm, and synergistic interactions with antimicrobials against resistant Staphylococcaceae - Faizan Ahmad; Pedro Rocha Garcia; Vitor Emanuel Lanes Viana; Sandy de Almada Estanislau; Nohman Rasheed; Rafael Reis de Rezende; Eduardo Luís Menezes de Almeida; Poliane Alfenas Zerbini; Marisa Alves Nogueira Diaz; Monalessa Fábia Pereira; Marcia Giambiagi-deMarval; Ciro César Rossi (Archives of Microbiology, 2026)
Antimicrobial resistance in Staphylococcaceae poses a serious threat to human and animal health, driving the search for alternative strategies such as bacteriophage therapy. Here, we describe the isolation and characterization of pTJK, one of the first bacteriophages reported to infect Mammaliicoccus lentus , recovered together with its host strain TJK24 from sewage-contaminated stream water. pTJK is a novel lytic phage with a broad host range, capable of infecting multiple Mammaliicoccus and Staphylococcus species. It significantly reduced biofilm formation and disrupted preformed biofilms, including in non-host strains, and displayed synergistic activity with gentamicin and erythromycin. The phage remained viable under moderate temperature and pH variations, UV exposure, and chloroform treatment. Genome analysis revealed a 135.8 kb double-stranded DNA genome with 231 ORFs, including multiple endolysins and depolymerases potentially involved in antibiofilm activity, and no detected resistance or host virulence genes. Comparative genomics placed pTJK within the genus Sciuriunavirus , representing a novel yet-to-be-defined species. These findings highlight the rarity, genomic distinctiveness, and biotechnological potential of pTJK, reinforcing the relevance of Staphylococcaceae phages as promising tools to combat antimicrobial resistance.

Pollen morphology, viability, and stigma receptivity of Canistrum (Bromelioideae: Bromeliaceae): implications for taxonomy and conservation - Sara Cristina Santos Oliveira; Gleice Quelle Silva dos Santos Nascimento; Pedro Schwambach de Almeida; Mônica Lanzoni Rossi; Fernanda Vidigal Duarte Souza; Lidyanne Yuriko Saleme Aona; Elton Martinez Carvalho Leme; Everton Hilo de Souza (Brazilian Journal of Botany, 2026)
Canistrum (Bromeliaceae) comprises 13 species endemic to the Atlantic Forest and is subdivided into two subgenera ( Canistrum and Cucullatanthus ). This study aimed to characterize the morphology of reproductive structures (pollen and stigma), assess pollen viability and stigma receptivity across all species of the genus, and evaluate the taxonomic, reproductive, and conservation relevance of these characters. Analyses were conducted using light microscopy (with pollen grains prepared by lactic acetolysis) and scanning electron microscopy. Pollen viability was assessed using histochemical tests and in vitro germination assays at three floral stages. Stigma receptivity was evaluated through enzymatic assays. Pollen grains are dispersed as monads and show variation in shape (oblate, suboblate, and oblate-spheroidal), polarity (apolar and subisopolar), amb (circular and elliptical), aperture (pantoporate and biporate), and exine ornamentation, consistently semitectate and reticulate-heterobrochate to foveolate, with differences in lumen structure depending on the presence of granules. The occurrence of distinct pollen types proved informative for infrageneric delimitation within Canistrum . Stigmas are conduplicate-spiral, with stigmatic lobes ranging from crenulate to laciniate, and coloration varying from white to yellow. Pollen viability was high in all species, especially during anthesis, a stage that also showed the highest in vitro germination rates. Stigma receptivity peaked at anthesis and remained high during post-anthesis, indicating synchrony between pollen and stigma and suggesting the absence of dichogamy. Overall, pollen aperture type and exine ornamentation are stable characters of taxonomic value, whereas viability, germination, and receptivity patterns provide insights into reproductive strategies, supporting conservation and reproductive management of endemic and threatened Canistrum species.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Exploring EnMAP hyperspectral images and ensemble deep learning for classifying forest land-cover types in Brazil - Matheus Pinheiro Ferreira; Matheus Santos Fuza; José M. S. M Viveiros; Tomás Ferranti; Dário Oliveira; Giulio Brossi Santoro; Paulo Guilherme Molin; Catherine Torres de Almeida; Angélica F. Resende; Danilo R. A. de Almeida; Yelu Zeng; Ricardo Ribeiro Rodrigues; et al. (International Journal of Remote Sensing, 2026)

Seasonal exposure alters climate change vulnerability estimates of marine species - Miguel Pinto; Juan Bueno-Pardo; João Nuno Monteiro; Pedro Sousa; Vânia Baptista; Joana Cruz; Marta Albo-Puigserver; Miguel Gaspar; Ana B. Barbosa; Filipe Martinho; Maria Alexandra Teodósio; Martinho Marta-Almeida; et al. (Journal of Environmental Management, 2026)

Monitoring the reserve effect of a coastal no-take area in the northeast Atlantic along the first ten years of implementation - Ana Filipa Silva; José Lino Costa; Patrícia Teodoro; João J. Castro; Pedro Raposo de Almeida; Bernardo Ruivo Quintella (Ocean & Coastal Management, 2026)

The land use-climate change-biodiversity nexus in the perceptions of European islands stakeholders - Aristides Moustakas; Irene Christoforidi; George Zittis; Nazli Demirel; Mauro Fois; Savvas Zotos; Eirini Gallou; Valentini Stamatiadou; Elli Tzirkalli; Christos Zoumides; Kristina Košić; Aikaterini Christopoulou; et al. (Environmental Impact Assessment Review, 2026)

Insights into chemical profile and leaf anatomy in the dioecious species Baccharis platypoda: sex-related differences and environmental patterns - Fábio Cassola; Guilherme Perez Pinheiro; Carina de Araujo; João Pedro Silvério Pena Bento; Guilherme Almeida Garcia Rodrigues; Alexandra Christine Helena Franklan Sawaya; Alex Aparecido Rosini Silva; Ingrid Koch; Adilson Sartoratto; Patrícia de Oliveira Carvalho; Juliana Lischka Sampaio Mayer (Protoplasma, 2026)

Hydrochar amendment in weathered soil: impacts on fertility, plant growth, and herbivore fitness in the soil–plant system - Isabela Carreira Constantino; Ciro Pedro Guidotti Pinto; Kelly Cristina Gonçalves; Beatriz Ariani Casagrande; Ana Clara Pereira Annelli; Vinicius Sarracini Santos; Altair Benedito Moreira; Fernanda Vasconcelos de Almeida; Ricardo Antonio Polanczyk; Márcia Cristina Bisinoti (Plant and Soil, 2026)
Background and aims The application of hydrochar (HC) to soil has beneficial effects, but few studies have evaluated its impact on soil–plant-insect systems. This study investigated the effects of HC derived from sugarcane vinasse and bagasse on soil properties, dissolved organic matter (DOM), plant development, and the performance of a key herbivore. Methods HC application was performed on maize and tomato crops in an Ultisol at doses of 5, 15, and 30 t ha −1 . Plant growth parameters (biomass, length, height, and chlorophyll index), soil β-glucosidase activity, and the quantity and quality of leached organic matter were measured, along with Spodoptera frugiperda (fall armyworm- FAW) fitness traits (larval viability and weight). Results In the short term, the lowest HC dose significantly enhanced tomato growth (p < 0.05). The responses of β-glucosidase activity and soil DOM indicate that enzymatic stimulation depends on both the HC rate and the presence of mineral fertilization. Furthermore, HC induced plant resistance, as evidenced by antibiosis effects on FAW (p < 0.05), reducing larval viability by up to 44% when insects were fed maize leaves, in addition to sublethal effects such as decreased larval weight, and for tomato, an average reduction of 22.96% in viability. Conclusion Therefore, the application of HC as a soil conditioner, in addition to its effects on soil fertility and plant growth, has been shown to have an antibiosis effect on the fall armyworm (FAW). Further investigations, such as the expression of genes and metabolites of the plant defense system, need to be conducted to elucidate the mechanisms of action involved. Graphical abstract

Greenhouse pre-screening of banana somaclones derived from the Grand Naine cultivar (Cavendish, AAA) resistant to Fusarium oxysporum f . sp. cubense, subtropical race 4 - Tamyres Amorim Rebouças; Anelita de Jesus Rocha; Mileide dos Santos Ferreira; Wanderley Diaciso dos Santos Oliveira; Fernanda dos Santos Nascimento; Welly Sacramento Santana; Tamires Souza Cerqueira; João Pedro Falcón Lago de Jesus; Vanusia Batista de Oliveira Amorim; Janay Almeida dos Santos-Serejo; Fernando Haddad; Claudia Fortes Ferreira; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)
Banana production is affected by several pests and diseases, of which Fusarium wilt, caused by Fusarium oxysporum f. sp. cubense (Foc), is notable. Despite the different control measures and management used to contain Fusarium wilt, the development of resistant cultivars has been the best approach to combating this disease. This study explores a biotechnological approach with the potential to induce somaclonal variation using the plant growth regulators Thidiazuron (TDZ) and paclobutrazol® (PBZ) in the banana cultivar ‘Grand Naine’ (Cavendish, AAA), and proposes a greenhouse pre-screening based on inoculation bioassays with Foc, using the commercial cultivar Grand Naine as a susceptible control. The somaclonal variants showed 3.5% of highly resistant plants, which were immune to Foc inoculation in the first round of tests. Of these, thirteen (43.3%) maintained their resistance response when subjected to a second test in an experiment with replicates. In addition, histological analysis of roots demonstrated the absence of pathogen structures, such as hyphae, conidia, or chlamydospores, within the tissues of these somaclones. This study provides Cavendish somaclones that have never before been generated and pre-selected under greenhouse conditions. These somaclones will be further evaluated for agronomic and market potential, as well as for validation of resistance stability, with the aim of future recommendation to farmers and use in breeding programs.

Systematic review update of organisational-level mental health promotion interventions: evidence from healthcare, construction, and telework-based mobile work settings - Eleftherios Giovanis; Oznur Ozdamar; Birgit Aust; Johanna Cresswell-Smith; Arlinda Cerga Pashoja; Caleb Leduc; Andrea Sinesi; Carolina Piña; Chantal Van Audenhove; Gentiana Qirjako; Victoria Ross; Margaret Kenneally; et al. (International Archives of Occupational and Environmental Health, 2026)

Resistance of melon genotypes to Meloidogyne incognita and M. javanica: an approach based on genetic parameters estimated via REML/BLUP - Francismária Freitas de Lima; Edicleide Macedo da Silva; Nynyve Thaynar Brito de Almeida; Antonio Cesar de Araujo Filho; Cintya Mikaelly Pereira Gaia Souza; Geovanna Alícia Dantas Gomes; Camila de Souza Alves; Denilson Eduardo Silva Dantas; Lindomar Maria da Silveira; Pedro Luiz Martins Soares; Rivanildo Júnior Ferreira; Rui Sales Júnior; et al. (Euphytica, 2026)
Melon is one of the main vegetable crops grown in Brazil and is severely affected by root-knot nematodes of the genus Meloidogyne . The identification of resistance sources is therefore essential. Estimates of genetic parameters in breeding programs provide insight into the effects underlying the traits under evaluation. The objective of this study was to identify melon accessions resistant to Meloidogyne incognita and M. javanica and to estimate genetic parameters using the REML/BLUP procedure. Four independent trials were conducted, two for M. incognita and two for M. javanica . In the initial screening trials, 41 melon accessions were evaluated. Ten accessions (nine classified as resistant to both species and one resistant only to M. incognita ) were re-evaluated to confirm resistance. In the screening trials, 71 and 26.8% of the genotypes were classified as resistant to M. incognita and M. javanica , respectively. In the confirmation trials, five genotypes retained resistance to M. incognita , whereas only two maintained resistance to M. javanica . The Scott–Knott test identified distinct groups in all trials for both nematode species. Broad-sense heritability was low to moderate, and selection accuracy was moderate. Accession AC-18 exhibited resistance to both nematode species and is a promising genotype for melon breeding programs. Five accessions were resistant to M. incognita , whereas only two were resistant to M. javanica .

Optimization of chemically activated carbon derived from malt bagasse for CO₂ adsorption: a simplex-centroid approach - Giovanna C. Carlos; Lucas H. S. Crespo; Pedro H. C. Voloch; Aline A. R. Andrade; Pedro H. V. Ribeiro; Faissal Robbin; Vitor C. Almeida; Lucas Spessato (Environmental Science and Pollution Research, 2026)
The intensification of the greenhouse effect has been primarily driven by anthropogenic CO₂ emissions, leading to significant climate change. Among the strategies to mitigate CO₂ emissions from industrial activities, adsorption using activated carbons (ACs) derived from renewable sources stands out as a promising approach. Activated carbons were prepared via chemical activation of malt bagasse, a brewing industry by-product, using NaOH, Na₂C₂O₄, Na₂CO₃, and their mixtures as activating agents. The augmented simplex-centroid method was employed to optimize the process and obtain an activated carbon (ACₒₚ) with high BET surface area. The materials were characterized by proximate analysis, N₂ physisorption, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and Raman spectroscopy. CO₂ adsorption experiments were performed at different temperatures to assess performance. The optimized carbon (ACₒₚ) exhibited a well-developed porous structure and high surface area, achieving a CO₂ adsorption capacity of 2.83 mmol g⁻ 1 at 273 K. The results demonstrated that NaOH-activated carbon provides favorable properties for CO₂ capture, confirming the feasibility of malt bagasse as a sustainable precursor for efficient adsorbent materials.

Neuroinflammation and RAMP1: the Role of the Peripheral and Central Nervous System in Tumor Progression - Pedro Daniel Moumesso Cavalcante; Jonas Lucas Dias da Silva; Laryssa Rosy Santos Oliveira; Rikelly Barbosa da Silva; Juliana Acioli Costa Lima; Guilherme de Brito Souza; Davi Ramon da Silva Santos; Júllia Victória Nascimento de Abrantes; Mateus Lima de Farias; Sofia Amancio de Almeida Oliveira; João Paulo Emiliano da Silva; Rafael de Oliveira Calaça Farias; et al. (Cell Biochemistry and Biophysics, 2026)
Calcitonin gene-related peptide (CGRP) and receptor activity modifier protein 1 (RAMP1) form a critical neuroimmunoendocrine axis in the modulation of neuroinflammation, pain, and tumor progression. CGRP, released by sensory and sympathetic fibers, is a potent vasodilator and nociceptive modulator; its action depends on the receptor composed of CALCRL and RAMP1. In the central nervous system, the activation of microglia and astrocytes and the induction of pathways such as NF-κB and MAPK culminate in the production of proinflammatory cytokines (TNF-α, IL-6), differing from systemic inflammation due to the presence of the blood-brain barrier and the glial microenvironment. Preclinical evidence demonstrates RAMP1 expression in neurons, glial cells, endothelium, and macrophages; CGRP/RAMP1 signaling promotes vascular permeability, cytokine release, and angiogenesis, potentially synergizing with VEGF. In animal models and cell cultures, genetic or pharmacological manipulations of the axis reduce tumor angiogenesis, pro-tumor immune infiltration, tumor growth, and nociceptive behavior. Given the clinical availability of CGRP antagonists and monoclonal antibodies, blocking the CGRP/RAMP1 axis is a promising translational strategy for modulating tumor progression and cancer pain. This review summarizes preclinical evidence on mechanisms and therapeutic feasibility. The article includes preclinical and clinical safety and biomarker studies.

Membrane-targeted photodynamic mechanisms of methylene violet 3RAX in melanoma models - Thais Soares de Oliveira; Mirella Boaro Kobal; André Satoshi Ferreira; Alexandre Mendes de Almeida Junior; Karina Alves Toledo; Sabrina Aléssio Camacho; Pedro Henrique Benites Aoki (Journal of Photochemistry and Photobiology B: Biology, 2026)

Encapsulation of jabuticaba (Plinia cauliflora) peel extract with whey or pea protein in combination with gum arabic enhances anthocyanin bioaccessibility and metabolite production - Larissa Lorrane Rodrigues Borges; Valdeir Viana Freitas; Janaina Gonçalves Fernandes; Amanda Lais Alves Almeida Nascimento; Hélia de Barros Kobi; Evandro Martins; Pedro Henrique Campelo Felix; Stephen T. Talcottt; Paulo César Stringheta (Food Chemistry, 2026)

Natural chlocarbazomycins as potential adenosine A1 receptor antagonists: ligand-based and structure-based virtual screening, quantum chemical analysis and CNS MPO study - Emanuelle Machado Marinho; Francisco Nithael Melo Lúcio; Matheus Nunes da Rocha; Victor Moreira de Oliveira; Francisco Wagner Queiroz de Almeida-Neto; Márcia Machado Marinho; Emmanuel Silva Marinho; Pedro de Lima-Neto (Molecular Diversity, 2026)
Parkinson’s disease (PD) is a neurodegenerative disorder that causes irreversible damage to brain structures through neurotransmitter oxidation, leading to motor symptoms like tremors and muscle rigidity. Although existing therapies target monoamine oxidase B, recent research has highlighted​​ a correlation between adenosine A 1 and A 2A R receptors in inhibiting dopamine reuptake, as observed in rats. Chlocarbazomycins (CCB), carbazole derivatives with neuroprotective properties, show potential for central nervous system (CNS) therapies. This study examines the structural and bioactivity properties of four carbazomicin derivatives (CCB1-4) using quantum-level Density Functional Theory (DFT) calculations, virtual screening, and a predictive pharmacokinetics study. The results showed that different environments (water, DMSO, and chloroform) had minimal impact on the reactivity of CCB1-4 derivatives. Structure-based virtual screening revealed that the heteroaromatic nature of CCB1-4 closely resembles that of adenosine (ADN), the endogenous ligand for A 1 R receptors. Molecular docking showed that CCB3 had the highest affinity for the receptor, with a binding energy of − 8.6 kcal/mol at the ADN agonist site. Molecular dynamics simulations confirmed the stable binding of CCB3, with a free energy of − 25.9 kcal/mol, suggesting that CCB3 may act as an antagonist to ADN in A1R modulation. The results of predictive pharmacokinetic studies indicate that the compound exhibits high passive cell permeability ( P app, A→B > 10 × 10 − 6 cm/s) and low hepatic clearance, which collectively ensure the safe activity of the compound in the CNS. These findings suggest that CCB3 has potential in PD treatment.

Plant sources and fermentation in cellular agriculture and alternative Proteins: A review - Diean Fabiano Alvares Pinheiro; Bibiana Porto da Silva; Bruna Silva de Farias; Débora Pez Jaeschke; Janaína Oliveira Gonçalves; Pedro Minasi Brandão; Luiz Antonio de Almeida Pinto; Anelise Christ-Ribeiro (Trends in Food Science & Technology, 2026)

Water mass influence on the distribution of larval mesopelagic fish (Sternoptychidae) in the South Brazil Bight (23°S-28°S) - Gabriel Vilanova; Maria de Lourdes Zani-Teixeira; Mario Katsuragawa; Ulisses Cavalcante dos Santos; Marcelo Dottori; Danilo Augusto Silva; Ilson Carlos Almeida da Silveira; João Pedro Mancio de Amorim; Frederico Pereira Brandini; Cláudia Namiki (Journal of Marine Systems, 2026)

Enantioselective toxicity of 3,4-methylenedioxypyrovalerone in Daphnia magna: Assessment of morphophysiological, behavioural, biochemical and reproductive responses - Ariana Pérez-Pereira; Ana R. Carvalho; Pedro A. Costa; Bruno B. Castro; João S. Carrola; Virgínia M.F. Gonçalves; Ana R.L. Ribeiro; Ana Sofia Almeida; Carla Fernandes; Maria E. Tiritan; Cláudia Ribeiro (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Associations Between APOE Polymorphisms, Neurological Symptoms, and Cognitive Assessments in Long COVID Patients: An Analysis of SNPs rs7412 and rs429358 - Isadora de Almeida Gomes; Pedro Braga-Neto; Thiago Loreto Matos; Emerson Lucena da Silva; Lais Lacerda Brasil de Oliveira; Luina Benevides Lima; José Wagner Leonel Tavares-Júnior; Alissa Elen Formiga Moura; Marcello Holanda de Andrade; Thaís de Maria Frota Vasconcelos; Reinaldo Barreto Oriá; Danilo Nunes Oliveira; et al. (Molecular Neurobiology, 2026)

All Reforestation Methods Can Support Tropical Tree Diversity Recovery, but Drivers and Species Composition Vary - Laura E. Boeschoten; Joannès Guillemot; Juliano van Melis; Lourens Poorter; Ricardo R. Rodrigues; Frans Bongers; Paulo G. Molin; Marielos Peña‐Claros; Vinicius C. Souza; Cássio A. P. Toledo; Patrick Faria Fernandes; Marcelo P. Ferreira; et al. (Global Change Biology, 2026)
Tropical landscapes are undergoing rapid transformation due to human activities and global change. Forest restoration has emerged as a key strategy to mitigate biodiversity loss and climate warming. However, a standardized assessment of how different restoration methods contribute to biodiversity recovery and conservation remains lacking. Here, we present the first comprehensive comparison of tree diversity restoration and the drivers of recovery across five main reforestation methods (naturally regenerating forests, biodiverse restoration plantings, short‐ and long‐rotation tree monocultures, agroforests) relative to three reference systems (agropastoral lands, degraded and conserved forest remnants). Tree inventories were conducted in 519 plots (900 m 2 each) across two forest types (rainforest and seasonally dry forest) in the Atlantic forest of São Paulo state, Brazil, encompassing over 39,000 trees and 869 species. We found that: (1) all reforestation methods except short‐rotation monoculture plots supported tree diversity recovery. In the rainforest, conserved remnant plots maintained the highest average Shannon diversity (Hill 1 = 29 ± 14), while naturally regenerating forests and restoration plantings approached the diversity of degraded remnant plots (15 ± 5). In seasonally dry forest, biodiverse restoration plantings and agroforests reached diversity levels comparable to conserved remnants (15 ± 6). Additionally, (2) recovery was influenced by forest age, climate (water availability), soil fertility, and landscape context, though the relative importance of these factors varied by method. Climate and landscape context were more influential for recovery in naturally regenerating forests, while soil conditions played a greater role in biodiverse restoration plantings. Lastly, (3) species composition in naturally regenerating forests most closely resembled that of conserved remnants. Conversely, restoration plantings and agroforests exhibited high compositional overlap across sites, reducing overall species richness. Our findings underscore the wide variation in biodiversity outcomes among and within reforestation methods, emphasizing that goals and strategies must align with local conditions to maximize benefits in complex tropical landscapes.

Rural dogs (Canis familiaris) as sentinels to ectoparasites and tick borne pathogens around six Atlantic Forest conservation units in Brazil - Pedro Henrique Cotrin Rodrigues; Nelson Henrique de Almeida Curi; Elizabete Pereira Barbosa; Guilherme Ramos Demétrio; Ana Maria Oliveira Paschoal; Rodrigo Lima Massara; Adriano Garcia Chiarello; Marcelo Passamani; Camila Stefanie Fonseca de Oliveira; Daniel Sobreira Rodrigues; Júlia Angélica Gonçalves Silveira (Veterinary Parasitology, 2025)

Multi-element profile (essential and potentially toxic elements) of seaweeds from the northeast coast of Brazil - João Pedro Cezário Brandão; Keila Almeida Santana; Thaís Luz de Souza; Eliabe Sousa da Silva; Laura Beatriz Souza e Souza; Ivana Ferreira Simões; Jorge Machado Freitas Júnior; Daniele Cristina Muniz Batista Santos; José Marcos de Castro Nunes; Gustavo Souza dos Santos; Djalma Lucas Sousa Maia; Aníbal de Freitas Santos Júnior (Regional Studies in Marine Science, 2025)

Mangrove squeeze potential due to combined effect of sea level rise and decadal human land use and changes in a sub-tropical estuarine environment - Luis Pedro Almeida; Lauren Cruz; Maiara Werner Pinto; Débora Lugli-Bernardes; Andreia Silva; Antonio Henrique da Fontoura Klein (Regional Studies in Marine Science, 2025)

An effective formulation from Annona squamosa L. Leaves against Aedes aegypti - Lucas Gabriel Pita dos Santos; Lívia Laís de Santana Silva Barbosa; Gabriel da Silva Coutinho; Emerson de Oliveira Silva; Júlio Cesar Ribeiro de Oliveira Farias de Aguiar; Glaucilane dos Santos Cruz; Alvaro Aguiar Coelho Teixeira; Valéria Wanderley Teixeira; Patrícia Maria Guedes Paiva; Daniela Maria do Amaral Ferraz Navarro; Pedro José Rolim Neto; Thiago Henrique Napoleão; et al. (Journal of Asia-Pacific Entomology, 2025)

Brazilian Latossolos (Ferralsols, Oxisols) from different biomes: a multiproxy study on the spatial variability of the most weathered tropical soils in South America - Carlos Ernesto Gonçalves Reynaud Schaefer; Rafael Gomes Siqueira; Luís Flávio Pereira; Lucas de Carvalho Gomes; Pedro Henrique Araújo Almeida; Márcio Rocha Francelino; Francis Henrique Tenório Firmino; José João Lélis Leal de Souza; João Carlos Ker; Elpídio Inácio Fernandes-Filho (Geoderma Regional, 2025)

Monitoring soil conservation techniques via UAV for sustainable production of intercropped forage cactus with reuse water in the Brazilian semiarid region - Lizandra de Barros de Sousa; Abelardo Antônio de Assunção Montenegro; Jorge Manuel G.P. Isidoro; Thieres George Freire da Silva; Thayná Alice Brito Almeida; João Luis Mendes Pedroso de Lima; Pedro Rogério Giongo; Alexandre Maniçoba da Rosa Ferraz Jardim; Marcos Vinícius da Silva; Ênio Farias de França e Silva; Breno Leonan de Carvalho Lima (Field Crops Research, 2025)

Modern colonialism in carbon markets? Insights from emergy accounting - Pedro Pierucci; Feni Agostinho; Federico Sulis; Cecília M.V.B. Almeida; Biagio F. Giannetti (Ecological Modelling, 2025)

Identification of a mouse-virulent recombinant type I/III Toxoplasma gondii strain in liver cytology of an immunosuppressed cat infected with FeLV–C subgroup - Joana Fonseca; Pedro Almeida; Sónia Campos; Vítor Borges; Anabela Vilares; Tânia Reis; Maria João Gargaté; Adriana Belas (Veterinary Research Communications, 2025)

Polymorphisms in STAT4 and PTPRC genes in rheumatoid arthritis: a Brazilian study and meta-analysis of susceptibility and TNFi response - João Locke Ferreira de Araújo; Ingrid Marins de Almeida; Pedro Augusto Silva dos Santos Rodrigues; Lilian de Sá Garcia Landeiro; Laryssa Cardoso Calmon; João Victor Andrade Cruz; Aramis Tupiná Alcântara de Moreira; Junison de Oliveira Santos; Gabriela Pimentel Pinheiro; Álvaro Augusto Souza da Cruz Filho; Camila Alexandrina Viana de Figueiredo; Pablo de Moura Santos; et al. (Immunologic Research, 2025)

Influence of Moisture and Cement Content on the Undrained Shear Response of Iron Ore Tailings - Nilo Cesar Consoli; Aziz Tebechrani Neto; Alexia Cindy Wagner; João Vítor de Azambuja Carvalho; Lessandro de Almeida Franco; João Pedro Camelo Guedes; João Paulo de Sousa Silva (Geotechnical and Geological Engineering, 2025)

Molecular and histochemical characterization of Grande Naine somaclones resistant to Fusarium oxysporum f. sp. cubense subtropical race 4 - Wanderley Diaciso dos Santos Oliveira; Tamyres Amorim Rebouças; Anelita de Jesus Rocha; Mileide dos Santos Ferreira; Tiago Abreu da Silva; Amanda Bahiano Passos Sousa; Andresa Priscila de Souza Ramos; João Pedro Falcón Lago de Jesus; Janay Almeida dos Santos-Serejo; Fernando Haddad; Claudia Fortes Ferreira; Edson Perito Amorim (Euphytica, 2025)

Intersecting realms of resistance: the epidemiology of Staphylococcus aureus carriage and multidrug resistance in primary healthcare settings in Recife, Brazil - Iago Carvalho Barbosa; Denny Parente de Sá Barreto Maia Leite; Pollyanne Raysa Fernandes de Oliveira; Órion Pedro da Silva; Maria Luisa Araújo Quinderé de Almeida; Taoana Perrelli Sarmento; Rafaela Silva Santos; José Givanildo da Silva; Maira Aparecida Scatamburlo Moreira; Tatiana Souza Porto; Rinaldo Aparecido Mota (Brazilian Journal of Microbiology, 2025)

Geographic Patterns of Fog‐Driven Isotopic Niches and Root Adaptations in Cacti Across the Arid‐to‐Hyperarid Gradients of the Atacama Desert - Sandy Toledo; José Angel García‐Beltrán; Ángela Sierra‐Almeida; Francisco A. Squeo; Juan Pedro Ferrio; Pablo C. Guerrero (Journal of Biogeography, 2025)
Aims Hydrological niche specialisation supports plant survival in hyperarid deserts by enabling access to distinct water sources in space and time. We investigated the isotopic hydrological niches of Eriosyce cacti across arid to hyperarid zones along a 1200 km gradient in the Atacama Desert. Using stable isotopes (δ 2 H, δ 18 O) in root water, we identified their primary water sources and evaluated how geographic and morphological factors shape water‐use strategies under extreme environmental constraints. Location Atacama Desert, Chile. Time Period From June 2021 to November 2023. Data collection was conducted as a single sampling event per population. Major Taxa Studied Eriosyce (Cactaceae). Methods We quantified the isotopic niches of 323 individuals across 62 populations representing 49 Eriosyce taxa. Deuterium excess was calculated to measure evaporative enrichment, and Bayesian mixing models were applied to characterize water source contributions (fog, rainfall, and snow). We then examined how these patterns relate to root morphology (fibrous, taproot, tuberous) and geographical gradients, using generalized phylogenetic least squares models based on Eriosyce Bayesian phylogeny. Results Overall, Eriosyce cacti spanned a broad isotopic spectrum. Fibrous‐rooted forms had notably negative Deuterium excess (D‐excess), while species with tuberous or taproots displayed more positive values (ANOVA, F = 32.05, p F = 179.6, p p p p p Main Conclusions Our findings reveal diverse, locally adapted water‐use strategies among Eriosyce cacti, highlighting how hydrological niche specialisation enables these species to endure in one of the world's most hyperarid deserts. This underscores the critical role of heterogeneous water sources, especially fog, in maintaining cactus diversity under harsh conditions.

Experimental assessment of beauvericin toxicity in tadpoles of Dendropsophus minutus (Anura: Hylidae) - Monica Chacon de Vicente; Luiza Gabriella Ferreira de Paula; Renata Maria Pereira de Freitas; Adieli dos Anjos Almeida; Diego da Silva Lima; Rebeca dos Santos Gabriel; Nathany Geraldino Nogueira; Nádya Raquel dos Santos Batista; Alexandre Có Mangoni Barros; Marcelino Benvindo de Souza; Rogério Pereira Bastos; Pedro Vale de Azevedo Brito; et al. (Toxicon, 2025)

Roles of predator–prey interactions and environmental drivers in sandy beach macrofauna populations - Vitor Figueira Arueira; Pedro Vianna Gatts; Fabio Bozzeda; Marcelo Gomes de Almeida; Carlos Eduardo de Rezende; Ilana Rosental Zalmon; Carlos Alberto de Moura Barboza; Lucia Fanini; Omar Defeo; Leonardo Lopes Costa (Marine Environmental Research, 2025)

The goat Longissimus thoracis et lumborum muscle proteome: effects of dry ageing and cooking in chevon - Menalda Valeriano André; Catarina Prista; Vítor D. Alves; David M. Ribeiro; Miguel Filipe Pedro; Laura Sacarrão-Birrento; Hugo Osório; André M. de Almeida; Teresa J.S. Matos (Food Research International, 2025)

Phytochemical diversity, antioxidant potential, antimicrobial activity, cytotoxicity, and genotoxicity analyses of unconventional food plants: Cymbopogon citratus (DC.) Stapf, Pereskia aculeata Mill., Portulaca oleracea L., and Talinum paniculatum (Jacq.) Gaertn. - Caroline dos Santos Giuliani; Carla Andressa Almeida Farias; Patrícia Kolling Marquezan; Karoline Longo de Aguiar; Pedro Henrique Fortes Guerim; Elize Aparecida Santos Musachio; Nathália Cardoso de Afonso Bonotto; Fernanda Barbisan; Milene Teixeira Barcia; Ana Lúcia Souza Silva Mateus; Aline Sobreira Bezerra; José Laerte Nörnberg (Food Chemistry, 2025)

Electroanalytical detection of nitrates, nitrites, and N-nitrosamines in foods - Pedro Antônio Arantes Palhano; Isadora Ponciano Almeida; Lorranne Marins-Gonçalves; Djenaine De Souza (Food Chemistry, 2025)

Enhancing bivalve depuration using a phage cocktail: An in vitro and in vivo study - Pedro Costa; Carla Pereira; Juan L. Barja; Jesús L. Romalde; Adelaide Almeida (Food Control, 2025)

Adhesion performance from nano and molecular — To macro insights for bio-based adhesives - Juliana Martins da Silva; Pedro Ivo Cunha Claro; Romana Petry; James Moraes de Almeida; Jefferson Bettini; Marcos Vinicius Lorevice; Adalberto Fazzio; Rubia Figueredo Gouveia (Chemical Engineering Journal, 2025)

Impact of thiamethoxam on Folsomia candida and Hypoaspis aculeifer in artificial and natural soils - Milena Cristina Azevedo Gloria; Juliane Gomes da Silva; Pedro Henrique do Nascimento-Silva; Renato de Almeida Sarmento; Grasiele Soares Cavallini; Vanessa Bezerra de Menezes-Oliveira (Ecotoxicology, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Beyond the scrotal circumference: Exploring phenotypic, nutritional and metabolic traits associated with early sexual development in young Nelore (Bos indicus) bulls - Bruna Lima Chechin Catussi; Romulo Germano de Rezende; Pedro Nacib Jorge-Neto; Laura Nataly Garcia-Oliveros; Emanuele Almeida Gricio; Lucas Oliveira e Silva; Eneiva Carla Carvalho Celeghini; Pietro Sampaio Baruselli (Theriogenology, 2025)

Alternative habitat use strategies in the catadromous Chelon ramada inferred by otolith microchemistry - Esmeralda Pereira; Françoise Daverat; Bernardo R. Quintella; M. João Lança; Pedro R. Almeida (Marine Environmental Research, 2025)

Mapping groundwater contamination risk in a periurban watershed in northeast Brazil - Matheus Natan Ferreira Alves de Sousa; Caio Victor Macêdo Pereira; Bárbara Hillary de Almeida Pinto; Diego Allysson Gomes Araujo; Pedro Júlio Castro dos Santos; Gabriel Dalla Rosa Carvalho; José Arthur do Nascimento Ramalho; Júlia Mairla Santos Herculano; Nixdali Freire de Oliveira; Francisca Luciana Bevenuto Gonzaga; Raíssa Cássia Andrade de Souza; Erizangela de Abreu Barbosa; et al. (Journal of South American Earth Sciences, 2025)

Effect of CuO nanoparticles from yerba mate on germination and initial growth of lettuce and tomato seeds - Juliana De Gregori da Rocha; Guilherme Almeida Garcia Rodrigues; Júlia Tirroni; Pedro Ezequiel Keller; Paulo Tamaso Mioto; Cíntia Soares; Natan Padoin; Humberto Gracher Riella (Journal of Environmental Chemical Engineering, 2025)

Petrophysical log responses of a core-drilled from the granite-gneiss complex of the Rio Negro Magmatic Arc (Neoproterozoic of Rio de Janeiro State, Southeastern Brazil) - Viktor Souto Louback; Patrick Führ Dal’ Bó; Pedro Henrique Alves Novaes; Caio Almeida Paula; Caio Almeida Carvalho; Marco Antônio Braga; João Paulo Porto Barros; Maria Filipa Perez Gama; Alan Souza Cunha (Journal of Applied Geophysics, 2025)

Recovery of tree species functional composition in eucalypt plantations with natural regeneration differs among canopy strata - Laura H.P. Simões; Marielos Peña-Claros; Joannès Guillemot; Rens Brouwer; Frans Bongers; Lourens Poorter; Catherine T. de Almeida; Danilo R.A. Almeida; Miguel Cooper; Mathieu Decuyper; José G. Fernandes Neto; Matheus S. Fuza; et al. (Forest Ecology and Management, 2025)

CRISPR-Cas systems in combating antimicrobial resistance: which system to choose? A systematic review - Hannay Crystynah Almeida de Souza; Pedro Panzenhagen; Ana Beatriz Portes; Anamaria M. P. dos Santos; Juliana Fidelis; Carlos Adam Conte Junior (World Journal of Microbiology and Biotechnology, 2025)

How to mitigate UHI and heat-related mortalities with urban strategies and policy adaptations?? A review - Mahmoud Ouria; Anibal T. de Almeida; Pedro Moura; André T. de Almeida; Shabnam Yaghoubi kondelaji (Mitigation and Adaptation Strategies for Global Change, 2025)

Physical Interactions between Cancer Cells and Tumor Microenvironment - Andressa Beatriz Apolinário da Silva Correia; Beatriz Medeiros de Souza Melo; Bruna Alves da Silva; Giovana Cruz Maciel; Guilherme Matheus Santos Marques Cavalcante; João Pedro Almeida dos Santos; Layza Maria Barbosa Silva; Luís Filipe Pereira Rocha; Maria Beatriz Cavalcante Brêda; Maria Eduarda Teixeira de Oliveira; Kayo Felipe Barbosa Lima; Luiz Ben-Hur de Oliveira Wanderley Nepomuceno; et al. (Cell Biochemistry and Biophysics, 2025)

Seroprevalence of Trypanosoma cruzi in household and shelter dogs in the northeastern region of Brazil - Carolina Ferreira de Oliveira; Pedro Levi Nascimento Oliveira; Jussara Nayanne dos Santos Nascimento; Márcia Kikuyo Notomi; Gabriela de Lima Rodrigues Pinto; Bruna Nobre de Souza; Victoria Gamboa Braga; Vitória Maximiana Soares dos Santos; Luiz Daniel de Barros; Hélio Langoni; Simone Baldini Lucheis; Jonatas Campos de Almeida (Topics in Companion Animal Medicine, 2025)

Mercury contamination in Amazon traditional populations: Metalloproteomic study associated with exposure frequency - Nubya Gonçalves Cavallini; Felipe Dalmazzo Cirinêu; José Cavalcante Sousa Vieira; Emerson Carlos de Almeida; Joyce Andrade da Silva; Victor Diego Faria; Tania Machado da Silva; Marcelo de Oliveira Lima; Luis Fabricio Zara; Jiri Adamec; Marília Afonso Rabelo Buzalaf; Pedro de Magalhães Padilha (Journal of Hazardous Materials, 2025)

Dynamic of infectious aerosols generated by cough from patients with pulmonary tuberculosis - Taline Canto Tristão; Mariana Abou Mourad Ferreira; Pedro Sousa de Almeida Júnior; Luiz Guilherme Schmidt Castellani; Manuela Negrelli Brunetti; Edward C. Jones-López; Kevin P. Fennelly; Michael R. Barer; Carlos Henrique Fantecelle; Saulo Almeida Morellato; David Jamil Hadad; Jerrold J. Ellner; et al. (Journal of Aerosol Science, 2025)

Functional recovery of tropical forests: The role of restoration methods and environmental conditions - Rens Brouwer; Marielos Peña-Claros; Frans Bongers; Lourens Poorter; Joannès Guillemot; Danilo R.A. Almeida; Catherine Torres de Almeida; Angélica F. Resende; Laura H.P. Simões; Natália M. Ivanauskas; Renato A. Ferreira de Lima; Vinicius Castro Souza; et al. (Biological Conservation, 2025)

Gene expression analysis and halting of ethylene receptors signaling pinpoint ethylene as a positive regulator of direct somatic embryogenesis in Coffea arabica - Natalia Gomes Vieira; Cesar Augusto Nascimento; Ilse Fernanda Ferrari; Mariana Silva Sartorello; Juliana Costa de Rezende; Daniela de Argollo Marques; Angelo Pedro Jacomino; Julieta Andrea Silva de Almeida; Jorge Maurício Costa Mondego (Planta, 2025)

In vitro effects of the new antifungal compound manogepix (APX001) against the three most clinically relevant species of Sporothrix - Fernando Almeida-Silva; Fernanda Praça Nogueira Marques; Pedro Henrique Tenório-Alvarenga; Vanice Rodrigues Poester; Melissa Orzechowski Xavier; Rosely Maria Zancopé-Oliveira; Rodrigo Almeida-Paes (Brazilian Journal of Microbiology, 2025)

Morphological responses of Eucalyptus demonstrate the potential of Trichoderma harzianum to promote resistance against Leptocybe invasa - Louis Antoniel Joseph; Nívea Maria Pereira Lima; Pedro Augusto Laurindo Rocha; Aloísio Freitas Chagas Júnior; João Pedro Laurindo Rocha; Jéssica Soares Pereira; Auxiliadora Oliveira Martins; Cristiano Bueno de Moraes; Márcio Leles Romarco de Oliveira; Wagner Luiz Araújo; Maíra Ignacio Sarmento; Renato Almeida Sarmento (Brazilian Journal of Microbiology, 2025)

Long‐Term Impact of the Largest Environmental Disaster in Latin America (Fundão Dam Failure) on Microbial Communities in Lakes of the Doce River Basin, Brazil - Pedro Almeida; André Torres; Marcelos Gomes; Ernesto Caffarena; Hugo Jesus; Pedro Pereira; Katariny Pereira Dos Santos; Carlos Eduardo Delfino Vieira; Yuri Dornelles Zebral; Camila Martins; Adalto Bianchini; Henrique Santos (Environmental Microbiology, 2025)
The collapse of the Fundão tailings dam in 2015 stands as the largest environmental disaster in Latin America and the global mining industry. This catastrophic event released around 62 million m 3 of mining waste into the Doce River basin. This study aimed to assess the long‐term effects of the disaster by analysing microbial communities in four lakes within the Doce River basin. Conducted over 4 years (2018–2021), with a total of six sampling campaigns. The microbiome of water and sediment was analysed using high‐throughput 16S rRNA gene sequencing. The results demonstrate a significant correlation between key microbial groups and metals associated with the disaster, including Deinococcus , Thermoanaerobaculaceae , Pirellula , and Rhodospirillaceae . Moreover, an enrichment of genes associated with xenobiotic degradation and metal metabolism pathways was detected. These findings suggest that microbial communities in the lakes remain functionally adapted to metal contamination, potentially playing a crucial role in ecosystem recovery and bioremediation. These microorganisms could be leveraged to monitor and mitigate the effects of heavy metal contamination. Despite years having passed since the disaster, the microbiota of the lakes remains significantly impacted, reinforcing the need for continued research to fully understand and mitigate long‐term ecological consequences.

Investigation of Cereus jamacaru DC. cladode extract for chemical composition and effects against pathogenic bacteria and Aedes aegypti L. larvae - Júlia Maria Rodrigues Guimarães; Lucas Gabriel Pita dos Santos; Alex Michel Silva Araújo; Welton Aaron de Almeida; Lidiane Quérolin Macena da Silva; Júlio César Ribeiro de Oliveira Farias de Aguiar; Emerson de Oliveira Silva; Isabella Coimbra Vila Nova; Ana Beatriz Sotero Siqueira; Maria Tereza dos Santos Correia; Márcia Vanusa da Silva; Rômulo Carlos Dantas da Cruz; et al. (South African Journal of Botany, 2025)

Evaluating the safety profile of rosuvastatin in pregnant Wistar rats: Bridging gaps in reproductive safety data - Diego dos Santos Reis; Graziele Alícia Batista Caixeta; João Pedro Monteiro Barbosa; Júlio César Gonçalves Guimarães dos Reis; Monatha Nayara Guimarães Teófilo; Camila Cristina Alves Machado; Ricardo Silva Tavares; Jorge Radif Rassi Filho; Clayson Moura Gomes; Wilson de Melo Cruvinel; Eduardo José de Almeida Araújo; Vanessa Cristiane Santana Amaral (Reproductive Toxicology, 2025)

Promoting a circular economy: Wastewater toxicity removal using activated carbon produced from industrial sludge - Keivison Almeida Monteiro; Ann H. Mounteer; Renata Pereira Lopes Moreira; José Pedro Rodrigues Ferreira; Aline Aparecida dos Santos Silva; Caroline Piccoli Miranda de Freitas; Jodieh Oliveira Santana Varejão (Journal of Environmental Chemical Engineering, 2025)

A new population of the threatened torrent-frog Hylodes sazimai and other possible suitable sites based on ecological niche modeling - João Pedro Bovolon; Natália Aranha; Pedro P.G. Taucci; Carlos Henrique L. Nunes-de-Almeida; Luís Felipe Toledo (Journal for Nature Conservation, 2025)

On the propagation and surface chlorophyll-a signature of long-lived Brazil Current eddies - Ian Ramos de Almeida; João Pedro Mancio de Amorim; Pedro Walfir Martins e Souza-Neto; Ilson Carlos Almeida da Silveira (Ocean Dynamics, 2025)

Insecticidal efficacy and chemical profile of Handroanthus impetiginosus extracts for sustainable management of the coffee leaf miner (Leucoptera coffeella) - Andriely B. Silva; Daniel L. Montagnini; Albert Katchborian-Neto; Miller Santos Ferreira; João V. Andrade; Guilherme Otoni Francisco; Pedro S. S. R. Cavallari; Samarah G. Almeida; Enes P. Barbosa; Wilson R. Cunha; Marisi G. Soares; Murilo de Oliveira Souza; et al. (Journal of Plant Diseases and Protection, 2025)

Determination of the volatile chemical profile of Momordica charantia (bitter melon) leaf and fruit by GC-MS - Natália Ferreira Almeida; Edenilson dos Santos Niculau; Pedro Cordeiro Toledo Lima; Wanderson Ferreira da Silva (Natural Product Research, 2025)

Partial laryngectomy in a cat with thyroid cartilage osteochondroma: Surgical management and postoperative care - Paloma Helena Sanches da Silva; Luíza Bortolotti de Carvalho; Pedro Antônio Bronhara Pimentel; Isabella Oliveira Almeida; Bruna Voltolin de Sena; Paula Baêta da Silva Rios Turquete; Tatiana Geraissate Gorenstein; Eutálio Luiz Mariani Pimenta; Bruno Ferrante; Patrícia Maria Coletto Freitas; Rodrigo dos Santos Horta (Topics in Companion Animal Medicine, 2025)

Droughts, livestock expansion, and Forest degradation: A 37-year assessment of landscape change in a semiarid municipality of Brazil - Francisco Éder Rodrigues de Oliveira; Eveline de Almeida Ferreira; Rodrigo Fernandes; Victor Neudo Santos Tavares; Yara de Almeida Araújo; João Luiz Lima; Luiz Fernando de Sousa Antunes; Noely Raiana da Costa Chagas; Pedro Lucas Nogueira de Freitas; Cirley Tavares Lemos; Ayslan do Nascimento Fernandes; Eulene Francisco da Silva (Science of The Total Environment, 2025)

Assessing the impact of climate-induced heatwaves on habitat conditions for reservoir fish communities - Manuel Almeida; Pedro Coelho (Ecological Modelling, 2025)

The Seaward Migration of European Eel at a Continental Scale: A Europe‐Wide Biotelemetry Meta‐Analysis - Pieterjan Verhelst; David Righton; Kim Aarestrup; Pedro R. Almeida; Tea Bašić; Jonathan D. Bolland; Liam Carter; Johan Coeck; José Lino Costa; Justas Dainys; Jan Grimsrud Davidsen; Isabel Domingos; et al. (Fish and Fisheries, 2025)
The European eel ( Anguilla anguilla L.) has a catadromous life cycle, with a single panmictic population that colonises continental Europe and northern Africa yet migrates 5000 to 9000 km to spawn in the Atlantic Ocean. It is unknown how this continental migration is organised so individual eels arrive in time for spawning with conspecifics. This meta‐analysis combined tracking data from 18 water bodies in freshwater and transitional systems distributed along the southwest‐northeast axis of Europe, resulting in a dataset of 2306 eels, making it the most comprehensive in terms of geographical coverage and number of eels tagged. The eels were tracked using acoustic telemetry and the Nedap Trail System and allowed us to study the eel's migration phenology at a continental scale. The findings reveal that the day when eels arrive at sea varies significantly with latitude, with northern eels arriving earlier. Migration speed differs between tidal and non‐tidal habitats, suggesting that tidal currents facilitate faster movement. However, despite these patterns, we observed substantial variability in arrival at sea time and migration speed within water bodies, suggesting that the eel's migration phenology is considerably plastic. The presence of water regulating structures such as weirs, pumping stations and hydropower plants can impact migration timing and speed, potentially delaying eels, but is likely dependent on local hydrological conditions which can be water body specific.

Antinociceptive and anti-inflammatory effects of essential oil from Lippia thymoides MART. & SCHAUER (VERBENACEAE) - David Souza Silva; Pedro Modesto Nascimento Menezes; Jamilly Araújo Santos; Jackson Roberto Guedes da Silva Almeida; Luciano Augusto de Almeida Ribeiro; Juliane Cabral Silva; Angélica Maria Lucchese; Raimundo Gonçalves de Oliveira Júnior; Fabrício Souza Silva (Natural Product Research, 2025)

Chemical emissions from offshore wind farms: From identification to challenges in impact assessment and regulation - Elena Hengstmann; Pablo Zapata Corella; Katharina Alter; Maria J. Belzunce-Segarra; Andy M. Booth; Javier Castro-Jiménez; Niklas Czerner; Karien De Cauwer; Geneviève Deviller; Alessio Gomiero; Nils Goseberg; Simone Hasenbein; et al. (Marine Pollution Bulletin, 2025)

Life cycle assessment of the Brazilian minipig bred for biomedical research and education: A case study - Gustavo Fonseca De Almeida; Ariadna Bàllega; João Pedro Queiroga Maluf; M. Andón; Marta Ruiz-Colmenero; Montserrat Núñez (Science of The Total Environment, 2025)

Edge effect impacts on forest structure and carbon stocks in REDD+ projects: An assessment in the Amazon using UAV-LiDAR - Leo Eiti Haneda; Pedro H.S. Brancalion; Denis Valle; Carlos Alberto Silva; Eric Bastos Gorgens; Gabriel Atticciati Prata; Renan Akio Kamimura; Silvio H.M. Gomes; Arthur K. Sanchez; Danilo Roberti Alves de Almeida (Forest Ecology and Management, 2025)

Forage cactus as a substitute for corn as an energy source in the finishing of feedlot lambs - Pedro Henrique Borba Pereira; Juliana Silva de Oliveira; Ricardo Romão Guerra; Ângela Imperiano da Conceição; André Luiz Rodrigues Magalhães; Dulciene Karla de Andrade Silva; Safira Valença Bispo; Geane Gonçalves Dias; Cleyton de Almeida Araújo; Roberta de Lima Valença; Daniel Barros Cardoso; Airon Aparecido Silva de Melo (Tropical Animal Health and Production, 2025)

Sustainable urban mitigation strategies regarding heat-related mortalities and thermal discomfort: an overview and comparative analysis - Mahmoud Ouria; Andre Almeida; Shabnam Yaghoubi Kondelaji; Pedro Moura; Anibal T. de Almeida (Theoretical and Applied Climatology, 2025)
This study provides an overview and comparative analysis of sustainable urban mitigation strategies to address heat-related mortalities and thermal discomfort. Employing a comprehensive literature review and quantitative analysis, it evaluates various interventions—including green infrastructure, building materials, urban morphology, and technological innovations—alongside their impacts on mortality rates. A novel methodology is proposed for assessing the relationship between urban design factors and heat stress-related health outcomes, with attention to vulnerable populations. Key findings reveal that each 0.1 increase in normalized difference vegetation index (NDVI) reduces heat-related mortality by 6–10% in low-GDP regions, while medical strategies such as warning systems and cooling centers lower mortality by 10–30%. However, emerging technologies like PV panels and AAHPs show localized temperature increases of up to 0.9℃. This paper highlights the critical role of balanced urban strategies to mitigate adverse effects of climate change, offering practical insights for policymakers, urban planners, and public health officials seeking sustainable solutions.

Characterizing a Tropical Soil Site using Seismic Dynamic Probing Light (SDPL) - Luis Pedro Rojas Herrera; Caio Henrique de Castro Almeida; Breno Padovezi Rocha; Heraldo Luiz Giacheti (Geotechnical and Geological Engineering, 2025)

Management intensity does not affect the ecological indicators of coffee agroforestry systems in agricultural landscapes of the Atlantic forest zone in Brazil - Vitoria Duarte Derisso; Ricardo Gomes César; Catherine Torres de Almeida; Pedro H. S. Brancalion; Danilo R. A. Almeida; Paulo G. Molin; Aline Souza; Edson Vidal (Agroforestry Systems, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

A new approach to modeling the routing problem in forest inventory planning - Antonio Almeida de Barros Junior; Gilson Fernandes da Silva; Geraldo Regis Mauri; Adriano Ribeiro de Mendonça; Helio Garcia Leite; Carlos Pedro Boechat Soares; Maria Alice Romanha Belumat (Computers and Electronics in Agriculture, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Evaluating the population dynamics of a maize weevil under varying initial population sizes - Daiane Marques Almeida; Vanderleia dos Santos Conceição; Francielen da Silva Dias; Barbara Maria Dias de Almeida Duarte; Loren Ribeiro Figueredo; Violeta Mayra Jatoba Irarrazabal; Marcia Araujo de Jesus; Gustavo Ferreira Macedo; Carolina Martins Magalhaes; Bruno Barbosa Mendes; Crislane Barbosa das Neves; Raissa Castro Nunes; et al. (Journal of Stored Products Research, 2025)

Evaluation of quality parameters, physicochemical and bioactive properties of licuri oil (Syagrus coronata) - Gabriel Sthefano Lourenço Pereira; Patrícia Tonon de Souza; Grace Kelly Mizuno Flozino; Rafael Fernandes Almeida; Dhayna Oliveira Sobral; Marcelo Antonio Morgano; Wilton Rogério Lustri; Silmara Cristina Lazarini; Pedro Paulo Corbi; Antonio José de Almeida Meirelles; Guilherme José Maximo; Eduardo Augusto Caldas Batista; et al. (Food Research International, 2025)

From the seaweeds' carrageenan composition to the hybrid carrageenans’ hydrogel elasticity: Identification of a relationship based on the content in iota-carrageenan - Loic Hilliou; Izabel Cristina Freitas Moraes; Pedro Lúcio Almeida (Food Hydrocolloids, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Biological activities of acanthoic acid and its pharmacological potential: a literature review - Carla Brígida Teixeira Magalhães Lima; Pedro Janelson dos Santos Lima; Tatiana de Queiroz Oliveira; Pedro Henrique Freitas de Rezende; Emmanoel Vilaça Costa; Jéssica Fernandes Auzier; Melissa Pires Souza; Maria Lúcia Belém Pinheiro; Jackson Roberto Guedes da Silva Almeida; Silvania Maria Mendes Vasconcelos (Natural Product Research, 2025)

Spatially explicit assessment of carbon storage and sequestration in forest ecosystems - Bruna Almeida; Luís Monteiro; Rafaela Tiengo; Artur Gil; Pedro Cabral (Remote Sensing Applications: Society and Environment, 2025)

Effects of deforestation on multitaxa community similarity in the Brazilian Atlantic Forest - Daniel Maurenza; Renato Crouzeilles; Jayme Augusto Prevedello; Mauricio Almeida‐Gomes; Marina Schmoeler; Renata Pardini; Cristina Banks‐Leite; Marcus Vinicius Vieira; Jean Paul Metzger; Carlos Roberto Fonseca; Marina Zanin; Alex Fernando Mendes; et al. (Conservation Biology, 2025)
Habitat loss can lead to biotic homogenization (decrease in β diversity) or differentiation (increase in β diversity) of biological communities. However, it is unclear which of these ecological processes predominates in human‐modified landscapes. We used data on vertebrates, invertebrates, and plants to quantify β diversity based on species occurrence and abundance among communities in 1367 landscapes with varying amounts of habitat ( 60% of forest cover) throughout the Brazilian Atlantic Forest. Decreases in habitat amount below 30% led to increased compositional similarity of vertebrate and invertebrate communities, which may indicate a process of biotic homogenization throughout the Brazilian Atlantic Forest. No pattern was detected in plant communities. We found that habitat loss was associated with a deterministic increase in faunal community similarity, which is consistent with a selected subset of species being capable of thriving in human‐modified landscapes. The lack of pattern found in plants was consistent with known variation between taxa in community responses to habitat amount. Brazilian legislation requiring the preservation of 20% of Atlantic Forest native vegetation may be insufficient to prevent the biotic homogenization of faunal communities. Our results highlight the importance of preserving large amounts of habitat, providing source areas for the recolonization of deforested landscapes, and avoiding large‐scale impacts of homogenization of the Brazilian Atlantic Forest.

Coastal natural products: a review applied to antimycobacterial activity - Rodolfo Moreira Baptista; Marcos Alaniz Rodrigues; Fabio Roselet; César Serra Bonifácio Costa; Pedro Eduardo Almeida da Silva; Daniela Fernandes Ramos (Natural Product Research, 2025)

Reservoir eutrophication in the Brazilian semiarid: modeling of sediment removal and control of external loads as remediation measures - Eveline Menezes Rodrigues da Silva; Luccas Gois de Almeida; Pedro Henrique Augusto Medeiros; Gabriela Domingos Lima; Eunice Maia de Andrade; José Carlos de Araújo (Environmental Science and Pollution Research, 2025)

Characterising phages for the control of pathogenic bacteria associated with bivalve consumption - Pedro Costa; Carla Pereira; Vanessa Oliveira; Newton C.M. Gomes; Jesús L. Romalde; Adelaide Almeida (International Journal of Food Microbiology, 2025)

Testing classical hypotheses on sandy beach ecology with a “goldilocks” indicator species: Study case with tiger beetles (Insecta: Cicindelidae) - Leonardo Lopes Costa; Vitor Figueira Arueira; João Pedro de Almeida Caetano; Adriane Baudson do Nascimento; Beatriz Torres e Ribeiro; Échily Sartori; Henrique Simfrone da Silva Valle; Luiza Silva do Nascimento; Marcela Costa e Silva Lombardi; Danilo Freitas Rangel; Eduardo Bulhões; Ilana Rosental Zalmon (Estuarine, Coastal and Shelf Science, 2025)

Exploring the safety parameters of Athenaea velutina ethanolic extract: a step towards harnessing its medicinal potential - Jordana Luizi dos Prazeres; Alisson Andrade Almeida; Renner Philipe Rodrigues Carvalho; Luiz Carlos Maia Ladeira; Luiz Pedro de Souza Costa; Markus Kohlhoff; Leandro Licursi de Oliveira; Mariana Machado-Neves; João Paulo Viana Leite (Toxicological Research, 2025)

Performance of Canola (Brassica napus L.) Hybrids at Different Sowing Dates in a Subtropical Environment - Gustavo Rufatto Comin; Anderson Hideo Yokoyama; Renan Caldas Umburanas; João Pedro Malanchuk; Juliano Luiz de Almeida; Jackson Kawakami (International Journal of Plant Production, 2025)

Cationic photosensitizers and potassium iodide: an innovative approach for enhanced photodynamic inactivation of pathogenic bacteria in aquaculture - Cátia Vieira; Maria Bartolomeu; Carlos J.P. Monteiro; Jesús L. Romalde; Pedro P. Gallego; M. Graça P.M.S. Neves; M. Amparo F. Faustino; Adelaide Almeida (Aquaculture, 2025)

Photoinactivation of sulfate-reducing bacteria using 1,9-dimethyl-methylene blue – DMMB and laser light - Gustavo Vital dos Santos; Hesrom Fernandes Serra Moura; Pedro Jorge Louro Crugeira; Anna Paula Lima Teixeira da Silva; Isabele Cardoso Vieira de Castro; Wellington Luís Reis Costa; Paulo Fernando de Almeida; Antonio Luiz Barbosa Pinheiro (Journal of Photochemistry and Photobiology B: Biology, 2025)

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Impact of land use intensification on key drivers of soil organic carbon pools in Brazil’s Central-West - Priscila Silva Matos; Janaína de Moura Oliveira; Marcia Tais de Melo Carvalho; Beata Emoke Madari; André Luiz Rodrigues da Silveira; Júnior Melo Damian; Pedro Augusto de Oliveira Moraes; Wilker Alves de Araujo; Matheus Mentone de Britto Siqueira; Ryan Rodrigues da Silva; Tatiana Maris Ferraresi; Luis Fernando Stone; et al. (CATENA, 2025)

Microbial Occupational Exposure in e-waste Recycling: Biological Hazards, Their Sources, and Potential Toxic Effects - Carla Viegas; Bianca Gomes; Marta Dias; Renata Cervantes; Pedro Pena; Sara Gonçalves; Marina Almeida-Silva; Elisabete Carolino; Magdalena Twarużek; Liliana Aranha Caetano; Susana Viegas (International Journal of Environmental Research, 2025)
E-waste management is a major environmental concern that also poses serious risks to occupational health. While e-waste workers are exposed to a variety of chemicals, little is known about occupational exposure to microbiological agents. This study aims to fill that gap. For that purpose, two e-waste facilities were assessed: one battery-recycling facility (BRF), and another facility (SRE) dedicated to e-waste sorting and storage before sending it for different processing. Filtering respiratory protection devices (FRPD, 24 samples) and settled dust (13 samples) were collected using standardized sampling approaches, and analyzed by culture-based, chemical and molecular methods. Workers also filled in a questionnaire regarding work activities and the use of FRPD. Microbial contamination, fungal diversity, azole resistance, and prevalence of Aspergillus sections Fumigati and Flavi (as surrogates of harmful fungal contamination) and mycotoxins were determined. To estimate potential health effects related to exposure, the FRPD cytotoxicity was determined in human A549 lung and HepG2 hepatic cells. Microbial contaminants with pathogenicity and toxigenic potential were observed in FRPD and settled dust. Aspergillus section Fumigati was widespread. The observed presence of Aspergillus section Flavi relates to the risk of exposure to aflatoxin B1 (a potent hepatocarcinogen). Four different mycotoxins were detected in 8% FRPD and 15% dust samples, including fumonisin B1 and sterigmatocystin (below the limit of quantification). A low to moderate cytotoxic effect of sampled FRPD was observed, with human lung alveolar cells more sensitive than hepatic cells. No relevant azole resistance was observed, nor correlations between fungal reduced azole-susceptibility and fungal growth at 37 °C or cytotoxicity. In summary, it can be concluded that this approach using FRPD and settled dust presents a promising potential for screening occupational exposure to microbiological contaminants in e-waste management. More studies in this occupational context should be prioritized to identify critical biological hazards and to support the implementation of appropriate health risk mitigation strategies.

Pollen morphology, viability, and stigma receptivity of Hohenbergia (Bromeliaceae) species occurring in the Atlantic forest biome with potential for landscaping and cut flowers - Tiago Abreu da Silva; Gleice Quelle Silva dos Santos Nascimento; Pedro Schwambach de Almeida; Brayan Paiva Cavalcante; Fernanda Vidigal Duarte Souza; Lidyanne Yuriko Saleme Aona; Maria Angélica Pereira de Carvalho Costa; Everton Hilo de Souza (Genetic Resources and Crop Evolution, 2025)

“Together is better”: the contribution of academy, citizen science and gray literature for the knowledge of the urban avifauna of a megadiverse easternmost Amazonian ecotonal border - Sara Miranda Almeida; Gustavo Gonsioroski; Nubia Carla Santos Marques; Fernanda Guimarães Fava; João Marcelo da Silva Abreu; Letícia Gomes da Silva; Rafaela Velloso Missagia; Vanessa Guimarães Lopes; Verônica Maria de Oliveira; Erick Cristofore Guimarães; Pedro Walfir M. Souza-Filho; Valéria da Cunha Tavares (Ornithology Research, 2025)

Nutritional and technological potential of umbu-caja and soursop co-product flours - Valeria Silva de Lana; Patrícia Nayara Estevam; Thais Barcelos de Castro; Vinícius Parzanini Brilhante de São José; Thais Carvalho Brito-Oliveira; Pedro Henrique Santos; Cristiane Almeida Santos Oliveira; Cristiane Bani Corrêa; Mauricio Ariel Rostagno; Hércia Stampini Duarte Martino; Izabela Maria Montezano de Carvalho (Food Research International, 2025)

Spatial variation of metal(loid)s in sediments of an Atlantic mesotidal estuary (Sado estuary, Portugal) - José Miguel Almeida; Carla Palma; Pedro M. Félix; Ana C. Brito (Marine Pollution Bulletin, 2024)

Top 10+1 indicators for assessing forest ecosystem conditions: A five-decade fragmentation analysis - Bruna Almeida; Pedro Cabral; Catarina Fonseca; Artur Gil; Pierre Scemama (Science of The Total Environment, 2024)

Combined effects of high hydrostatic pressure and pulsed electric fields on quinoa starch: Analysis of microstructure, morphology, thermal, and pasting properties - Raphael Lucas Jacinto Almeida; Newton Carlos Santos; Marcelo da Silva Pedro; Iêda Leticia de Souza Ferreira; Raphael da Silva Eduardo; Cecilia Elisa Sousa Muniz; Vitória de Andrade Freire; Ana Carolina Nóbrega Leite; Bárbara Freire de Oliveira; Paloma Benedita da Silva; Ynis Thaciane Felix da Silva; Raimunda Valdenice da Silva Freitas; et al. (Food Chemistry, 2024)

Enhancement of phenolic compounds bioaccessibility in jabuticaba wine through fermentation by Saccharomyces cerevisiae - Larissa Lorrane Rodrigues Borges; Valdeir Viana Freitas; Amanda Lais Alves Almeida Nascimento; Janaina Gonçalves Fernandes; Hélia de Barros Kobi; Monique Renon Eller; Frederico Augusto Ribeiro de Barros; Luciana Ângelo de Souza; Gabriel Abranches Dias Castro; Arthur Figueira de Carvalho; Jaqueline de Araújo Bezerra; Sergio Antonio Fernandes; et al. (Food and Bioproducts Processing, 2024)

Structured lipids from fish viscera and coconut oils improve weight gain and intestinal morphology of piglets at nursery phase - Rennan Rômullo Silva Pinheiro; Pedro Henrique Watanabe; Lina Raquel Santos Araújo; Ingrid Barbosa de Mendonça; João José de Mesquita Sales; Marcelo Emersom Costa Santos; Leonardo Augusto Fonseca Pascoal; Ricardo Romão Guerra; Jonathan Madson dos Santos Almeida; Ednardo Rodrigues Freitas (Tropical Animal Health and Production, 2024)

40-Year Journey of Shoreline Changes Along the Benin Coast Using Satellite Data Through the CASSIE Tool - Frédéric Bonou; Raïssa Christelle Madiesseu Metem; Luis Pedro Almeida; Bapentire Donatus Angnuureng; Zacharie Sohou (Ocean Science Journal, 2024)

Microarray data analysis of antileukemic action of Cinnamoylated benzaldehyde LQB-461 in Jurkat cell line - Rachell R. C. Thimoteo; Pedro Nicolau Neto; Debora S. S. Costa; Fabrício da Mota Ramalho Costa; Douglas Cazaroti Brito; Paulo R. R. Costa; Tatiana de Almeida Simão; Ayres G. Dias; Graça Justo (Molecular Biology Reports, 2024)

In vitro probiotic potential of lactic acid bacteria isolated from the intestines of Muscovy ducks - Leandro de Carvalho Maquiné; Kelven Wladie dos Santos Almeida Coelho; Maria Fernanda da Silva Gomes; Jackelyne Ribamar Vieira; Thatiana Farias Cavalcante; Elen Bethleen de Souza Carvalho; João Paulo Ferreira Rufino; Adriano Teixeira de Oliveira; Pedro de Queiroz Costa Neto; José Odair Pereira (Brazilian Journal of Microbiology, 2024)

The spermidine promotes maturation and tissue differentiation of somatic embryos of Euterpe edulis Martius, an endangered Atlantic Forest species - Joana Silva Costa; Tamyris de Mello; Débora Pellanda Fagundes; Tatiane Dulcineia Silva; Caroline Palacio de Araujo; Ingridh Medeiros Simões; Mariana Ribeiro de Almeida; Eduardo Santos Cade; João Pedro Vieira Fraga de Assis; Edilson Romais Schmildt; Wagner Campos Otoni; Amir Ali Khoddamzadeh; et al. (In Vitro Cellular & Developmental Biology - Plant, 2024)

Extracellular vesicles from the mycoparasitic fungus Trichoderma harzianum - Gabrielle Rosa Silva; Felipe de Pina Cavalcanti; Reynaldo Magalhães Melo; Emilio Cintra; Eliana Martins Lima; Pedro Ricardo Vieira Hamann; Luis H. F. do Vale; Cirano José Ulhoa; Fausto Almeida; Eliane Ferreira Noronha (Antonie van Leeuwenhoek, 2024)

Acoustic Imaging Learning-Based Approaches for Marine Litter Detection and Classification - Pedro Alves Guedes; Hugo Miguel Silva; Sen Wang; Alfredo Martins; José Almeida; Eduardo Silva (Journal of Marine Science and Engineering, 2024)
This paper introduces an advanced acoustic imaging system leveraging multibeam water column data at various frequencies to detect and classify marine litter. This study encompasses (i) the acquisition of test tank data for diverse types of marine litter at multiple acoustic frequencies; (ii) the creation of a comprehensive acoustic image dataset with meticulous labelling and formatting; (iii) the implementation of sophisticated classification algorithms, namely support vector machine (SVM) and convolutional neural network (CNN), alongside cutting-edge detection algorithms based on transfer learning, including single-shot multibox detector (SSD) and You Only Look once (YOLO), specifically YOLOv8. The findings reveal discrimination between different classes of marine litter across the implemented algorithms for both detection and classification. Furthermore, cross-frequency studies were conducted to assess model generalisation, evaluating the performance of models trained on one acoustic frequency when tested with acoustic images based on different frequencies. This approach underscores the potential of multibeam data in the detection and classification of marine litter in the water column, paving the way for developing novel research methods in real-life environments.

First report of Meloidogyne javanica infecting Thymus vulgaris in the state of São Paulo, Brazil - Edicleide Macedo da Silva; Ricardo Koroiva; Rivanildo Júnior Ferreira; Daniel Dalvan do Nascimento; João Pedro Peixoto Fernandes; Benedito Charlles Damasceno Neves; Antonio Cesar de Araujo Filho; Rafaelle Fazzi Gomes; Nynyve Thaynar Brito de Almeida; Andréia Mitsa Paiva Negreiros; Pablo Forlan Vargas; Laura Raissa Fagundes Costa Bezerra; et al. (Crop Protection, 2024)

Energy savings and emissions reduction of BEVs at an isolated complex intersection - Radha Reddy; Luis Almeida; Pedro M. Santos; Harrison Kurunathan; Eduardo Tovar (Transportation Research Part D: Transport and Environment, 2024)

Treatment of metastatic apocrine sweat gland adenocarcinoma in a cat with association of surgical resection and angular oris reconstruction, extensive lymphadenectomy, electrochemotherapy and systemic chemotherapy - Pedro Antônio Bronhara Pimentel; Isabella Oliveira Almeida; Bruna Voltolin de Sena; Sarah Kowalczyk; Geovanni Dantas Cassali; Rodrigo dos Santos Horta (Topics in Companion Animal Medicine, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Improving the accuracy of an integrated watershed-reservoir water quality modeling approach (SWAT and CE-QUAL-W2) in data scarce watersheds - Manuel Almeida; Pedro Coelho (Journal of Hydrology, 2024)

Insecticidal activity of extracts of handroanthus impetiginosus on Plutella xylostella (Lepidoptera: plutellidae) larvae - Andriely B. Silva; Daniel L. Montagnini; Albert Katchborian-Neto; João V. Andrade; Hallana A. Manuquian; Pedro S. S. R. Cavallari; Samarah G. Almeida; Enes P. Barbosa; Wilson R. Cunha; Marisi G. Soares; Mario F. C. Santos; Márcio L. A. Silva; et al. (Natural Product Research, 2024)

The frequency of the ACE I/D polymorphism in South America: a systematic review and meta-analysis - Rebeca Gonçalves Trevisano; Helen Matias; Thais de Jesus Teani; Valmir Oliveira Silvino; Cirley Pinheiro Ferreira; Marcos Antonio Pereira dos Santos; Pedro Luiz Garcia Braga; Sandro Soares Almeida (Molecular and Cellular Biochemistry, 2024)

Evapotranspiration measurements in pasture, crops, and native Brazilian Cerrado based on UAV-borne multispectral sensor - Gabriella Santos Arruda de Lima; Manuel Eduardo Ferreira; Jepherson Correia Sales; Joelson de Souza Passos; Selma Regina Maggiotto; Beata Emoke Madari; Márcia Thaís de Melo Carvalho; Pedro Luiz Oliveira de Almeida Machado (Environmental Monitoring and Assessment, 2024)

Desorption of mineral-bound phosphorus across different cropping systems and agronomic strategies to promote efficient input use - Juan Pablo Almeida; Dries Roobroeck; Linda-Maria Dimitrova Mårtensson; Pedro Rosero; Geoffrey Kimutai; Thomas Kätterer; Håkan Wallander (Applied Soil Ecology, 2024)

Fully protected marine areas linked to reduced home ranges of fishes - Sarah Ohayon; David Abecasis; Pedro R. Almeida; Josep Alós; Eneko Aspillaga; Ana Filipa Belo; José Lino Costa; Antonio Di Franco; Manfredi Di Lorenzo; Adrian Ferguson; Paolo Guidetti; Sebastian Kraft; et al. (Fish and Fisheries, 2024)
Home range size is a fundamental trait that can affect the probability of fish being harvested and, at the same time, may be affected by fishing. The relationship between home range size and fishing will impact the effectiveness of fully protected areas (FPAs), as it will influence the number of fish moving into fished areas, affecting both spillover and edge effects. One hypothesis is that individuals within FPAs will present reduced home range size relative to individuals in fished areas. This pattern can be driven by demographic selection (e.g. fishing of individuals with large home ranges leaving the FPAs), improved habitat requiring less foraging movements, or behavioural changes associated with reduced fishing threats. To test the relationship between home range size and protection, we compiled 1143 individual‐level home range sizes based on acoustic tracking, covering 17 species from 11 FPAs in 7 countries, with information on distance from FPA borders. A dichotomic analysis (in/out of FPAs) did not support a significant change in the home range size between FPAs and fished areas. However, continuous analysis across the FPA borders demonstrated reduced home range size within the FPAs. We did not find an effect of FPA age or size on this pattern. While we cannot pinpoint the underlying mechanism for the pattern revealed, we suggest behavioural changes as the main driver for reduced home range within FPAs. This mechanism will lead to more resident populations within FPAs, reducing fishing mortality within FPAs yet limiting spillover benefits to adjacent fisheries.

Potential of nature-based solutions to reduce antibiotics, antimicrobial resistance, and pathogens in aquatic ecosystems. a critical review - Edward J. Pastor-López; Mònica Escolà; Vaidotas Kisielius; Carlos A. Arias; Pedro N. Carvalho; Ana M. Gorito; Sandra Ramos; Vânia Freitas; Laura Guimarães; C. Marisa R. Almeida; Jochen A. Müller; Eberhard Küster; et al. (Science of The Total Environment, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Microwave-enhanced preparation of finned-FER zeolites and their application in the skeletal isomerization of FAME - Alexandre Ferreira Young; Pedro Nothaft Romano; Marco Aurélio Suller Garcia; Donato Alexandre Gomes Aranda; João Monnerat Araújo Ribeiro de Almeida (Fuel, 2024)

Insights of potential trypanocidal effect of the synthetic derivative (2E)-1-(4-aminophenyl)-3-(2,4-dichlorophenyl)prop-2-en-1-one: in vitro assay, MEV analysis, quantum study, molecular docking, molecular dynamics, MPO analysis, and predictive ADMET - Márcia Machado Marinho; Matheus Nunes da Rocha; Emanuel Paula Magalhães; Lyanna Rodrigues Ribeiro; Caio Henrique Alexandre Roberto; Francisco Wagner de Queiroz Almeida-Neto; Marília Lopes Monteiro; João Victor Serra Nunes; Ramon Róseo Paula Pessoa Bezerra de Menezes; Emmanuel Silva Marinho; Pedro de Lima Neto; Alice Maria Costa Martins; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Lactic acid bacteria secreted proteins as potential Listeria monocytogenes quorum sensing inhibitors - Pedro Henrique Marques; Arun Kumar Jaiswal; Felipe Alves de Almeida; Uelinton Manoel Pinto; Alessandra Barbosa Ferreira-Machado; Sandeep Tiwari; Siomar de Castro Soares; Aline Dias Paiva (Molecular Diversity, 2024)

Accuracy assessment of global DEMs for the mapping of coastal flooding on a low-lying sandy environment: Cassino Beach, Brazil - Isadora Bicho Emmendorfer; Luís Pedro Melo de Almeida; Deivid Cristian Leal Alves; Leonardo Ramos Emmendorfer; Jorge Arigony-Neto (Regional Studies in Marine Science, 2024)

The roman saltworks of the Atlantic coast of Gallaecia: Traces and evidence of a large sea salt production complex - Brais X. Currás Refojos; Antonio Rodríguez-Fernández; Mar Cortegoso; Ana Almeida; Miguel Costa; Tiago Brochado; Jorge Machado; Pedro Brochado; Rafael Rodríguez-Martínez; Carlos A. Brochado de Almeida (Quaternary Science Reviews, 2024)

Sequential and continuous processes of coalescence and adsorption in produced water treatment by coupling a vegetal fiber coalescer and a fixed bed with biochar produced by vacuum pyrolysis of ouricury palm (Syagrus coronata) - Flávia Bartira Pedro da Silva Almeida; Karla Patrícia Santos Oliveira Rodriguez Esquerre; João Inácio Soletti; Carlos Eduardo de Farias Silva; Ithalo José da Silva; Brígida Maria Villar da Gama (Journal of Water Process Engineering, 2024)

Model of bores interaction in the swash - José Barale; Laurent Lacaze; Dominique Astruc; Rafael Almar; Luis Pedro Almeida (Coastal Engineering, 2024)

Histone 3 Trimethylation Patterns are Associated with Resilience or Stress Susceptibility in a Rat Model of Major Depression Disorder - Lucas Santos; Luiza Behrens; Camila Barbosa; Camila Tiefensee-Ribeiro; Helen Rosa-Silva; Nauana Somensi; Pedro Ozorio Brum; Alexandre Kleber Silveira; Matheus Scarpatto Rodrigues; Jade de Oliveira; Daniel Pens Gelain; Roberto F Almeida; et al. (Molecular Neurobiology, 2024)

Beta diversity and regionalization of the western Atlantic marine biota - Ubirajara Oliveira; Fernanda Azevedo; Alan Dias; Ana Carolina Sousa de Almeida; André R. Senna; Antonio C. Marques; Dafinny Rezende; Eduardo Hajdu; Erick Alves Pereira Lopes‐Filho; Fábio Bettini Pitombo; Gabriela Moura de Oliveira; João Gabriel Doria; et al. (Journal of Biogeography, 2024)
Aim Understanding the factors determining marine community variations is important for biogeography and conservation. Beta diversity is a metric for mapping species composition variations between communities and regionalizing biota. Ecoregions are commonly used for regionalization, but their empirical testing has been limited. Our aim is to map marine species composition variations in the Western Atlantic, identify variables related to these variations, and regionalize areas based on community distribution. Additionally, we test whether currently proposed ecoregions represent unique biota units and specific environmental conditions. Location Western Atlantic Ocean. Taxon Vertebrates, invertebrates and algae. Methods We constructed a large marine biodiversity database, including vertebrates, invertebrates, and algae, totalling over 4 million records. We used the generalized dissimilarity model (GDM) to identify variables most related to species composition variations and map beta‐diversity variations. We employed an unsupervised classifier for community regionalization. To test if the ecoregion regionalization boundaries are corroborated by species distribution data, we used the Sørensen index. To assess if ecoregions correspond to environmental units, we checked if areas had distinct environmental conditions using a PCA of 134 marine environmental variables. Results The GDM explained a high variation in species composition, 61% in the complete database. Analysing vertebrates, invertebrates and algae separately also yielded relatively high results: 46%, 54%, and 33%, respectively. Coastal areas differed from open sea areas in composition. Environmental variables combined better explained beta diversity than isolated variables. The regionalization based on GDM was not congruent with ecoregion boundaries. Moreover, ecoregions showed no distinction in species composition or environmental conditions. Main Conclusions This study's regionalization is crucial for marine biodiversity conservation, focusing on understanding species composition patterns between coastal and open sea areas to develop tailored conservation strategies. Despite sampling limitations, the study advances marine biogeography knowledge by analysing over 4 million species records and 134 environmental variables. This comprehensive approach enhances understanding marine species distribution and diversity and aiding the development of effective conservation measures.

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

FeCo@hydrochar nanocomposites as efficient peroxymonosulfate activator for organic pollutant degradation - Fernando Lima de Menezes; Tiago Melo Freire; Carlos Pedro Gonçalves do Nascimento; Lillian Maria Uchôa Dutra Fechine; Victor Moreira da Costa; Rafael Melo Freire; Elisane Longhinotti; José Heriberto Oliveira do Nascimento; Juliano Casagrande Denardin; Pierre Basílio Almeida Fechine (Environmental Science and Pollution Research, 2024)

Polycyclic aromatic hydrocarbons in seawater after the mysterious oil spill of 2019 on the Pernambuco coast, northeast Brazil - Thayane Cristina da S. Moreira; Ana Flávia B. de Oliveira; Pedro Gabriel C. de Lucena; Estefani S. do Nascimento; Leonardo M.F. de Almeida; Cristiane Maria V. de Araújo-Castro; Lino Angel V. Rojas; Gilvan T. Yogui; Eliete Zanardi-Lamardo; Jandyson M. Santos (Marine Pollution Bulletin, 2024)

Does Covid-19 influence the dynamics of envenomation by animals in a country strongly affected by both conditions? Epidemiological data from Brazil - Pedro Ferreira Bisneto; Alexandre Vilhena da Silva Neto; Jady Shayenne Mota Cordeiro; Wuelton Marcelo Monteiro; Jacqueline de Almeida Gonçalves Sachett (Toxicon, 2024)

Life cycle assessment of electric motors - A systematic literature review - Danilo Ferreira de Souza; Pedro Paulo Fernandes da Silva; Ildo Luis Sauer; Aníbal Traça de Almeida; Hédio Tatizawa (Journal of Cleaner Production, 2024)

Advancing air quality monitoring: A low-cost sensor network in motion – Part I - Carolina Correia; Pedro Santana; Vânia Martins; Pedro Mariano; Alexandre Almeida; Susana Marta Almeida (Journal of Environmental Management, 2024)

Do catadromous thinlip grey mullet benefit from shifting to freshwater? A perspective from fatty acid signature analysis - Esmeralda Pereira; André Jorge; Bernardo Quintella; Marco Gomes da Silva; Pedro R. Almeida; Maria João Lança (Fish Physiology and Biochemistry, 2024)
To investigate the potential benefits of the catadromous thinlip grey mullet ( Chelon ramada Risso, 1827) migration to freshwater, the total lipid content and fatty acid (FA) profile of female’s muscle and gonads caught in both the estuary and river were analyzed. The freshwater contingent presented a higher body condition, greater muscle gross energy, and larger gonads with higher lipid reserves. These animals showed a muscle profile rich in C16:1n-7 and lower LC-PUFA that contrast with the higher relative amount of C18:1n-9, n-3 FA, and unsaturated LC-PUFA, such as C18 and C20 FA found in the estuarine contingent. The gonads of both contingents showed a constant and high relative amount of polyunsaturated FAs (PUFA, 37%). However, in terms of essential fatty acids (EFAs), the estuarine contingent had a higher relative amount of C18:2n-6, C20:4n-6, C20:5n-3, and C22:6n-3. On the other hand, the freshwater contingent showed a higher relative amount of n-3 FA precursors, namely C18:3n-3, and a still low relative amount of C22:6n-3. This suggests a mismatch between the metabolic omega-3 pathway and the physiological maturity stages, similar to a phenomenon of dormancy. In this sense, not all these individuals may reproduce annually, and the later stages of gonad development will require supplementary energy derived from feeding at the estuary. Thus, freshwater migration may promote a reproductive strategy enabling adults to take advantage of the warm and food-rich summer/autumn period, adjust spawning and juvenile appearance, and reduce the population’s exposure to habitat changes and/or stochastic events.

Male external genitalia morphology of the solo ex situ pacarana Dynomis branickii (mammalia: Rodentia: Dinomyidae) - Larissa Schneider Brandão-Souza; Gediendson Ribeiro de Araújo; Thyara Deco-Souza; Derek Andrew Rosenfield; Sofia Regina Polizelle; Felippe Azzolini; Anah Tereza de Almeida Jácomo; Leandro Silveira; Alexia Pimenta Bom-Conselho; Letícia Alecho Requena; Cristiane Schilbach Pizzutto; Pedro Nacib Jorge-Neto (Zoologischer Anzeiger, 2024)

Study of the stability of hydroelectrolytic sports beverages enriched with phenolic extract from jaboticaba peel or blueberry pulp - Thaís Caroline Buttow Rigolon; Larissa Lorrane Rodrigues Borges; Amanda Lais Alves Almeida Nascimento; Janaina Gonçalves Fernandes; João Carlos Bouzas Marins; Evandro Martins; Pedro Henrique Campelo; Paulo César Stringheta (Food and Humanity, 2024)

Comparison of externalities of biogas and photovoltaic solar energy for energy planning - Pedro Henrique Gonçalves Rigueira Pinheiro Castro; Delly Oliveira Filho; André Pereira Rosa; Luis Manuel Navas Gracia; Thais Cristina Almeida Silva (Energy Policy, 2024)

Ecological descriptors in environmental impact assessments: An urgent review of the method in Brazilian reports - Ricardo Pedro Guazzelli Rosario; Maurício Lamano Ferreira; Elisabeth de Almeida Meirelles; Eduardo Luis Martins Catharino (Environmental Impact Assessment Review, 2024)

Assessment spatial soil physical properties under rotational cattle grazing in Northeastern Brazil - Pedro Henrique Dias Batista; Gledson Luiz Pontes de Almeida; Héliton Pandorfi; Renato Paiva de Lima; Victor Wanderley Costa de Medeiros; Jhon Lennon Bezerra da Silva; Airon Aparecido Silva de Melo; Adriel Sales Coutinho (CATENA, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Envenomation by a common green racer (Chlorosoma viridissimum) in the Brazilian Amazon: A report of three cases - Pedro Ferreira Bisneto; Ana Claudia Alzier Lobo; Débora Nery Oliveira; Marco Aurélio Sartim; Wuelton Marcelo Monteiro; Jacqueline de Almeida Gonçalves Sachett (Toxicon, 2024)

Polyethylene terephthalate (PET) as a recycled raw material for particleboards produced from pinus wood and biopolymer resin - Pedro Henrique da Silva Cazella; Matheus Viana de Souza; Felipe Reis Rodrigues; Sergio Augusto Mello da Silva; Rodrigo Andraus Bispo; Victor Almeida De Araujo; André Luis Christoforo (Journal of Cleaner Production, 2024)

Enhancing deforestation monitoring in the Brazilian Amazon: A semi-automatic approach leveraging uncertainty estimation - Jorge Andres Chamorro Martinez; Gilson A. Ostwald Pedro da Costa; Cassiano Gustavo Messias; Luciana de Souza Soler; Claudio A. de Almeida; Raul Queiroz Feitosa (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Functional and structural attributes of Brazilian tropical and subtropical forests and savannas - Cléber Rodrigo de Souza; Fernanda Coelho de Souza; Renata Dias Françoso; Vinícius Andrade Maia; José Roberto Rodrigues Pinto; Pedro Higuchi; Ana Carolina Silva; Jamir Afonso do Prado Júnior; Camila Laís Farrapo; Eddie Lenza; Henrique Mews; Helena L. Lemos Rocha; et al. (Forest Ecology and Management, 2024)

Liposomal nanoformulations with trans-caryophyllene and caryophyllene oxide: do they have an inhibitory action on the efflux pumps NorA, Tet(K), MsrA, and MepA? - Jorge Ederson Gonçalves Santana; Cícera Datiane de Morais Oliveira-Tintino; Gabriel Gonçalves Alencar; Gustavo Miguel Siqueira; José Weverton Almeida-Bezerra; João Pedro Viana Rodrigues; Vanessa Barbosa Pinheiro Gonçalves; Roberto Nicolete; Saulo Relison Tintino; Henrique Douglas Melo Coutinho; Teresinha Gonçalves da Silva (Chemico-Biological Interactions, 2024)

Pathways of surface oceanic water intrusion into the Amazon Continental Shelf - Pedro Paulo de Freitas; Mauro Cirano; Carlos Eduardo Peres Teixeira; Martinho Marta-Almeida; Francisco Flávio de Brito Borges; Camilo Andrés Guerrero-Martin; Vando José Costa Gomes (Ocean Dynamics, 2024)

Satellite-based Machine Learning modelling of Ecosystem Services indicators: A review and meta-analysis - Bruna Almeida; João David; Felipe S. Campos; Pedro Cabral (Applied Geography, 2024)

Estimation of the main air pollutants from different biomasses under combustion atmospheres by artificial neural networks - Thalyssa Oliveira Monteiro; Pedro Augusto Araújo da Silva de Almeida Nava Alves; Alex Oliveira Barradas Filho; Harvey Alexander Villa-Vélez; Glauber Cruz (Chemosphere, 2024)

Hydrogen peroxide electrogeneration from O2 electroreduction: A review focusing on carbon electrocatalysts and environmental applications - Aline B. Trench; Caio Machado Fernandes; João Paulo C. Moura; Lanna E.B. Lucchetti; Thays S. Lima; Vanessa S. Antonin; James M. de Almeida; Pedro Autreto; Irma Robles; Artur J. Motheo; Marcos R.V. Lanza; Mauro C. Santos (Chemosphere, 2024)

An innovative alternative to reduce sodium in cheese: Babassu coconut byproduct improving quality and shelf-life of reduced‑sodium Minas fresh cheese - Rayssa Cruz Lima; Anna Paula Azevedo de Carvalho; Carini Aparecida Lelis; Douglas José Faria; Bruno Dutra da Silva; Mayara Regina da Silva de Figueiredo; Pedro Henrique Thimotheu Chaves; Antônio Eugenio Castro Cardoso de Almeida; Carlos Adam Conte-Junior (Innovative Food Science & Emerging Technologies, 2024)

Applying a water-energy-food nexus approach to seafood products from the European Atlantic area - Sandra Ceballos-Santos; Eduardo Entrena-Barbero; Jara Laso; María Margallo; Sara González-García; María Teresa Moreira; Cheila Almeida; António Marques; Paula Quinteiro; Ana Cláudia Dias; Pedro Villanueva-Rey; Philippe Loubet; et al. (Journal of Cleaner Production, 2024)

Investigating the role of promoters (Ga, Nb, La, and Mg) on In2O3-based catalysts: Advancing on CO2 hydrogenation to C5+ hydrocarbons - Camila Palombo Ferraz; Marlon Tavares; Luís Felipe Bordini; Marco Aurélio Suller Garcia; João Monnerat Araújo Ribeiro de Almeida; Eduardo Falabella Sousa-Aguiar; Pedro Nothaft Romano (Fuel, 2024)

Exploring the effects of eugenol, menthol, and lidocaine as anesthetics on zebrafish glucose homeostasis - Gabriela Maressa Machado Baesso; Amanda Vitória Venâncio; Lívia Costa Varela Barca; Pepita Fernanda Peppi; Caique Aparecido Faria; João Pedro Cosmo Machado; Luiz David Solis Murgas; Álvaro José de Almeida Bicudo; Eduardo Maurício Mendes de Lima; André Rodrigues da Cunha Barreto-Vianna (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Copper-induced exopolysaccharide production by Lelliottia amnigena strain LABEM - Igor Carvalho Fontes Sampaio; Isabela Viana Lopes de Moura; Pedro Jorge Louro Crugeira; Luiz Fernando Widmer; Jairo Pinto de Oliveira; Servio Tulio Alves Cassini; Paulo Fernando de Almeida (Biocatalysis and Agricultural Biotechnology, 2024)

Genomic features and comparative analysis of a multidrug-resistant Acinetobacter bereziniae strain infecting an animal: a novel emerging one health pathogen? - Eliana Guedes Stehling; Fábio P. Sellera; Otávio Guilherme Gonçalves de Almeida; Irys Hany Lima Gonzalez; Patrícia Locosque Ramos; Nathália Gonsales da Rosa-Garzon; Marcia Regina von Zeska Kress; Hamilton Cabral; João Pedro Rueda Furlan (World Journal of Microbiology and Biotechnology, 2024)

Effects of Water Temperature and Structural Habitat Complexity on the Routine Swimming Speed and Escape Response of Post-Settlement Stage White Seabream - Patrícia Vicente; João Almeida; Laura Ribeiro; Sara Castanho; Ana Candeias-Mendes; Pedro Pousão-Ferreira; Ana Margarida Faria (Oceans, 2024)
Coastal habitats are increasingly threatened by multiple anthropogenic-related activities, which include ocean warming and loss of structural habitat complexity. These two pressures have the potential to severely affect the structure and function of marine biodiversity. Early life stages of many fish species recruit to coastal habitats at the end of their pelagic phase, benefiting from access to food, shelter and protection. However, changes in temperature have been shown to influence ecologically relevant behaviours in post-settlement stage fish, and the loss of structural habitat complexity has been related to low recruitment and deleterious behaviours of fish in coastal habitats. Here, we evaluated the individual and interactive effects of prolonged exposure to increasing temperature and changed structural habitat complexity on routine swimming speed and escape response of post-settlement white seabream, Diplodus sargus (Linnaeus, 1758). Fish were reared under different temperatures (control 19 °C; high 22 °C) and structural habitat complexity (low and high) scenarios, in a cross-experimental design, and the routine swimming and escape responses were analyzed after 6 weeks of exposure. Change in temperature did not induce alterations at the behavioural level, but loss of structural habitat complexity increased speed and distance travelled during routine swimming, and responsiveness to a stimulus during the escape response behaviour. The interaction of the two factors did not influence performance. Determining how species are affected by changes in their environment, and the mechanisms that underlie these changes, will be critical to understanding the fish recruitment and populations’ fitness and survival.

A hybrid modelling approach for detecting seasonal variations in inland Green-Blue Ecosystems - Bruna Almeida; Pedro Cabral (Remote Sensing Applications: Society and Environment, 2024)

Long-term heat acclimation training in mice: Similar metabolic and running performance adaptations despite a lower absolute intensity than training at temperate conditions - Gustavo de Oliveira Zanetti; Pedro William Martins Pessoa; Tales Sambrano Vieira; Rodrigo de Almeida Garcia; Nicolas Henrique Santos Barbosa; Rosa Maria Esteves Arantes; Isis do Carmo Kettelhut; Luiz Carlos C. Navegantes; Samuel Penna Wanner; Danusa Dias Soares; Dawit Albieiro Pinheiro Gonçalves (Journal of Thermal Biology, 2024)

Mechanosignaling-related angiocrine factors drive osteoblastic phenotype in response to zirconia - Célio Junior da C. Fernandes; Gerson Santos de Almeida; Patrícia Fretes Wood; Anderson M. Gomes; Fábio J. Bezerra; José C.S. Vieira; Pedro M. Padilha; Willian F. Zambuzzi (Journal of Trace Elements in Medicine and Biology, 2024)

A methodology to improve the accuracy of Total phosphorous diffuse load estimates from agroforestry watersheds - Manuel Almeida; António Rodrigues; Pedro Coelho (Journal of Hydrology, 2024)

Recyclable liquid metal – Graphene supercapacitor - Afsaneh L. Sanati; Pedro Alhais Lopes; Alexandre Chambel; André F. Silva; Diogo M. Oliveira; Carmel Majidi; Anibal T. de Almeida; Mahmoud Tavakoli (Chemical Engineering Journal, 2024)

Effects of particle size of corn and stocking densities on the performance, carcass traits and gastrointestinal tract development of Muscovy ducks in housing - Leandro de Carvalho Maquiné; João Paulo Ferreira Rufino; Kelven Wladie dos Santos Almeida Coelho; Gilberto Batista Viana Filho; Francisco Alberto de Lima Chaves; Frank George Guimarães Cruz; Pedro de Queiroz Costa Neto (Tropical Animal Health and Production, 2024)

Long-term trends and wave climate variability in the South Atlantic Ocean: The influence of climate indices - Natan Z. Maia; Luis Pedro Almeida; João Luiz Nicolodi; Lauro Calliari; Bruno Castelle (Regional Studies in Marine Science, 2023)

Exploring strategies to enhance anthocyanin bioavailability and bioaccessibility in food: A literature review - Amanda Lais Alves Almeida Nascimento; Larissa Lorrane Rodrigues Borges; Janaina Gonçalves Fernandes; Valdeir Viana Freitas; Evandro Martins; Pedro Henrique Campelo; Paulo Cesar Stringheta (Food Bioscience, 2023)

Red propolis extract as a natural ionophore for confined sheep: performance and morphological and histopathological changes - Pedro Henrique de Melo Garcia; Neila Lidiany Ribeiro; Juliana Silva de Oliveira; Dorgival Morais de Lima Júnior; Vitor Visintin Silva de Almeida; Edijanio Galdino da Silva; Tamiris Matias da Costa; Ricardo Romão Guerra (Tropical Animal Health and Production, 2023)

An improved reference genome and first organelle genomes of Quercus suber - Ana Usié; Octávio Serra; Pedro M. Barros; Pedro Barbosa; Célia Leão; Tiago Capote; Tânia Almeida; Leandra Rodrigues; Isabel Carrasquinho; Joana B. Guimarães; Diogo Mendoça; Filomena Nóbrega; et al. (Tree Genetics & Genomes, 2023)
Cork oak ( Quercus suber L.) is an ecologically and economically important evergreen tree species native to the Mediterranean region and widespread in southwest Europe and northwest Africa. An improved genome assembly of cork oak using a combination of Illumina and PacBio sequencing is presented in this study. The assembled genome contains 2351 scaffolds longer than 1000 bp, accounting for 765.7 Mbp of genome size, L90 of 755, and a N50 of 1.0 Mbp, with 40,131 annotated genes. The repetitive sequences constitute 53.6% of the genome. The genome sequences of chloroplast and mitochondrion were determined for the first time, with a genome size of 161,179 bp and 531,858 bp, respectively. Phylogenetic analysis based on complete chloroplast genome sequence showed that Q. suber is closely related to Quercus variabilis , two cork-producing species with commercial use. All data generated are available through the public databases, being ready to be used without restrictions. This study provides an improved nuclear genome assembly together with the organelle genomes of cork oak. These resources will be useful for further breeding strategies and conservation programs and for comparative genomic studies in oak species.

Prevention, protocols, and lab capacity: lessons from a norovirus outbreak in the Algarve - Regina Sá; Joana Roque; Pedro Marques Mendes; Inês Gonçalves; Judite Sousa; Cátia Matos; Álvaro Júnior; Anabela Coelho; Cristina Belo Correia; Vera Manageiro; Corrado Minetti; Rita de Sousa; et al. (Archives of Virology, 2023)

A first assessment of ERA5 and ERA5‐Land reanalysis air temperature in Portugal - Manuel Almeida; Pedro Coelho (International Journal of Climatology, 2023)
This study evaluates the reliability of ERA5 and ERA5‐Land reanalysis datasets in describing the mean daily air temperature of four climate domains in mainland Portugal. The reanalysis datasets were compared with ground observations from 94 meteorological stations (1980–2021). Overall, the results demonstrated a good degree of correlation between the observed and reanalysis data on both a daily and seasonal scale. Both the latitudinal distribution of the air temperature and the moderating effect of the Atlantic Ocean are well described. However, in the case of Portugal, the ERA5‐Land was shown to be considerably more effective at describing the mean daily air temperature than ERA5. The results also indicated that, in general, the reanalysis methodologies perform better when applied to air temperature simulation in flatter regions as opposed to regions with high‐altitude and complex terrain. The study further suggests that ERA5 and ERA5‐Land reanalysis should be used with caution in the case of short‐term environmental studies. In fact, relevant differences were shown to exist between the reanalyses and the observed daily mean air temperature datasets for certain specific years. Overall, considering the RMSE between the ERA5‐Land reanalysis datasets for mean daily air temperature and the observed datasets there is a 28% probability of locally having a mean RMSE 1.5°C and 2.0°C and

Effect of Dietary Inorganic and Chelated Trace Mineral Supplementation on the Growth Performance and Skeletal Deformities of European Seabass and Senegalese Sole Post-larvae - Michael N. Viegas; Maria A. Salgado; Carla Aguiar; Agostinho Almeida; Pedro Pousão-Ferreira; Jorge Dias (Biological Trace Element Research, 2023)

Correction to: Progress and promise of alternative animal and non-animal methods in biomedical research - Irlan Almeida Freires; David Fernando Colon Morelo; Lélio Fernando Ferreira Soares; Isabela Silva Costa; Leonardo Pereira de Araújo; Isadora Breseghello; Henrique Ballassini Abdalla; Josy Goldoni Lazarini; Pedro Luiz Rosalen; Suzane Cristina Pigossi; Marcelo Franchin (Archives of Toxicology, 2023)

Methodological insights from unmanned system technologies in a rock quarry environment and geomining heritage site: coupling LiDAR-based mapping and GIS geovisualisation techniques - Ana Pires; André Dias; Pedro Silva; António Ferreira; Paulo Rodrigues; Tiago Santos; Alexandre Oliveira; Liliana Freitas; Alfredo Martins; José Almeida; Eduardo Silva; Helder I. Chaminé (Arabian Journal of Geosciences, 2023)

The damage caused by Cd toxicity to photosynthesis, cellular ultrastructure, antioxidant metabolism, and gene expression in young cacao plants are mitigated by high Mn doses in soil - Joedson Pinto Barroso; Alex-Alan Furtado de Almeida; Junea Leandro do Nascimento; Bruna Rafaela Machado Oliveira; Ivanildes Conceição dos Santos; Pedro Antônio Oliveira Mangabeira; Dário Ahnert; Virupax C. Baligar (Environmental Science and Pollution Research, 2023)

Do costal erosion and urban development threat loggerhead sea turtle nesting? Implications for sandy beach management - Leonardo Lopes Costa; Eduardo Manuel Rosa Bulhões; João Pedro Almeida Caetano; Vitor Figueira Arueira; Daniella Torres de Almeida; Tatiane Bittar Vieira; Leandro Jorge Telles Cardoso; Ilana Rosental Zalmon (Frontiers in Marine Science, 2023)
Nest beach selection by sea turtles at a regional scale may depend on upper shore environmental cues. Thus, the variability of sandy beach conditions, including coastal erosion rates and urban development can affect their nesting ecology. Almost half of worldwide sandy beaches are suffering from erosion and most of them are located in highly developed areas. This can lead to shore stretches with coastal squeeze and loss of habitat for beach-dependent species such as sea turtles. Understanding whether an endangered species, such as the loggerhead sea turtle Caretta caretta (Linnaeus, 1758), selects certain beaches to nest is the first step in devising mitigation strategies for human activities and climate change impacts. We predicted that the occurrence of loggerhead nests along 62 km of sandy beaches in southeastern Brazil is negatively related to higher urbanization levels and extreme erosion. A total of 731 nests of the loggerhead sea turtle were recorded in the 2022-2023 nesting season. Only 6% of those nests were found on beach sectors with severe and extreme erosion. The probability of laying a nest was negatively related to erosion rate. Also, approximately 50% of nests were found on low-urbanized beaches; thus, the higher the urbanization, the lower the probability of a turtle laying a nest. Nature-based solutions to recover the beach-dune system are recommended in order to mitigate coastal erosion where loggerheads are avoiding nesting. This should be coupled with management planning of the protected areas where nests are laid and must include nest relocation and monitoring as priority actions.

Biopolymers Synthesized by Microalgae Grown in Wastewater: a Technological Survey - Ana Victória dos Santos Borges; Bianca Bomfim Andrade; Jamille Santos Santana; Ravena Maria de Almeida Medeiros; Carolina Oliveira de Souza; Denilson de Jesus Assis; Jania Betania Alves da Silva; Pedro Paulo Lordelo Guimarães Tavares; Lucas Guimarães Cardoso (BioEnergy Research, 2023)

Control of basin-scale accommodation zones on syn-rift Aptian lacustrine carbonate reservoirs. Implications for reservoir quality estimates of Brazilian pre-salt - Pedro Henrique Silvany Sales; Mario Neto Cavalcanti de Araujo; Julio Cesar Horta de Almeida; Rodrigo Brandao Bunevich (Marine and Petroleum Geology, 2023)

Characterization of water status and vegetation cover change in a watershed in Northeastern Brazil - Jessica Bruna Alves da Silva; Gledson Luiz Pontes de Almeida; Marcos Vinicius da Silva; Jose Francisco de Oliveira-Junior; Heliton Pandorfi; Adelia Maria Oliveira de Sousa; Gabriel Thales Barboza Marinho; Pedro Rogerio Giongo; Maria Beatriz Ferreira; Jacqueline Santos de Sousa; Marcio Mesquita; Alexsandro Claudio dos Santos Almeida (Journal of South American Earth Sciences, 2023)

A comparison study of grid impact of photovoltaic installations in Brazil according to Normative Resolution 482 and Federal law 14.300 - José César de Souza Almeida Neto; Pedro Ferreira Torres; Alex Renan Arrifano Manito; João Tavares Pinho; Roberto Zilles (Energy Policy, 2023)

In vitro anti-inflammatory activity and ameliorative effects on gastric ulcers of Licania rigida benth seed extract - Joanna de Freitas Rocha; Letícia de Castro Viana; Luiz Carlos Pereira Almeida Filho; Thiago Silva de Almeida; José Joaquim Lopes Neto; Veríssimo Vieira Neto; Pedro Matheus Sousa Tabosa; Diana Célia Sousa Nunes-Pinheiro; Virgínia Cláudia Carneiro Girão-Carmona; Ana Fontenele Urano Carvalho; Erika Freitas Mota (Inflammopharmacology, 2023)

Laboratory and clinical practices in antinuclear antibody detection and related antigens: recommendations from a Spanish multicentre survey - Laura Martinez-Martinez; Juan Irure-Ventura; Aurora Jurado; Garbiñe Roy; Marco Antonio Montes; Yvelise Barrios; Beatriz Rodríguez-Bayona; Esther Vergara; Álvaro Prada; Ricardo Rojo; María Luisa Vargas; Cristina Abad Molina; et al. (Immunologic Research, 2023)

Electrobiochemical skills of Pseudomonas aeruginosa species that produce pyocyanin or pyoverdine for glycerol oxidation in a microbial fuel cell - Ana Clara Bonizol Zani; Érica Janaina Rodrigues de Almeida; João Pedro Rueda Furlan; Matheus Pedrino; María-Eugenia Guazzaroni; Eliana Guedes Stehling; Adalgisa Rodrigues de Andrade; Valeria Reginatto (Chemosphere, 2023)

Multi-criteria decision-making in decarbonizing urban transportation systems: A case study from Tabriz-Iran - Mahmoud Ouria; Joaquim Delgado; Pedro Moura; Aníbal T. de Almeida (Transportation Research Part D: Transport and Environment, 2023)

Riverine communities and management systems for anadromous fisheries in the Iberian Peninsula: global strategy, local realities - Yorgos Stratoudakis; Carlos Antunes; Cláudia Correia; Ana Filipa Belo; Pedro R. Almeida (Reviews in Fish Biology and Fisheries, 2023)

Progress and promise of alternative animal and non-animal methods in biomedical research - Irlan Almeida Freires; David Fernando Colon Morelo; Lélio Fernando Ferreira Soares; Isabela Silva Costa; Leonardo Pereira de Araújo; Isadora Breseghello; Henrique Ballassini Abdalla; Josy Goldoni Lazarini; Pedro Luiz Rosalen; Suzane Cristina Pigossi; Marcelo Franchin (Archives of Toxicology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

In vivo evaluation of analgesic and anti-inflammatory activity of hydroalcoholic extracts from Handroanthus impetiginosus and their chemical composition by UPLC/MS analysis - Ìcaro E. F. Da Silva; Daniela G. Zoca; Gabriela N. Andrade e Silva; Albert Katchborian-Neto; Pedro S. dos S. R. Cavallari; Samarah G. de Almeida; Ana H. Januário; Patricia M. Pauletti; João Victor Andrade; Raquel P. Morais-Urano; Wilson Roberto Cunha; Mario F. C. Santos; et al. (Natural Product Research, 2023)

Protein profiles identified by LC-MS/MS demonstrate change in beta oxidation, ketogenesis, and propionate metabolism in rumen epithelium with different additives - Leone Campos Rocha; Andrey Sávio de Almeida Assunção; Renata Aparecida Martins; Victor Valério de Carvalho; Alexandre Perdigão; Marília Afonso Rabelo Buzalaf; Jiri Adamec; Camila Pereira Braga; Danilo Domingues Millen; José Cavalcante Souza Vieira; Pedro de Magalhães Padilha (Livestock Science, 2023)

Comparison of dynamic cobble berm revetments with differing gravel characteristics - Ollie Foss; Chris E. Blenkinsopp; Paul M. Bayle; Kévin Martins; Stefan Schimmels; Luis Pedro Almeida (Coastal Engineering, 2023)

Patterns of mistletoe infestation in neotropical urban areas - Marcelo Oliveira Teles de Menezes; Marcelo Freire Moro; Marina Oliveira de Souza; Jorhan Marinho de Almeida; Dávila Vitória de Freitas Braga; Pedro Lucas Rodrigues de Alencar; Francisca Soares de Araújo (Urban Ecosystems, 2023)

Evaluating the potential of biodiversity offsets to achieve net gain - Barbara Almeida Souza; Josianne Claudia Sales Rosa; Pedro Bueno R. Campos; Luis Enrique Sánchez (Conservation Biology, 2023)
Evaluating the outcomes and tracking the trajectory of biodiversity offsets is essential to demonstrating their effectiveness as a mechanism to conciliate development and conservation. We reviewed the literature to determine the principles that should underpin biodiversity offset planning and the criteria for offset evaluation at the project level. According to the literature, the core principles of equivalence, additionality, and permanence are used as criteria to evaluate conservation outcomes of offsets. We applied the criteria to evaluate offsets of a large iron ore mining project in the Atlantic Forest in Brazil. We examined equivalence in terms of the amount of area per biodiversity value affected and fauna and flora similarity, additionality in terms of landscape connectivity, and permanence in terms of guarantees to ensure protection and restoration offsets lasting outcomes. We found an offset ratio (amount of affected area:offset area) of 1:1.8 for forests and 1:2 for grasslands. Ecological equivalence (i.e., similarity between affected and offset areas) was found for forested areas, but not for ferruginous rupestrian grasslands or for fauna. Landscape metrics showed that connectivity improved relative to the preproject situation as a result of locating restoration offsets in the largest and best‐connected forest patch. Permanence of offsets was addressed by establishing covenants and management measures, but financial guarantees to cover maintenance costs after mine closure were lacking. Offsets should be equivalent in type and size, provide conservation outcomes that would not be obtained without them (additionality), and be lasting (permanence). To monitor and evaluate offsets, it is necessary to determine how well these 3 principles are applied in the planning, implementation, and maintenance of offsets. Achieving measurable conservation outcomes from offsets is a long‐term endeavor that requires sustained management support, and is information intensive. Thus, offsets require ongoing monitoring and evaluation as well as adaptive management.

Metarhizium anisopliae E6 secretome reveals molecular players in host specificity and toxicity linked to cattle tick infection - Laura Rascovetzki Saciloto-de-Oliveira; Leonardo Broetto; Camila Innocente Alves; Rafael Lopes da Rosa; Yohana Porto Calegari Alves; Rodrigo Campos da Silva; Markus Berger; Alexandre José Macedo; Pedro Ferrari Dalberto; Cristiano Valim Bizarro; Jorge Almeida Guimarães; John R. Yates; et al. (Fungal Biology, 2023)

Changes in the surface water quality of a tropical watershed in the southeastern amazon due to the environmental impacts of artisanal mining - Gabriel Negreiros Salomão; Roberto Dall’Agnol; Prafulla Kumar Sahoo; Gabriel Soares de Almeida; Rafael Tarantino Amarante; Leiliane Bozzi Zeferino; João Paulo Nobre Lopes; Pedro Walfir Martins e Souza Filho; Normara Yane Mar da Costa; José Tasso Felix Guimarães; Marcio Sousa da Silva; Gabriel Caixeta Martins; et al. (Environmental Pollution, 2023)

The decline of the ecosystem services generated by anadromous fish in the Iberian Peninsula - Pedro R. Almeida; Catarina S. Mateus; Carlos M. Alexandre; Sílvia Pedro; Joana Boavida-Portugal; Ana F. Belo; Esmeralda Pereira; Sara Silva; Inês Oliveira; Bernardo R. Quintella (Hydrobiologia, 2023)
This work aims to present an historical review of the ecosystem services provided by anadromous fish (i.e., species that migrate from the sea to the river to spawn) throughout Human time, as well as of the main related threats, focusing on the Iberian Peninsula region. Anadromous fish provide important provision, cultural, regulatory and supporting ecosystem services across their distribution range and have been extensively exploited by humans since prehistoric times. In the Iberian Peninsula, sea lamprey, allis and twaite shads, sea trout, Atlantic salmon and European sturgeon were once abundantly present in several river basins covering what is now Portuguese and Spanish territory. These species have suffered a severe decline across their distribution range, mainly due to habitat loss and overexploitation. Considered regal delicacies, these fishes were once a statement on the tables of the highest social classes, a much appreciated bounty for the poorer population and are still an important part of the local gastronomy and economy. Such high economic and cultural interest encouraged intensive fishing. Currently, management efforts are being implemented, pairing habitat rehabilitation (e.g., construction of fish passes in obstacles to migration such as weirs and dams) with sustainable fisheries. Considering the present climate change scenario, these species are bound to endure increased pressures, demanding novel management approaches to ensure population numbers that are able to secure their sustainable exploitation.

Patterns of species richness and beta diversity of vascular plants along elevation gradient in Brazilian páramo - Anais de Almeida Campos Cordeiro; Kari Klanderud; Pedro Manuel Villa; Andreza Viana Neri (Journal of Mountain Science, 2023)

On the noxious black Amazonian scorpion, Tityus obscurus (Scorpiones, Buthidae): Taxonomic notes, biology, medical importance and envenoming treatment - Jonas Gama Martins; Karla de Castro Figueiredo Bordon; Jairo A. Moreno-González; Bruno Rafael Ribeiro de Almeida; Pedro P.O. Pardal; André Felipe de Araújo Lira; Denise M. Cândido; Eliane Candiani Arantes; Rudi Emerson de Lima Procópio (Toxicon, 2023)

Corrigendum to ‘A horizon scan exercise for aquatic invasive alien species in Iberian inland waters’ Sci. Total Environ.869 (2023) 161798 - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

Methodological guidelines for the calculation of a Water-Energy-Food nexus index for seafood products - Eduardo Entrena-Barbero; Sandra Ceballos Santos; Antonio Cortés; Xavier Esteve-Llorens; María Teresa Moreira; Pedro Villanueva-Rey; Diego Quiñoy; Cheila Almeida; António Marques; Paula Quinteiro; Ana Cláudia Dias; Jara Laso; et al. (Science of The Total Environment, 2023)

Evaluation of the performance and feasibility of a pseudo-catalytic solution in the biogas purification process - Fernanda Naiara Campos de Almeida; Anderson Rafael Igarashi; Ariane Cezarotto Fiewski; Wardleison Martins Moreira; Djeine Cristina Schiavon Maia; Pedro Augusto Arroyo; Nehemias Curvelo Pereira (Process Safety and Environmental Protection, 2023)

Characterization of oil-in-water microemulsions based on ethoxylated surfactant for paraffinic deposits removal - Yanne Katiussy Pereira Gurgel Aum; Pedro Tupã Pandava Aum; Daniel Nobre Nunes da Silva; Luyara de Almeida Cavalcante; Eduardo Lins de Barros Neto; Tereza Neuma de Castro Dantas (Fuel, 2023)

Phenotypic plasticity and behavioral responses of dairy cattle on rotational grazing - Pedro Henrique Dias Batista; Gledson Luiz Pontes de Almeida; Héliton Pandorfi; Victor Wanderley Costa de Medeiros; Alex Souza Moraes; Airon Aparecido Silva de Melo; Marcos Vinícius da Silva; Marco Antonio Silva (Tropical Animal Health and Production, 2023)

Effects of molasses supplementation on animal performance and carcass parameters of beef cattle: a meta-analysis - Rodrigo de Nazaré Santos Torres; João Pedro Amaral Bertoco; Maria Carolina Gonçalves de Arruda; Larissa de Melo Coelho; Josimari Regina Paschoaloto; Otavio Rodrigues Machado Neto; Jane Maria Bertocco Ezequiel; Marco Túlio Costa Almeida; Luis Artur Loyola Chardulo; Welder Angelo Baldassini (Tropical Animal Health and Production, 2023)

Upstream movement of juvenile eels (Anguilla anguilla L.) in a southwestern European river - Rui M. Monteiro; Isabel Domingos; Pedro R. Almeida; José L. Costa; Esmeralda Pereira; Ana F. Belo; Teresa Portela; Ana Telhado; Bernardo R. Quintella (Environmental Biology of Fishes, 2023)
The upstream movement of juvenile eels (median total length (TL) = 138 mm) in the Mondego River, Portugal, was analysed between January 2017 and August 2019. A total of 12,019 individuals (TL ranging from 60 to 287 mm) were counted and measured on an eel ladder at Coimbra weir, 44 km upstream from the river mouth, during their upstream movements. Although eels were counted throughout the year, a clear seasonal peak was detected in spring and late summer, with 93% of total movements occurring between April and September. No differences were found in the total length of individuals moving upstream between years. Generalised additive models, with an explained deviance of 83% and an adjusted R 2 of 0.88, identified minimum water temperature as the main environmental variable explaining these movements, with a threshold of 13 °C triggering the onset of movements, and a peak between 15 and 19 °C, which corresponds to the spring and summer periods. Other predictors such as photoperiod, precipitation and river flow also contributed as explanatory variables in the model but less importantly. The present results may contribute to the management of this endangered species in the southern region of its distribution range by defining adequate temporal windows to monitor and promote the movement of juvenile European eels through obstacles to migration.

Correction to: Potential outbreak by herpesvirus in equines: detection, clinical, and genetic analysis of equid gammaherpesvirus 2 (EHV-2) - Angélica Cristine de Almeida Campos; Sofia Cicolo; Cairo Monteiro de Oliveira; Camila Vieira Molina; Pedro Enrique Navas-Suárez; Thais Poltronieri dos Santos; Vanessa Barbosa da Silveira; Carla Meneguin Barbosa; Raquel Yvonne Arantes Baccarin; Edison Luiz Durigon; Luiz Gustavo Bentim Góes; Carla Bargi Belli; et al. (Brazilian Journal of Microbiology, 2023)

Potential outbreak by herpesvirus in equines: detection, clinical, and genetic analysis of equid gammaherpesvirus 2 (EHV-2) - Angélica Cristine de Almeida Campos; Sofia Cicolo; Cairo Monteiro de Oliveira; Camila Vieira Molina; Pedro Enrique Navas-Suárez; Thais Poltronieri dos Santos; Vanessa Barbosa da Silveira; Carla Meneguin Barbosa; Raquel Yvonne Arantes Baccarin; Edison Luiz Durigon; Luiz Gustavo Bentim Góes; Carla Bargi Belli; et al. (Brazilian Journal of Microbiology, 2023)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

How diverse a genus can be: An integrated multi-layered analysis into Desmonostoc (Nostocaceae, Cyanobacteriota) - Allan Victor M. Almeida; Marcelo Gomes Marçal Vieira Vaz; Naira Valle de Castro; Diego Bonaldo Genuário; Jean Coutinho Oder; Pedro Augusto Marazzo de Souza; Sandy Bastos Martins; Mariana Machado; Adriano Nunes-Nesi; Wagner L. Araújo (Systematic and Applied Microbiology, 2023)

Distinguishing forest types in restored tropical landscapes with UAV-borne LIDAR - Janneke Scheeres; Johan de Jong; Benjamin Brede; Pedro H.S. Brancalion; Eben Noth Broadbent; Angelica Maria Almeyda Zambrano; Eric Bastos Gorgens; Carlos Alberto Silva; Ruben Valbuena; Paulo Molin; Scott Stark; Ricardo Ribeiro Rodrigues; et al. (Remote Sensing of Environment, 2023)

DNA metabarcoding to assess prey overlap between tuna and seabirds in the Eastern tropical Atlantic: Implications for an ecosystem-based management - Ana Rita Carreiro; Jaime A. Ramos; Vanessa A. Mata; Nathalie M. Almeida; Isabel Rodrigues; Ivo dos Santos; Diana M. Matos; Pedro M. Araújo; Teresa Militão; Jacob González-Sólis; Vitor H. Paiva; Ricardo Jorge Lopes (Marine Environmental Research, 2023)

A review of 121 years of studies on the freshwater zooplankton of Brazil - Maria Stela Maioli Castilho-Noll; Gilmar Perbiche-Neves; Natan Guilherme dos Santos; Leilane Talita Fatoreto Schwind; Fernando Miranda Lansac-Tôha; Alan Cleber Santos da Silva; Bianca Ramos de Meira; Ciro Yoshio Joko; Cláudio Simões de Morais-Júnior; Edissa Emi Cortez Silva; Eneida Maria Eskinazi-Sant'Anna; Felipe Rafael Oliveira; et al. (Limnologica, 2023)

Shotgun proteomics reveals changes in the pectoralis major muscle of broilers supplemented with passion fruit seed oil under cyclic heat stress conditions - Andrey Sávio de Almeida Assunção; Renata Aparecida Martins; José Cavalcante Souza Vieira; Leone Campos Rocha; Fernanda Kaiser de Lima Krenchinski; Marília Afonso Rabelo Buzalaf; José Roberto Sartori; Pedro de Magalhães Padilha (Food Research International, 2023)

Cold plasma as a pre-treatment for processing improvement in food: A review - Jaqueline de Araújo Bezerra; Carlos Victor Lamarão; Edgar Aparecido Sanches; Sueli Rodrigues; Fabiano A.N. Fernandes; Gustavo Luis P.A. Ramos; Erick Almeida Esmerino; Adriano G. Cruz; Pedro H. Campelo (Food Research International, 2023)

An innovative insecticidal approach based on plant protease inhibitor and Bt protoxins inhibits trypsin-like activity in zebrafish - Íris Flávia Sousa Gonçalves; Cleyton de Sousa Gomes; Luiz Carlos Pereira Almeida Filho; Juliana Alves da Costa Ribeiro Souza; Bruno Anderson Matias Rocha; Pedro Filho Noronha de Souza; Augusto Cézar Vasconcelos de Freitas Júnior; Ana Fontenele Urano Carvalho; Davi Farias (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Grain-cropping suitability for evaluating the agricultural land use change in Brazil - José Lucas Safanelli; Rogério de Souza Nóia Júnior; Pedro Alves Quilici Coutinho; Marcela Almeida de Araujo; Arthur Nicolaus Fendrich; Rodnei Rizzo; Ana Letícia Sbitkowski Chamma; Paulo André Tavares; Alberto Giaroli de Oliveira Pereira Barretto; Rodrigo Fernando Maule; Klaus Reichardt; Gerd Sparovek; et al. (Applied Geography, 2023)

Consensus Recommendations for Clinical Outcome Assessments and Registry Development in Ataxias: Ataxia Global Initiative (AGI) Working Group Expert Guidance - Thomas Klockgether; Matthis Synofzik; Saud Alhusaini; Mathieu Anheim; Irina Antonijevic; Tee Ashizawa; Luis Bataller; Mélanie Berard; Enrico Bertini; Sylvia Boesch; Pedro Braga-Neto; Emanuel Cassou; et al. (The Cerebellum, 2023)
To accelerate and facilitate clinical trials, the Ataxia Global Initiative (AGI) was established as a worldwide research platform for trial readiness in ataxias. One of AGI’s major goals is the harmonization and standardization of outcome assessments. Clinical outcome assessments (COAs) that describe or reflect how a patient feels or functions are indispensable for clinical trials, but similarly important for observational studies and in routine patient care. The AGI working group on COAs has defined a set of data including a graded catalog of COAs that are recommended as a standard for future assessment and sharing of clinical data and joint clinical studies. Two datasets were defined: a mandatory dataset (minimal dataset) that can ideally be obtained during a routine clinical consultation and a more demanding extended dataset that is useful for research purposes. In the future, the currently most widely used clinician-reported outcome measure (ClinRO) in ataxia, the scale for the assessment and rating of ataxia (SARA), should be developed into a generally accepted instrument that can be used in upcoming clinical trials. Furthermore, there is an urgent need (i) to obtain more data on ataxia-specific, patient-reported outcome measures (PROs), (ii) to demonstrate and optimize sensitivity to change of many COAs, and (iii) to establish methods and evidence of anchoring change in COAs in patient meaningfulness, e.g., by determining patient-derived minimally meaningful thresholds of change.

A horizon scan exercise for aquatic invasive alien species in Iberian inland waters - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

Long-Term Water Quality Modeling of a Shallow Eutrophic Lagoon with Limited Forcing Data - Manuel Almeida; Ricardo Rebelo; Sérgio Costa; António Rodrigues; Pedro Coelho (Environmental Modeling & Assessment, 2023)

Spatial non-stationarity in the distribution of fish species richness of tropical streams - Thiago Bernardi Vieira; Jorge Iván Sánchez-Botero; Danielle Sequeira Garcez; Sergio Maia Queiroz Lima; Carla Simone Pavanelli; Lilian Casatti; Welber Senteio Smith; Evanilde Benedito; Rosana Mazzoni; Paulo Santos Pompeu; Carlos Sérgio Agostinho; Luciano Fogaça de Assis Montag; et al. (Community Ecology, 2023)

Growth and blood chemistry of juvenile Neotropical catfish (Lophiosilurus alexandri) self-feeding on diets that differ in protein-to-energy (P:E) ratio - Fabio Aremil Costa dos Santos; Leandro Santos Costa; Helder de Oliveira Guilherme; Pedro Gomes Gamarano; Jose Fernando López-Olmeda; Verônica Guimarães Landa Prado; Débora de Almeida Freitas; Luiz Felipe da Silveira Silva; Ronald Kennedy Luz; Paula Adriane Perez Ribeiro (Aquaculture International, 2023)

Feeding behaviour, locomotion rhythms and blood biochemistry of the neotropical red‐tail catfish ( Phractocephalus hemioliopterus ) - Helder de Oliveira Guilherme; Paula Adriane Perez Ribeiro; Verônica Guimarães Landa Prado; Raphael Nogueira Bahiense; Pedro Gomes Gamarano; Camila Gomes de Oliveira; Débora de Almeida Freitas; Leandro Santos Costa (Journal of Fish Biology, 2023)
The study evaluated the feeding behaviour of Phractocephalus hemioliopterus through the animals' ability to adapt to the self‐feeding system, their preferred feeding times and locomotor activity, as well as the blood biochemistry of juveniles fed in a light/dark cycle. The study was carried out through two experiments, the first of which contained two phases. In experiment 1 – phase I, 24 juveniles (35.28 ± 0.62 g) were distributed in eight 48 l tanks. The tanks were equipped with a self‐feeding system and the experiment consisted of evaluating whether the animals were able to adapt to the self‐feeding system, as well as evaluating the preferred feeding times and locomotor activity of these animals. A feeding challenge to the animals was introduced in phase II, based on the results of phase I. The results of the first phase evidenced a nocturnal feeding preference. Thus, the feeding challenge consisted of measuring whether the animal would feed during the day and how long it would take to adapt. When the animals consumed 100% of the amount of feed provided daily, phase II was ended. In experiment 2, 24 juveniles of P . hemioliopterus (182.00 ± 14.03 g) were distributed in eight 96 l tanks. This experiment consisted of two treatments with four repetitions, one with exclusive feeding during the middle of the light cycle and another with exclusive feeding in the middle of the dark cycle. At the end, blood samples were collected from the animals for blood biochemistry evaluations. In experiment 1 – phase I, the results showed that the fish adapted very well to the self‐feeding system and had a strictly nocturnal feeding behaviour and locomotor rhythm. When they were submitted to the feeding challenge in phase II, the feed intake was stabilized from the 17th day onwards, proportionally to the nocturnal consumption observed in the first phase, thus demonstrating feeding plasticity. In experiment 2, the feeding times influenced the animals' biochemical parameters. Animals fed during the night had higher values of cholesterol and triglycerides than animals fed during the day. It is concluded that P . hemioliopterus has fast adaptability to a self‐feeding system, with strictly nocturnal feeding and locomotor behaviours. However, it has feeding plasticity, adapting its behaviour according to food availability. Blood biochemical parameters are influenced by the light/dark feeding cycle.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Four diterpenes identified in silico were isolated from Hyptidinae and demonstrated in vitro activity against Mycobacterium tuberculosis - Andreza Barbosa Silva Cavalcanti; Mayara dos Santos Maia; Pedro Thiago Ramalho de Figueiredo; Renata Priscila Barros de Menezes; Alex France Messias Monteiro; Roseana Araújo Ramos Meireles; Gabriela Cristina Soares Rodrigues; Ana Rita Rodrigues de Almeida Silva; Jociano da Silva Lins; Laísa Vilar Cordeiro; Valnês S. Rodrigues Junior; Ana Paula O. T. Castelo Branco; et al. (Natural Product Research, 2023)

Trace metal concentration along the Brazilian coast: An assessment of the influence of the Doce River plume - Échily Sartori; Cristiane dos Santos Vergilio; Pedro Vianna Gatts; Braulio Cherene Vaz de Oliveira; Marcelo Gomes de Almeida; Fabiano Thompson; Carlos Eduardo de Rezende (Marine Pollution Bulletin, 2023)

Long-term variation of dissolved metals and metalloid in the waters of an Atlantic mesotidal estuary (Sado Estuary, Portugal) - José Miguel Almeida; Carla Palma; Pedro M. Félix; Ana C. Brito (Marine Pollution Bulletin, 2023)

Envenomation by Micrurus hemprichii in Brazilian Amazonia: A report of three cases - Pedro Ferreira Bisneto; Handerson Silva Pereira; Jacqueline de Almeida Gonçalves Sachett; Igor Luis Kaefer; Wuelton Marcelo Monteiro (Toxicon, 2023)

Spread of Mycobacterium tuberculosis in Southern Brazilian persons deprived of liberty: a molecular epidemiology study - Caroline Busatto; Lia Gonçalves Possuelo; Dienefer Bierhals; Carolina Larrosa de Oliveira; Mariana Quaresma de Souza; Dandara Fanfa; Érika Barreto; Pauline Schwarzbold; Andrea Von Groll; Isabel Portugal; João Perdigão; Julio Croda; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

1H NMR-based metabolic profile and chemometric analysis for the discrimination of Passiflora species genotypic variations - Livia Macedo Dutra; Pedro Henrique Vieira Teles; Alan Diego da Conceição Santos; Natoniel Franklin de Melo; Noemi Nagata; Jackson Roberto Guedes da Silva Almeida (Food Research International, 2023)

Connectivity patterns and gene flow among Chelon ramada populations - Esmeralda Pereira; Catarina S. Mateus; Maria J. Alves; Rita Almeida; Joana Pereira; Bernardo R. Quintella; Pedro R. Almeida (Estuarine, Coastal and Shelf Science, 2023)

Energy access during and post-COVID-19 pandemic in sub-Saharan countries: the case of Ethiopia - Yohannes Biru Aemro; Pedro Moura; Aníbal T. de Almeida (Environment, Development and Sustainability, 2023)

Tissue-resident glial cells associate with tumoral vasculature and promote cancer progression - Beatriz G. S. Rocha; Caroline C. Picoli; Bryan O. P. Gonçalves; Walison N. Silva; Alinne C. Costa; Michele M. Moraes; Pedro A. C. Costa; Gabryella S. P. Santos; Milla R. Almeida; Luciana M. Silva; Youvika Singh; Marcelo Falchetti; et al. (Angiogenesis, 2023)

Poor Quality of Sleep is Associated with Lower Academic Performance in Undergraduate Dental Students: A Cross-Sectional Study - Mariana da Silva Muñoz; Pedro Paulo de Almeida Dantas; Natália Marcumini Pola; Maísa Casarin; Rafaela Zazyki de Almeida; Francisco Wilker Mustafa Gomes Muniz (Sleep and Vigilance, 2023)

Metalloproteomic approach to liver tissue of rats exposed to mercury - Maria Gabriela A. Santiago; Victor Diego Faria; Felipe Dalmazzo Cirinêu; Lucas Luan de Lima Queiroz da Silva; Emerson Carlos de Almeida; Nubya Gonçalves Cavallini; José Cavalcante Souza Vieira; Ana Angélica Henrique Fernandes; Camila Pereira Braga; Luís Fabrício Zara; Marília Afonso Rabelo Buzalaf; Jiri Adamec; et al. (Chemosphere, 2023)

Forest landscape restoration: Spectral behavior and diversity of tropical tree cover classes - Leo Eiti Haneda; Pedro H.S. Brancalion; Paulo G. Molin; Matheus Pinheiro Ferreira; Carlos Alberto Silva; Catherine Torres de Almeida; Angelica Faria Resende; Giulio Brossi Santoro; Marcos Rosa; Joannes Guillemot; Guerric Le Maire; Jean-Baptiste Feret; et al. (Remote Sensing Applications: Society and Environment, 2023)

Photodynamic inactivation of Staphylococcus aureus by ecological antibacterial solutions associating LED (ʎ 450 ± 10 nm) with curcumin and olive leaf extracts - Pedro J.L. Crugeira; Heloísa H.S. Almeida; Liandra G. Teixeira; M. Filomena Barreiro (Journal of Photochemistry and Photobiology B: Biology, 2023)

The microbial profile of rivers and lagoons three years after the impact of the world's largest mining disaster (Fundão dam, Brazil) - Pedro Ivo Neves de Almeida; Hugo Emiliano de Jesus; Pedro Henrique Freitas Pereira; Carlos Eduardo Delfino Vieira; Adalto Bianchini; Camila De Martinez Gaspar Martins; Henrique Fragoso dos Santos (Environmental Research, 2023)

Integrated Application of Nitrogen, Molybdenum and Plant Growth-Promoting Rhizobacterium can Enhance the Sugarcane Growth - Amanda Michele Santos de Lima; Emídio Cantídio Almeida de Oliveira; Valeska Regina Silva Martins; Larissa Batista da Silva; Pedro Henrique Neves de Souza; Fernando José Freire (Sugar Tech, 2022)

Immunological imbalance in microcephalic children with congenital Zika virus syndrome - Amanda Costa Ayres Salmeron; Wallace Pitanga Bezerra; Rafaela Lúcia Lopes de Souza; Luanderson Cardoso Pereira; Lícia Maria do Nascimento; Anna Cláudia Calvielli Castelo Branco; Luiza Emilia Cavalcanti Simas; Valéria Azevedo de Almeida; Pedro Henrique de Souza Palmeira; Christiane Medeiros Bezerra; Paulo Marcos Matta Guedes; Maria Notomi Sato; et al. (Medical Microbiology and Immunology, 2022)

Identification of eQTLs and differential gene expression associated with fetal programming in beef cattle - Guilherme Henrique Gebim Polizel; Aline Silva Mello Cesar; Roberta Cavalcante Cracco; Arícia Christofaro Fernandes; Gustavo Morandini Reginato; Pedro Luiz Porfirio Xavier; Isabela Mortari; Édison Furlan; Heidge Fukumasu; Miguel Henrique de Almeida Santana (Journal of Applied Genetics, 2022)

Molecular detection and phylogenetic analysis of Cyprinid herpesvirus 3 in Brazilian ornamental fish - Samara Rita de Lucca Maganha; Pedro Henrique Magalhães Cardoso; Simone de Carvalho Balian; Sabrina Ribeiro de Almeida-Queiroz; Andrezza Maria Fernandes; Ricardo Luiz Moro de Sousa (Brazilian Journal of Microbiology, 2022)

Evidence of Genetic Segregation among Meagre (Argyrosomus regius) Atlantic Spawning Areas - Rita Almeida; Catarina S. Mateus; Maria Judite Alves; João P. Marques; Joana Pereira; Nuno Prista; Henrique Cabral; Pedro R. Almeida; Bernardo R. Quintella (Journal of Marine Science and Engineering, 2022)
The meagre Argyrosomus regius, one of the largest sciaenidae in the world, is a valuable resource for fisheries and aquaculture. Despite its socioeconomic relevance, knowledge about population dynamics and wild stocks is still scarce, and conservation risks are associated with overexploitation. Two genetic distinct groups, one in the North Atlantic Ocean and one in the eastern Mediterranean Sea, were identified by previous studies. However, little is known about the genetic structure of the Atlantic group, where four important spawning areas have been identified. To assess if each spawning area is an independent breeding unit, the genetic diversity, populational structure, and demographic history of A. regius along the North–East and Eastern Central Atlantic coast were analyzed, using 15 microsatellite loci. Results corroborate the hypothesis tested, suggesting four genetic groups: a first group encompassing individuals from the Gironde spawning area, a second group encompassing individuals from the Tagus spawning area, a third group corresponding to individuals captured in the Algarve region, and a forth group gathering individuals from Morocco and Mauritania. This study reveals the need for specific fisheries management plans considering genetic structure information, and highlights the need for international cooperation.

Sexual segregation in the foraging distribution, behaviour, and trophic niche of the endemic Boyd’s shearwater (Puffinus lherminieri boydi) - Ivo dos Santos; Jaime A. Ramos; Filipe R. Ceia; Isabel Rodrigues; Nathalie Almeida; Stefan Antunes; Ana R. Carreiro; Diana M. Matos; Ricardo J. Lopes; Pedro Geraldes; Vítor H. Paiva (Marine Biology, 2022)

Macro-Habitat Suitability for Threespine Stickleback (Gasterosteus aculeatus L.) Near the Southern Limit of Its Global Distribution: Implications for Species Management and Conservation - Andre Moreira; Joana Boavida-Portugal; Pedro R. Almeida; Sara Silva; Carlos M. Alexandre (Fishes, 2022)
The threespine stickleback is a freshwater fish listed as endangered in Portugal, near the southern limit of the species global distribution. However, few measures have been proposed aiming at the conservation of this species in suboptimal environments. From existing databases and specific sampling campaigns, we obtained occurrence data of threespine stickleback for a total of 646 sites. The occurrence data, together with 15 environmental macrohabitat predictors, were used to model the potential distribution of the species using an ensemble of species distribution models. Through the results of our final ensemble, we project that the threespine stickleback occurs predominantly at lower stretches of river systems, where sandy substrate is dominant and flow is higher. Within this region, sticklebacks are also more likely to occur in sites with high levels of rainfall in the driest month, thus avoiding locations with high potential for drying during summer. The species also tends to avoid steep slope areas with high levels of annual precipitation. Based on our results, a map of the species probability of occurrence was generated and river sections were categorized into levels according to their importance for the species’ conservation.

Anti-inflammatory and anti-necrotic effects of lectins from Canavalia ensiformis and Canavalia brasiliensis in experimental acute pancreatitis - Samara Rodrigues Bonfim Damasceno Oliveira; Álvaro Xavier Franco; Marielle Pires Quaresma; Cecília Mendes Morais de Carvalho; Fabrícia da Cunha Jácome Marques; Patrícia da Silva Pantoja; Vanessa Azevedo Mendonça; Vinicius José da Silva Osterne; Jorge Luis Almeida Correia; Ana Maria Sampaio Assreuy; Marcellus Henrique Loiola Pontes de Souza; Kyria Santiago do Nascimento; et al. (Glycoconjugate Journal, 2022)

Widespread Hybridization between Invasive Bleak (Alburnus alburnus) and Iberian Chub (Squalius spp.): A Neglected Conservation Threat - Manuel Curto; Miguel Morgado-Santos; Carlos M. Alexandre; Maria Judite Alves; Hugo F. Gante; Christos Gkenas; João P. Medeiros; Paulo J. Pinheiro; Pedro R. Almeida; Maria Filomena Magalhães; Filipe Ribeiro (Fishes, 2022)
Hybridization between native and nonnative fish species is a major conservation issue, especially in ecosystems with high levels of endemism, such as Iberian streams. To date, hybridization with the invasive bleak Alburnus alburnus has been reported for the Iberian chub Squalius alburnoides and S. pyrenaicus and in scattered locations only. However, the bleak is spreading in the region, potentially increasing the risks of hybridization with other Squalius species. To gather a more comprehensive picture on the current geography of hybridization, we compiled records on hybrids between bleak and chub in Portugal and conducted genetical assessments of hybrids between bleak and S. carolitertii. We found that hybridization with bleak is widespread throughout Portuguese river basins and involves at least S. alburnoides, S. pyrenaicus and S. carolitertii. Hybridization with bleak may not only cause waste of reproductive effort and damage the genetic integrity of these endemic species but also promote shifts in the reproductive dynamics of the S. alburnoides hybrid complex, which includes individuals with various ploidy levels and combinations of parental genomes, reproducing sexually and asexually. We recommend that future studies characterize the fitness of bleak hybrids and their ecological and genetic interactions with native fish, in order to design effective conservation measures.

Thanatology in the northern muriqui (Brachyteles hypoxanthus) - Robério Freire Filho; Igor Inforzato; Fernanda P. Tabacow; Waldney Martins; Carla B. Possamai; Daniel Ferraz; Robson O. E. Hack; Samantha Rocha; Daniel V. Slomp; Marcello S. Nery; Letícia Almeida; Naíla Fernandes; et al. (Primates, 2022)

Movements of Hatchery-Reared Dusky Groupers Released in a Northeast Atlantic Coastal Marine Protected Area - Ana Filipa Silva; Bárbara Horta e Costa; José Lino Costa; Esmeralda Pereira; João Pedro Marques; João J. Castro; Pedro G. Lino; Ana Candeias-Mendes; Pedro Pousão-Ferreira; Inês Sousa; Luís Bentes; Jorge M. S. Gonçalves; et al. (Journal of Marine Science and Engineering, 2022)
No-take areas are key instruments to promote the effectiveness of Marine Protected Areas (MPAs), particularly concerning the protection of endangered species such as the dusky grouper (Epinephelus marginatus). However, despite the establishment of no-take areas and the prohibition of catching this species in a southwestern Portuguese MPA (SACVMP—‘Sudoeste Alentejano’ and ‘Costa Vicentina’ Marine Park) since 2011, there is still no evidence of population recovery. By using acoustic biotelemetry, this work aimed to evaluate the feasibility of restocking hatchery-reared adult dusky groupers in two no-take areas within the SACVMP. In 2019 and 2021, thirty groupers were tagged with acoustic transmitters and the site attachment and movements of the groupers were assessed in the releasing sites (no-take areas). None of the tagged fish settled down in either of the areas, leaving the no-take areas mainly at dusk and night. Some individuals displayed extended movements of more than a hundred kilometers along the Portuguese coast which was rarely reported for this species. At least in some coastal stretches, those movements were performed close to the shore, which may evidence the importance of coastal MPAs to protect and promote the connectivity of species more associated with rocky reef habitats. Following studies should focus on the conditions that promote site attachment and fidelity by hatchery-reared dusky groupers so that future large-scale restocking programs can be successful in MPAs with appropriate habitats.

Hydrogen Peroxide Reduces the Effect of Salt Stress on Growth and Postharvest Quality of Hydroponic Mini Watermelon - André Alisson Rodrigues da Silva; Pedro Francisco do Nascimento Sousa; Geovani Soares de Lima; Lauriane Almeida dos Anjos Soares; Hans Raj Gheyi; Carlos Alberto Vieira de Azevedo (Water, Air, & Soil Pollution, 2022)

Influence of deforestation inside and outside indigenous lands in the Brazilian Amazon Biome - Alex Mota dos Santos; Carlos Fabricio Assunção da Silva; Silas Nogueira de Melo; Pedro Monteiro de Almeida Junior; Luis Fernando Bueno (Regional Environmental Change, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Correction to: Translation, Cross-Cultural Adaptation, and Validation to Brazilian Portuguese of the Cerebellar Cognitive Affective/Schmahmann Syndrome Scale - Stephanie Suzanne de Oliveira Scott; José Luiz Pedroso; Victor Vitalino Elias; Paulo Ribeiro Nóbrega; Emmanuelle Silva Tavares Sobreira; Marcela Patrícia de Almeida; Maria Thereza Drumond Gama; Breno Kazuo Massuyama; Orlando Graziani Povoas Barsottini; Norberto Anizio Ferreira Frota; Pedro Braga-Neto (The Cerebellum, 2022)

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

Foraging costs drive within-colony spatial segregation in shearwaters from two contrasting environments in the North Atlantic Ocean - Jorge M. Pereira; Jaime A. Ramos; Nathalie Almeida; Pedro M. Araújo; Filipe R. Ceia; Pedro Geraldes; Ana M. Marques; Diana M. Matos; Isabel Rodrigues; Ivo dos Santos; Vitor H. Paiva (Oecologia, 2022)

Translation, Cross-Cultural Adaptation, and Validation to Brazilian Portuguese of the Cerebellar Cognitive Affective/Schmahmann Syndrome Scale - Stephanie Suzanne de Oliveira Scott; José Luiz Pedroso; Victor Vitalino Elias; Paulo Ribeiro Nóbrega; Emmanuelle Silva Tavares Sobreira; Marcela Patrícia de Almeida; Maria Thereza Drumond Gama; Breno Kazuo Massuyama; Orlando Graziani Povoas Barsottini; Norberto Anizio Ferreira Frota; Pedro Braga-Neto (The Cerebellum, 2022)

The wind regime over the Brazilian Southeast: Spatial and temporal characterization using multivariate analysis - Washington Luiz Félix Correia Filho; Pedro Henrique de Almeida Souza; José Francisco de Oliveira‐Júnior; Dimas de Barros Santiago; Gustavo Bastos Lyra; Marcelo Zeri; Gisleine Cunha‐Zeri (International Journal of Climatology, 2022)
The characterization of spatial and temporal patterns of wind is essential to several sectors, including energy, urban climate, and applied meteorology. However, few studies describe the regional characteristics of the wind regime over the Brazilian Southeast (SEB), the most developed and populated part of the country. The objectives of the current work were (a) to assess the spatial patterns of the wind regime using cluster analysis (CA) and (b) to apply principal components analysis (PCA) to investigate which meteorological systems influence the spatial and temporal patterns of the wind regime. The dataset consisted of wind speed and direction from 70 automatic weather stations with records from 2008 to 2019. According to the CA method, four groups of homogeneous wind speed (G1–G4) were identified; G4 presented the highest magnitudes of wind speed (wind speed >5 m·s −1 , with maxima of 7.2 m·s −1 ). Seasonal well‐defined minima (March–June) and maxima (July–October) were observed only for G2 and G3. The systems South Atlantic Subtropical Anticyclone (SASA), Frontal Systems (FS), and the South Atlantic Convergence Zone (SACZ) influenced these groups. In addition, the mesoscale meteorological systems likely influence other groups such as breezes from land/sea (G1, G3, and G4), lakes (G2 and G3), and valley/mountain (G2 and G3). The topography had a strong influence on G3, mainly due to the mountain ranges of Mantiqueira and Serra do Mar and Paraíba River valley. Dominant wind directions were E, N/NE, and NW, associated with SASA, in addition to S and SE/SW, influenced by FS and SACZ. The wind speed range of 1.4–3.9 m·s −1 was dominant in all groups, except for G4 (range of 2.4–5.5 m·s −1 ). According to PCA analysis, two PCs are enough to explain the wind pattern in the SEB with 69.9% of the total variance explained. The surface roughness accounted for 29% of the total variance explained in PC1. The latitude (37.6%) and distance to the coast (30.8%) are the most important variables for PC2. Region's physiography and meteorological systems strongly influenced the wind regime over the Brazilian Southeast. The assessment of wind regime variability presented in this work is expected to support public policies on renewable energy applications, air pollution, and climate change mitigation.

Gene duplication to the Y chromosome in Trinidadian Guppies - Yuying Lin; Iulia Darolti; Benjamin L. S. Furman; Pedro Almeida; Benjamin A. Sandkam; Felix Breden; Alison E. Wright; Judith E. Mank (Molecular Ecology, 2022)
Differences in allele frequencies at autosomal genes between males and females in a population can result from two scenarios. First, unresolved sexual conflict over survival can produce allelic differentiation between the sexes. However, given the substantial mortality costs required to produce allelic differences between males and females at each generation, it remains unclear how many loci within the genome experience significant sexual conflict over survival. Alternatively, recent studies have shown that similarity between autosomal and Y sequences can create perceived allelic differences between the sexes. However, Y duplications are most likely in species with large nonrecombining regions, in part because they simply represent larger targets for duplications. We assessed the genomes of 120 wild‐caught guppies, which experience extensive predation‐ and pathogen‐induced mortality and have a relatively small ancestral Y chromosome. We identified seven autosomal genes that show allelic differences between male and female adults. Five of these genes show clear evidence of whole or partial gene duplication between the Y chromosome and the autosomes. The remaining two genes show evidence of partial homology to the Y. Overall, our findings suggest that the guppy genome experiences a very low level of unresolved sexual conflict over survival, and instead the Y chromosome, despite its small ancestral size and recent origin, may nonetheless accumulate genes with male‐specific functions.

Evaluation of hematological, biochemical and oxidative stress profile in calves under propofol anesthesia - Pedro Paulo Arcanjo Lima; Luis Gustavo Narciso; Jefferson Filgueira Alcindo; Maurício Deschk; Paulo Cesar Ciarlini; Paulo Sérgio Patto dos Santos; Breno Fernando Martins de Almeida (Veterinary Research Communications, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Proximate Composition, Nutritional Lipid Quality, and Health Indices of Largemouth Bass ( Micropterus salmoides Lacépède, 1802) from Several Mediterranean Reservoirs - André Jorge; M. Graça Machado; Carlos M. Alexandre; Marco Gomes da Silva; Pedro R. Almeida; M. João Lança (Journal of Aquatic Food Product Technology, 2022)

Diatom Species that Characterize Saline Ponds (Southern Spain) with the Description of a New Navicula Species - David Fernández-Moreno; Pedro M. Sánchez-Castillo; Cristina Delgado; Salomé F. P. Almeida (Wetlands, 2022)

Nanopore Genome Sequencing and Variant Analysis of the Susceptible Candida auris Strain L1537/2020, Salvador, Brazil - Auke W. de Jong; Elaine C. Francisco; João Nóbrega de Almeida; Igor B. Brandão; Felicidade M. Pereira; Pedro H. Presta Dias; Magda M. de Miranda Costa; Regiane T. de Souza Jordão; Duong Vu; Arnaldo L. Colombo; Ferry Hagen (Mycopathologia, 2021)
Candida auris has been reported worldwide, but only in December 2020, the first strain from a COVID-19 patient in Brazil was isolated. Here, we describe the genome sequence of this susceptible C. auris strain and performed variant analysis of the genetic relatedness with strains from other geographic localities.

Whale bones: a key and endangered substrate for cryptogams in Antarctica - Jair Putzke; Carlos Ernesto Gonçalves Reynaud Schaefer; Pedro Manuel Villa; Pedro Henrique Araújo Almeida (Polar Biology, 2021)

Supplementation with an Inorganic Zinc Source in the Metalloproteomic Profile of Royal Jelly in Apis mellifera L. - Aimê de Almeida Longuini; Gabriel Moreno Martineli; Marcelo Polizel Camilli; Daniel Cavalcante Brambila de Barros; José Cavalcante Souza Vieira; Pedro de Magalhães Padilha; Ricardo de Oliveira Orsi (Biological Trace Element Research, 2021)

Inefficient cooking systems a challenge for sustainable development: a case of rural areas of Sub-Saharan Africa - Yohannes Biru Aemro; Pedro Moura; Aníbal T. de Almeida (Environment, Development and Sustainability, 2021)

Phytochemical identification and quantification of quercetin in Triplaris gardneriana wedd. leaves by HPLC-DAD with evaluation of antibacterial activity - Sandra K. S. Macêdo; Tamires S. Almeida; José Marcos T. Alencar Filho; Kátia S. Bezerra Lima; Rafael C. Libório; Mateus M. Costa; Pedro J. Rolim Neto; Larissa A. Rolim; Xirley P. Nunes (Natural Product Research, 2021)

Astragallus mollissimus plant extract: a strategy to reduce ruminal methanogenesis - Pedro Antonio Ochoa-García; Robin C. Anderson; Martha María Arévalos-Sánchez; Felipe Alonso Rodríguez-Almeida; Monserrath Félix-Portillo; Alberto Muro-Reyes; Aleksandar K. Božić; Claudio Arzola-Álvarez; Agustín Corral-Luna (Tropical Animal Health and Production, 2021)

Light- and nutrient-related relationships in mixed plantations of Eucalyptus and a high diversity of native tree species - Nino Tavares Amazonas; David I. Forrester; Carina Camargo Silva; Danilo Roberti Alves de Almeida; Rafael Silva Oliveira; Ricardo Ribeiro Rodrigues; Pedro H. S. Brancalion (New Forests, 2021)

Potential of an estuarine salt marsh plant (Phragmites australis (Cav.) Trin. Ex Steud10751) for phytoremediation of bezafibrate and paroxetine - Sofia Dias; Bárbara Correia; Pedro Fraga-Santiago; Cristiana Silva; Paula C. Baptista; Carlos R. Gomes; C. Marisa R. Almeida (Hydrobiologia, 2021)

Potential of the predatory mite Amblydromalus zannoui to control pest mites on Jatropha curcas - Valdirene Coutinho Miranda; Emiliano Brandão de Azevedo; Wilton Pires da Cruz; Sofía Jiménez Jorge; Marçal Pedro-Neto; Raphael de Campos Castilho; Marie-Stéphane Tixier; Gilberto José de Moraes; Renato Almeida Sarmento (BioControl, 2021)

Investigating the Characteristics and Predictability of Measured Wind Speed Data Over Rio de Janeiro, Brazil - Washington Luiz Félix Correia Filho; Pedro Henrique de Almeida Souza; José Francisco de Oliveira-Júnior; Paulo Miguel de Bodas Terassi; Givanildo de Gois; Carlos Antonio da Silva Junior; Bruno Serafini Sobral; Rafael Henrique Oliveira Rangel; Luiz Cláudio Gomes Pimentel (Pure and Applied Geophysics, 2021)

Effects of intranasal guanosine administration on brain function in a rat model of ischemic stroke - Gabriel C. Müller; Samanta O. Loureiro; Letícia F. Pettenuzzo; Roberto F. Almeida; Evandro Y. Ynumaru; Pedro A. Guazzelli; Fabíola S. Meyer; Mayara V. Pasquetti; Marcelo Ganzella; Maria Elisa Calcagnotto; Diogo O. Souza (Purinergic Signalling, 2021)

Preservation of historical heritage increases bird biodiversity in urban centers - Tulaci Bhakti; Fernanda Rossi; Pedro de Oliveira Mafia; Eduardo Franco de Almeida; Maria Augusta Gonçalves Fujaco; Cristiano Schetini de Azevedo (Environment, Development and Sustainability, 2021)

Structural features and stability of apo- and holo-forms of a simple iron–sulfur protein - Ana V. Almeida; João P. Jacinto; João P. L. Guerra; Bruno J. C. Vieira; João C. Waerenborgh; Nykola C. Jones; Søren V. Hoffmann; Alice S. Pereira; Pedro Tavares (European Biophysics Journal, 2021)

Dps–DNA interaction in Marinobacter hydrocarbonoclasticus protein: effect of a single-charge alteration - João P. Jacinto; Daniela Penas; João P. L. Guerra; Ana V. Almeida; Nykola C. Jones; Søren V. Hoffmann; Pedro Tavares; Alice S. Pereira (European Biophysics Journal, 2021)

Alternative fuel technologies emissions for road heavy-duty trucks: a review - Ana Carolina Rodrigues Teixeira; Pedro Gerber Machado; Flávia Mendes de Almeida Collaço; Dominique Mouette (Environmental Science and Pollution Research, 2021)

An Inverted Management Strategy for the Fishery of Endangered Marine Species - Hudson T. Pinheiro; Jose A. C. C. Nunes; E. O. C. Coni; E. C. G. Almeida; C. L. S. Sampaio; Carlos E. L. Ferreira; Pedro M. Meirelles; M. Hostim-Silva; Pedro H. C. Pereira; Vinicius J. Giglio; J. L. Gasparini; L. A. Rocha; et al. (Frontiers in Marine Science, 2021)
Overfishing is notorious for triggering population collapses and disrupting marine biological functioning worldwide. To counter such a threat, policy-makers have created and implemented multiple management strategies, but most were incapable to prevent the decline of several key species. Here, we discuss a new management strategy in force since June 2019 in Brazil that aims to deter the overfishing of parrotfish species of the genera Scarus and Sparisoma . This innovative strategy, here referred to as inverted management, allows the capture of endangered parrotfish species inside management areas, such as partially protected marine areas—MPAs, but bans it elsewhere. This initiative is supposed to be built in a partnership among the government, scientists, managers, and fishers. If implemented correctly, endangered species would recover in the much larger area outside MPAs, and fishers would benefit from the conservation-value of the scarce and valued product. However, to succeed, the strategy depends on the adoption of a series of challenging management rules that are not currently being enforced along an extensive coastline. So far, few MPAs have incorporated rules for endangered species in their management plan, and those that have done so have no plans or the means to enforce them. Therefore, fishing of endangered species is currently ongoing without any management or monitoring in the entire Brazilian coast. Concerned with the challenges to develop plans to recover populations of endangered species faced by Brazilian managers, we suggest wide communication and a ban on the fisheries until management plans are implemented. Additionally, we suggest that the effectiveness of the inverted management strategy for parrotfishes should be assessed before it’s applied to other endangered species.

Viability of the use of mycotoxin adsorbent in the finishing of Texel lambs in confinement - Fabiola Cristine de Almeida Rego; Pedro Leonardo Olszewski Savio; Simone Fernanda Nedel Pertile; Joice Sifuentes dos Santos; Josiane Ito Eleodoro; Alfredo Jorge Costa Teixeira; Marilice Zundt; Luiz Fernando Coelho da Cunha Filho; José Victor Pronievicz Barreto (Tropical Animal Health and Production, 2021)

Explosive radiation at the origin of Old World fruit bats (Chiroptera, Pteropodidae) - Francisca Cunha Almeida; Lucila Inés Amador; Norberto Pedro Giannini (Organisms Diversity & Evolution, 2021)

Kiwifruit bacterial canker: an integrative view focused on biocontrol strategies - Carla Pereira; Pedro Costa; Larindja Pinheiro; Victor M. Balcão; Adelaide Almeida (Planta, 2021)

Metalloproteomic Strategies for Identifying Proteins as Biomarkers of Mercury Exposure in Serrasalmus rhombeus from the Amazon Region - João Vitor de Queiroz; Bruna Cavecci-Mendonça; José Cavalcante Souza Vieira; Renata Aparecida Martins; Andrey Sávio de Almeida Assunção; Nubya Gonçalves Cavallini; Felipe André dos Santos; Pedro de Magalhães Padilha (Biological Trace Element Research, 2021)

Early settlement and growth of stocked European glass eels in a fragmented watercourse - Pedro M. Félix; José Lino Costa; Bernardo R. Quintella; Pedro R. Almeida; Rui Monteiro; Joana Santos; Teresa Portela; Isabel Domingos (Fisheries Management and Ecology, 2021)
One of the actions that has been implemented to support the recovery of the panmictic population of European eel is stocking of waterbodies where natural recruitment is low or null. However, growth conditions of the stocked eels can vary greatly. This circumstance emphasises the importance to determine ideal habitat conditions to contribute to the success of stocking actions and, consequently, to increase the production of silver eels. This study aims to evaluate the early settlement and growth of stocked glass eels in the upper reaches of a fragmented river. Stocking was carried out, in 2014, at three sites of an inland tributary of the Mondego river basin (Central Portugal), and its monitoring was conducted during the following two years, until 2016, along with the collection of environmental and hydromorphological parameters. The results showed a successful dispersion throughout the study area. Growth varied spatially, although environmental parameters have not clearly explained this variation, but overall with high growth rates and a positive allometric growth in this early stage of stocking, suggesting a good condition of the stocked individuals. This study showed that these upper reaches of fragmented watercourses, a shared feature amongst most European rivers that are currently inaccessible for natural recruitment, may be suitable habitats for eel stocking.

Biochemical characterization of extracellular fructosyltransferase from Aspergillus oryzae IPT-301 immobilized on silica gel for the production of fructooligosaccharides - Larissa Lemos Faria; Sergio Andres Villalba Morales; José Pedro Zanetti Prado; Giancarlo de Souza Dias; Alex Fernando de Almeida; Michelle da Cunha Abreu Xavier; Elda Sabino da Silva; Alfredo Eduardo Maiorano; Rafael Firmani Perna (Biotechnology Letters, 2021)

Marine Environmental Plastic Pollution: Mitigation by Microorganism Degradation and Recycling Valorization - Juliana Oliveira; Afonso Belchior; Verônica D. da Silva; Ana Rotter; Željko Petrovski; Pedro L. Almeida; Nídia D. Lourenço; Susana P. Gaudêncio (Frontiers in Marine Science, 2020)
Plastics are very useful materials and present numerous advantages in the daily life of individuals and society. However, plastics are accumulating in the environment and due to their low biodegradability rate, this problem will persist for centuries. Until recently, oceans were treated as places to dispose of litter, thus the persistent substances are causing serious pollution issues. Plastic and microplastic waste has a negative environmental, social, and economic impact, e.g., causing injury/death to marine organisms and entering the food chain, which leads to health problems. The development of solutions and methods to mitigate marine (micro)plastic pollution is in high demand. There is a knowledge gap in this field, reason why research on this thematic is increasing. Recent studies reported the biodegradation of some types of polymers using different bacteria, biofilm forming bacteria, bacterial consortia, and fungi. Biodegradation is influenced by several factors, from the type of microorganism to the type of polymers, their physicochemical properties, and the environment conditions (e.g., temperature, pH, UV radiation). Currently, green environmentally friendly alternatives to plastic made from renewable feedstocks are starting to enter the market. This review covers the period from 1964 to April 2020 and comprehensively gathers investigation on marine plastic and microplastic pollution, negative consequences of plastic use, and bioplastic production. It lists the most useful methods for plastic degradation and recycling valorization, including degradation mediated by microorganisms (biodegradation) and the methods used to detect and analyze the biodegradation.

Variation in soil carbon, nitrogen and microbial attributes within a silvopastoral system in the Brazilian Cerrado - Luiz Henrique Gomes de Abreu; Igor Costa de Freitas; Pedro Henrique Lopes Santana; Demerson Luiz de Almeida Barbosa; Leonardo David Tuffi Santos; Márcia Vitória Santos; Demerson Arruda Sanglard; Leidivan Almeida Frazão (Agroforestry Systems, 2020)

Hydrogeochemistry of granitic mountain zones and the influence of adjacent sedimentary basins at their tectonic borders: the case of the Spanish Central System batholith - Miguel Martín-Loeches; Javier Pavón-García; Eugenio Molina-Navarro; Pedro Martínez-Santos; Carlos Almeida; Jaime Reyes-López; Ignacio Cienfuegos-Hevia; Antonio Sastre-Merlín (Hydrogeology Journal, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Will COVID-19 Containment and Treatment Measures Drive Shifts in Marine Litter Pollution? - João Canning-Clode; Pedro Sepúlveda; Sílvia Almeida; João Monteiro (Frontiers in Marine Science, 2020)

Marine Biofouling: A European Database for the Marine Renewable Energy Sector - Pedro Almeida Vinagre; Teresa Simas; Erica Cruz; Emiliano Pinori; Johan Svenson (Journal of Marine Science and Engineering, 2020)
Biofouling is a major problem shared among all maritime sectors employing submerged structures where it leads to substantially increased costs and lowered operational lifespans if poorly addressed. Insight into the ongoing processes at the relevant marine locations is key to effective management of biofouling. Of specific concern for the marine renewable energy (MRE) sector is the fact that information on biofouling composition and magnitude across geographies is dispersed throughout published papers and consulting reports. To enable rapid access to relevant key biofouling events the present work describes a European biofouling database to support the MRE sector and other maritime industries. The database compiles in one document qualitative and quantitative data for challenging biofouling groups, including non-native species associated with MRE and related marine equipment, in different European Ecoregions. It provides information on the occurrence of fouling species and data on key biofouling parameters, such as biofouling thickness and weight. The database aims to aid the MRE sector and offshore industries in understanding which biofouling communities their devices are more susceptible to at a given site, to facilitate informed decisions. In addition, the biofouling mapping is useful for the development of biosecurity risk management plans as well as academic research.

Saline water irrigation strategies in two production cycles of naturally colored cotton - Lauriane Almeida dos Anjos Soares; Pedro Dantas Fernandes; Geovani Soares de Lima; Hans Raj Gheyi; Reginaldo Gomes Nobre; Francisco Vanies da Silva Sá; Rômulo Carantino Lucena Moreira (Irrigation Science, 2020)

Toxicity of Carmine Cochineal and Caramel IV Dyes to Terrestrial Plants and Micro-crustaceans - Ana Paula Soares e Silva; Tamires de Sousa Silva; Amanda de Almeida dos Santos; Karoline Griebler Ribeiro; Márcia Maria Mendes Marques; Pedro Marcos de Almeida; Ana Paula Peron (Water, Air, & Soil Pollution, 2020)

Detection and molecular characterization of Lymphocystivirus in Brazilian ornamental fish - Samara Rita de Lucca Maganha; Pedro Henrique Magalhães Cardoso; Simone de Carvalho Balian; Sabrina Ribeiro de Almeida-Queiroz; Andrezza Maria Fernandes; Ricardo Luiz Moro de Sousa (Brazilian Journal of Microbiology, 2020)

Contributions of intercropping systems for diversity and abundance of mite community on Jatropha curcas - Ernesto Cañarte; Renato Almeida Sarmento; Eduardo Andrea Lemus Erasmo; Angelo Pallini; Madelaine Venzon; Ismael de Oliveira Pinto; Marçal Pedro-Neto (BioControl, 2020)

Application of Remote Sensing Methods to Monitor Coastal Zones - Luis Pedro Almeida; Rafael Almar (Journal of Marine Science and Engineering, 2020)
In this Special Issue “Application of Remote Sensing Methods to Monitor Coastal Zones” nine original research papers were published, with topics covering a wide range of ranging of remote sensing applications including coastal topography, bathymetry, land cover, and nearshore hydrodynamics [...]

Cytotoxicity, Genotoxicity, and Toxicity of Plant Biostimulants Produced in Brazil: Subsidies for Determining Environmental Risk to Non-Target Species - Tamires de Sousa Silva; Ana Paula Soares e Silva; Amanda de Almeida Santos; Karoline Griebler Ribeiro; Debora Cristina de Souza; Paulo Agenor Alves Bueno; Márcia Maria Mendes Marques; Pedro Marcos de Almeida; Ana Paula Peron (Water, Air, & Soil Pollution, 2020)

Running to the mountains: mammal species will find potentially suitable areas on the Andes - Cleide Carnicer; Pedro V. Eisenlohr; Anah Tereza de Almeida Jácomo; Leandro Silveira; Giselle Bastos Alves; Natália Mundim Tôrres; Fabiano Rodrigues de Melo (Biodiversity and Conservation, 2020)

Lidar Observations of the Swash Zone of a Low-Tide Terraced Tropical Beach under Variable Wave Conditions: The Nha Trang (Vietnam) COASTVAR Experiment - Luís Pedro Almeida; Rafael Almar; Chris Blenkinsopp; Nadia Senechal; Erwin Bergsma; France Floc’h; Charles Caulet; Melanie Biausque; Patrick Marchesiello; Philippe Grandjean; Jerome Ammann; Rachid Benshila; et al. (Journal of Marine Science and Engineering, 2020)
A field experiment was conducted at a tropical microtidal intermediate sandy beach with a low tide terrace (Nha Trang, Vietnam) to investigate the short-term swash-zone hydrodynamics and morphodynamics under variable wave conditions. Continuous 2D Lidar scanner observations of wave height at the lower foreshore, subsequent run-up and swash-induced topographic changes were obtained. These data were complemented by detailed real-time kinematic GPS topographic surveys. Variable wave and tide conditions were experienced during the field experiment with relatively large swell waves (offshore significant wave height, Hs = 0.9 m to 1.3 m; peak wave period, Tp = 8 to 12 s) concomitant with spring tides at the beginning of the period, followed by mild wind waves (offshore Hs under 0.5 m and Tp 5 s) and neap tides. This resulted in the following morphological sequence: berm erosion followed by rapid neap berm reformation and beach recovery within a few days. New insights into the link between intra-tidal swash dynamics and daily beach profile evolution were found using the Lidar dataset. While waves directly cause morphology changes on a wave-by-wave basis, tidal levels were found to be a key factor in determining the morphological wave-effect (accretive or erosive) due to modulated interaction between surf and swash hydro-morphodynamics.

Petrogenesis of the Low-TiO2 Batalha Suite in the eastern Parnaíba basin, northeastern Brazil - Pedro Miloski; Sérgio de Castro Valente; Julio Cezar Mendes; Cícera Neysi de Almeida; Francisco de Assis Negri; Silvia Regina de Medeiros; Alan Wanderley Miranda; Artur Corval; Leonardo Borghi (International Journal of Earth Sciences, 2020)

Mitigation of Cd toxicity by Mn in young plants of cacao, evaluated by the proteomic profiles of leaves and roots - Bruna Rafaela Machado Oliveira; Alex-Alan Furtado de Almeida; Carlos P. Pirovani; Joedson P. Barroso; Carlos H. de C. Neto; Nayara A. Santos; Dário Ahnert; Viropax C. Baligar; Pedro Antonio O. Mangabeira (Ecotoxicology, 2020)

Phylogenetic analysis of rabies viruses isolated from cattle in southern Brazil - Marcélia Emanuele S. Fernandes; Pedro Carnieli; Adriele N. F. Gregório; Juliana G. C. Kawai; Rafael N. Oliveira; Laura L. Almeida; Julio C. A. Rosa; José C. Ferreira; Sandra D. Traverso; Paulo M. Roehe; Helena B. C. R. Batista (Virus Genes, 2020)

Irrigation Water Quality of a Community Garden Complex in the State of Piauí, Northeastern Brazil - Yeda Gabriela Alves do Espírito Santo Silva; Pedro Marcos de Almeida; Ana Paula Peron (Water, Air, & Soil Pollution, 2020)

Synthesis and process optimization of symmetric and unsymmetric barbiturates C5-coupled with 2,1-benzisoxazoles - João L. Serrano; Pedro F. Soeiro; Melani A. Reis; Renato E. F. Boto; Samuel Silvestre; Paulo Almeida (Molecular Diversity, 2020)

Primary and secondary oocyte growth dynamics in anadromous semelparous Allis shad Alosa alosa - Foivos A. Mouchlianitis; Ana F. Belo; Ana R. Vieira; Bernardo R. Quintella; Pedro R. Almeida; Kostas Ganias (Journal of Fish Biology, 2019)
We analysed the ovarian dynamics of the anadromous semelparous allis shad Alosa alosa for which our working hypothesis was that mature pre‐spawning females would have very low or even exhausted primary growth (PG) oocyte reserves; semelparity has been linked with the depletion of the pool of PG oocytes. To test this hypothesis, the PG oocytes were enumerated, their recruitment pattern to the secondary growth (SG) phase was analysed and their potential replenishment from the pool of oogonia was examined in females caught very close to the Mondego River mouth, in central Portugal and along the river. The development of the SG oocytes was also analysed, the fecundity (batch, total and annual) values were estimated and the intensity of atresia was quantified. Ovarian samples and histological sections were investigated in parallel. A dynamic recruitment pattern of PG oocytes to the SG phase was revealed, where all PG oocytes were recruited and were not replenished by oogonia. Annual fecundity was subject to down‐regulation due to atresia prior to spawning and its size was multiple times higher than the size of batch fecundity. Lack of population synchronicity in ovarian development and spawning migration was also observed. This multifaceted analysis of the ovarian dynamics of this species will contribute to management efforts for this critically endangered and economically important fish throughout its geographical distribution. The results reported in this study will also assist in unravelling the complexity of the early processes of oogenesis in fish.

Is there an indication of the origin of nutrient supply in different morphological structures of macrofauna at two different Brazilian southeastern sandy beaches? Comparison by C and N stable isotopes - Tito C. M. Almeida; Pedro F. P. Rocha; Ilana R. Zalmon; Marcelo G. Almeida; Carlos E. Rezende; Claudemir M. Radetski (Environmental Science and Pollution Research, 2019)

Coalescence process to treat produced water: an updated overview and environmental outlook - Flávia Bartira Pedro da Silva Almeida; Karla Patrícia Santos Oliveira Rodr Esquerre; João Inácio Soletti; Carlos Eduardo De Farias Silva (Environmental Science and Pollution Research, 2019)

Spasmolytic and antidiarrheal activities of Lippia thymoides (Verbenaceae) essential oil - Pedro Modesto Nascimento Menezes; Henrique Ribeiro de Oliveira; Mariana Coelho Brito; Gabriela Olinda de Paiva; Luciano Augusto de Almeida Ribeiro; Angélica Maria Lucchese; Fabrício Souza Silva (Natural Product Research, 2019)

The new psychoactive substance 3-methylmethcathinone (3-MMC or metaphedrone) induces oxidative stress, apoptosis, and autophagy in primary rat hepatocytes at human-relevant concentrations - Diana Dias da Silva; Bárbara Ferreira; Rita Roque Bravo; Rita Rebelo; Tomás Duarte de Almeida; Maria João Valente; João Pedro Silva; Félix Carvalho; Maria de Lourdes Bastos; Helena Carmo (Archives of Toxicology, 2019)

Cognitive and Psychiatric Evaluation in SYNE1 Ataxia - Maria Thereza Drumond Gama; Pedro Braga-Neto; Livia Almeida Dutra; Helena Alessi; Lilia Alves Maria; Ary Araripe Gadelha; Bruno Bertolucci Ortiz; Ilda Kunii; Silvia Regina Correia-Silva; Magnus R. Dias da Silva; Patrick A. Dion; Guy A. Rouleau; et al. (The Cerebellum, 2019)

Use of antibiotics to control endophytic bacterial growth migration onto culture medium in Eucalyptus cloeziana F.Muell.: a micropropagation approach - Gabriela Ferraz Leone; Pedro Avelino Maia Andrade; Carolina Vieira de Almeida; Cristina Vieira de Almeida; Fernando Dini Andreote; Marcílio de Almeida (In Vitro Cellular & Developmental Biology - Plant, 2019)

Treatment of oily effluent using a low-cost biosurfactant in a flotation system - Elias J. Silva; Ivison A. Silva; Pedro P. F. Brasileiro; Priscilla F. Correa; Darne G. Almeida; Raquel D. Rufino; Juliana M. Luna; Valdemir A. Santos; Leonie A. Sarubbo (Biodegradation, 2019)

Production, formulation and cost estimation of a commercial biosurfactant - Rita de Cássia Freire Soares da Silva; Darne Germano de Almeida; Pedro Pinto Ferreira Brasileiro; Raquel Diniz Rufino; Juliana Moura de Luna; Leonie Asfora Sarubbo (Biodegradation, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Connectivity Between Coastal and Oceanic Zooplankton From Rio Grande do Norte in the Tropical Western Atlantic - Sigrid Neumann Leitão; Mauro de Melo Junior; Fernando de Figueiredo Porto Neto; Andréa Pinto Silva; Xiomara Franchesca Garcia Diaz; Tamara de Almeida e Silva; Dilma Aguiar do Nascimento Vieira; Lucas Guedes Pereira Figueiredo; Alejandro Esteweson Santos Faustino da Costa; Jana Ribeiro de Santana; Renata Polyana de Santana Campelo; Pedro Augusto Mendes de Castro Melo; et al. (Frontiers in Marine Science, 2019)

Muscle fatty acid profiles of sea lamprey (Petromyzon marinus L.) indicate the use of fast metabolized energy during ontogenesis - Elói Martins; Pedro R. Almeida; Bernardo R. Quintella; Marco Gomes da Silva; Maria João Lança (Fish Physiology and Biochemistry, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Diacetylcurcumin: a new photosensitizer for antimicrobial photodynamic therapy in Streptococcus mutans biofilms - Carolina Veronez Garbúggio Sanches; Janaina de Cássia Orlandi Sardi; Raquel Sano Suga Terada; Josy Goldoni Lazarini; Irlan Almeida Freires; Carlos Roberto Polaquini; Guilherme Silva Torrezan; Luis Octavio Regasini; Mitsue Fujimaki; Pedro Luiz Rosalen (Biofouling, 2019)

Antimicrobial activity of nitrochalcone and pentyl caffeate against hospital pathogens results in decreased microbial adhesion and biofilm formation - Fernanda Teresinha de Almeida Sayão de Emeri; Pedro Luiz Rosalen; Éder Ramos Paganini; Mayara Aparecida Rocha Garcia; Ana Carolina Nazaré; Josy Goldoni Lazarini; Severino Matias de Alencar; Luis Octávio Regasini; Janaina de Cassia Orlandi Sardi (Biofouling, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Impact of environmental temperatures on mortality, sex and caste ratios in Melipona interrupta Latreille (Hymenoptera, Apidae) - Tatiane Becker; Pedro Aurélio Costa Lima Pequeno; Gislene Almeida Carvalho-Zilse (The Science of Nature, 2018)

Human predisposition to cognitive impairment and its relation with environmental exposure to potentially toxic elements - Marina M. S. Cabral Pinto; A. Paula Marinho-Reis; Agostinho Almeida; Carlos M. Ordens; Maria M. V. G. Silva; Sandra Freitas; Mário R. Simões; Paula I. Moreira; Pedro A. Dinis; M. Luísa Diniz; Eduardo A. Ferreira da Silva; M. Teresa Condesso de Melo (Environmental Geochemistry and Health, 2018)

Evaluation of the effectiveness of red mud-supported catalysts in combination with ozone and TiO2 in the treatment of solution containing benzene, toluene, and xylene - Bernardo Alves de Lima; Pedro Paulo Rocha de Castro; Alexandre Boscaro França; Eduardo Prado Baston; Renata Carolina Zanetti Lofrano; Gisella Rossana Lamas Samanamud; Carla Cristina Almeida Loures; Luzia Lima Rezende Naves; Fabiano Luiz Naves (Environmental Monitoring and Assessment, 2018)

Non-potable use of Lisbon underground water: microbiological and hydrochemical data from a 4-year case study - Pedro Teixeira; Luís Almeida; João Brandão; Sílvia Costa; Susana Pereira; Elisabete Valério (Environmental Monitoring and Assessment, 2018)

Molecular detection and phylogenetic analysis of megalocytivirus in Brazilian ornamental fish - Samara Rita de Lucca Maganha; Pedro Henrique Magalhães Cardoso; Simone de Carvalho Balian; Sabrina Ribeiro de Almeida-Queiroz; Andrezza Maria Fernandes; Ricardo Luiz Moro de Sousa (Archives of Virology, 2018)

Evolutionary analysis of Porcine circovirus 3 (PCV3) indicates an ancient origin for its current strains and a worldwide dispersion - Giuliana Loreto Saraiva; Pedro Marcus Pereira Vidigal; Juliana Lopes Rangel Fietto; Gustavo Costa Bressan; Abelardo Silva Júnior; Márcia Rogéria de Almeida (Virus Genes, 2018)

Correction to: Can in vivo surface dental enamel microbiopsies be used to measure remote lead exposure? - Kelly Polido Kaneshiro Olympio; Manuel Fernando Gonzalez Huila; Cristiane de Almeida Baldini Cardoso; Ana Paula Sacone da Silva Ferreira; Adrielly Garcia Ortiz; Henrique Eisi Toma; Ricardo Henrique Alves da Silva; Maciel Santos Luz; Maria Regina Alves Cardoso; Gislayne Aparecida Rodrigues Kelmer; Pedro Vitoriano de Oliveira; Etelvino José Henriques Bechara; et al. (Environmental Science and Pollution Research, 2018)

Can in vivo surface dental enamelmicrobiopsies be used to measure remote lead exposure? - Kelly Polido Kaneshiro Olympio; Manuel Fernando Gonzalez Huila; Cristiane de Almeida Baldini Cardoso; Ana Paula Sacone da Silva Ferreira; Adrielly Garcia Ortiz; Henrique Eisi Toma; Ricardo Henrique Alves da Silva; Maciel Santos Luz; Maria Regina Alves Cardoso; Gislayne Aparecida Rodrigues Kelmer; Pedro Vitoriano de Oliveira; Etelvino José Henriques Bechara; et al. (Environmental Science and Pollution Research, 2018)

Cortical Bilateral Adaptations in Rats Submitted to Focal Cerebral Ischemia: Emphasis on Glial Metabolism - Yasmine Nonose; Pedro E. Gewehr; Roberto F. Almeida; Jussemara S. da Silva; Bruna Bellaver; Leo A. M. Martins; Eduardo R. Zimmer; Samuel Greggio; Gianina T. Venturin; Jaderson C. Da Costa; André Quincozes-Santos; Luc Pellerin; et al. (Molecular Neurobiology, 2018)

Use of two doses of cloprostenol in different intervals for estrus synchronization in hair sheep under tropical conditions - Sheylla Foligno de Carvalho Menezes de Almeida; Joanna Maria Gonçalves Souza-Fabjan; Mario Felipe Alvarez Balaro; Gláucia Mota Bragança; Pedro Henrique Nicolau Pinto; José Gabriel de Almeida; Ana Beatriz Bossois Moura; Jeferson Ferreira da Fonseca; Felipe Zandonadi Brandão (Tropical Animal Health and Production, 2018)

Evaluation of the genetic variability found in Brazilian commercial vaccines for infectious bronchitis virus - Giuliana Loreto Saraiva; Marcus Rebouças Santos; Claiton Gonçalves Pereira; Pedro Marcus Pereira Vidigal; Juliana Lopes Rangel Fietto; Tiago Antonio de Oliveira Mendes; Gustavo Costa Bressan; Jamária A. P. Soares-Martins; Márcia Rogéria de Almeida; Abelardo Silva-Júnior (Virus Genes, 2018)

Carbon-optimised land management strategies for southern Amazonia - Gerhard Gerold; Eduardo Guimarães Couto; Beata Emoke Madari; Hermann F. Jungkunst; Ricardo Silva Santos Amorim; Stefan Hohnwald; Michael Klingler; Pedro Luiz Oliveira de Almeida Machado; Regine Schönenberg; Claas Nendel (Regional Environmental Change, 2018)

Integrated farming systems for improving soil carbon balance in the southern Amazon of Brazil - Janaína de Moura Oliveira; Beata Emoke Madari; Márcia Thaís de Melo Carvalho; Paula Camylla Ramos Assis; André Luiz Rodrigues Silveira; Mateus de Leles Lima; Flávio Jesus Wruck; João Carlos Medeiros; Pedro Luiz Oliveira de Almeida Machado (Regional Environmental Change, 2018)

Environmental factors influencing the settlement of Diplodus spp. juveniles in temperate marine rocky shores - Pedro Duarte-Coelho; Ruxanda Lungu; Joana Martins; Diana Vieira; Ana Coelho; José Neto; Sofia Sousa; Pedro Almeida; Frederico Almada (Frontiers in Marine Science, 2018)

Antioxidant enzymes activities in the liver of sea bass, Dicentrarchus labrax, juveniles fed diets with different levels of vitamins - Catarina Almeida; Sara Castanho; Anaísa Silva; Ana Mendes; Pedro Pousão-Ferreira; Michael Viegas; Jorge Dias; Teresa Baptista; Laura Ribeiro (Frontiers in Marine Science, 2018)

Correction to: Lipophilic gold(I) complexes with 1,3,4-oxadiazol-2-thione or 1,3-thiazolidine-2-thione moieties: synthesis and their cytotoxic and antimicrobial activities - Angelina Maria de Almeida; Bruno Assis de Oliveira; Pedro Pôssa de Castro; Camille Carvalho de Mendonça; Ricardo Andrade Furtado; Heloiza Diniz Nicolella; Vânia Lúcia da Silva; Cláudio Galuppo Diniz; Denise Crispim Tavares; Heveline Silva; Mauro Vieira de Almeida (BioMetals, 2017)

Lipophilic gold(I) complexes with 1,3,4-oxadiazol-2-thione or 1,3-thiazolidine-2-thione moieties: synthesis and their cytotoxic and antimicrobial activities - Angelina Maria de Almeida; Bruno Assis de Oliveira; Pedro Pôssa de Castro; Camille Carvalho de Mendonça; Ricardo Andrade Furtado; Heloiza Diniz Nicolella; Vânia Lúcia da Silva; Cláudio Galuppo Diniz; Denise Crispim Tavares; Heveline Silva; Mauro Vieira de Almeida (BioMetals, 2017)

The triterpenoid alpha, beta-amyrin prevents the impaired aortic vascular reactivity in high-fat diet-induced obese mice - Flávia Almeida Santos; Karine Maria Martins Bezerra Carvalho; Francisco José Batista-Lima; Paulo Iury Gomes Nunes; Ana Flávia Seraine Custódio Viana; Armenio André de Carvalho Almeida da Silva; Said Gonçalves da Cruz Fonseca; Mariana Helena Chaves; Vietla Satyanarayana Rao; Pedro Jorge Caldas Magalhães; Teresinha Silva de Brito (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Hermaphroditism can compensate for the sex ratio in the Astyanax scabripinnis species complex (Teleostei: Characidae): expanding the B chromosome study model - Diana Cornelio; Jonathan Pena Castro; Mateus Henrique Santos; Marcelo Ricardo Vicari; Mara Cristina de Almeida; Orlando Moreira-Filho; Juan Pedro M. Camacho; Roberto Ferreira Artoni (Reviews in Fish Biology and Fisheries, 2017)

An integrative overview of the molecular and physiological responses of sugarcane under drought conditions - Camilo Elber Vital; Andrea Giordano; Eduardo de Almeida Soares; Thomas Christopher Rhys Williams; Rosilene Oliveira Mesquita; Pedro Marcus Pereira Vidigal; Amanda de Santana Lopes; Túlio Gomes Pacheco; Marcelo Rogalski; Humberto Josué de Oliveira Ramos; Marcelo Ehlers Loureiro (Plant Molecular Biology, 2017)

Hospital microbial surface colonization revealed during monitoring of Klebsiella spp., Pseudomonas aeruginosa, and non-tuberculous mycobacteria - Pedro Geadas Farias; Fernando Gama; Diogo Reis; Susana Alarico; Nuno Empadinhas; José Carlos Martins; Ana Figueiredo de Almeida; Paula Vasconcelos Morais (Antonie van Leeuwenhoek, 2017)

Morphology, ultrastructure, and element uptake in Calophyllum brasiliense Cambess. (Calophyllaceae J. Agardh) seedlings under cadmium exposure - Alezania Silva Pereira; Priscila Andressa Cortez; Alex-Alan Furtado de Almeida; Majeti Narashima Vara Prasad; Marcel Giovanni Costa França; Maura da Cunha; Raildo Mota de Jesus; Pedro Antônio Oliveira Mangabeira (Environmental Science and Pollution Research, 2017)

Alternative Animal and Non-Animal Models for Drug Discovery and Development: Bonus or Burden? - Irlan Almeida Freires; Janaina de Cássia Orlandi Sardi; Ricardo Dias de Castro; Pedro Luiz Rosalen (Pharmaceutical Research, 2017)

Adaptive divergence in wine yeasts and their wild relatives suggests a prominent role for introgressions and rapid evolution at noncoding sites - Pedro Almeida; Raquel Barbosa; Douda Bensasson; Paula Gonçalves; José Paulo Sampaio (Molecular Ecology, 2017)
In Saccharomyces cerevisiae , the main yeast in wine fermentation, the opportunity to examine divergence at the molecular level between a domesticated lineage and its wild counterpart arose recently due to the identification of the closest relatives of wine strains, a wild population associated with Mediterranean oaks. As genomic data are available for a considerable number of representatives belonging to both groups, we used population genomics to estimate the degree and distribution of nucleotide variation between wine yeasts and their closest wild relatives. We found widespread genomewide divergence, particularly at noncoding sites, which, together with above average divergence in trans‐acting DNA binding proteins, may suggest an important role for divergence at the level of transcriptional regulation. Nine outlier regions putatively under strong divergent selection were highlighted by a genomewide scan under stringent conditions. Several cases of introgressions, originating in the sibling species Saccharomyces paradoxus, were also identified in the Mediterranean oak population. FZF1 and SSU 1 , mostly known for conferring sulphite resistance in wine yeasts, were among the introgressed genes, although not fixed. Because the introgressions detected in our study are not found in wine strains, we hypothesize that ongoing divergent ecological selection segregates the two forms between the different niches. Together, our results provide a first insight into the extent and kind of divergence between wine yeasts and their closest wild relatives.

Effects of dietary Gracilaria sp. and Alaria sp. supplementation on growth performance, metabolic rates and health in meagre (Argyrosomus regius) subjected to pathogen infection - Maria João Peixoto; Emílio Salas-Leitón; Francisca Brito; Luís Ferreira Pereira; Jon C. Svendsen; Teresa Baptista; Rui Pereira; Helena Abreu; Pedro Alexandre Reis; José Fernando Magalhães Gonçalves; Rodrigo Otávio de Almeida Ozório (Journal of Applied Phycology, 2017)

Toxoplasma gondii in backyard pigs: seroepidemiology and mouse bioassay - Erika Fernanda Torres Samico-Fernandes; Marcela Fernanda Torres Samico-Fernandes; Pedro Paulo Feitosa de Albuquerque; Jonatas Campos de Almeida; André de Souza Santos; André da Rocha Mota; Orestes Luiz de Souza Neto; Rinaldo Aparecido Mota (Acta Parasitologica, 2017)
The aim of this study was to evaluate the occurrence of

Detection and Molecular Characterization of Gemycircularvirus from Environmental Samples in Brazil - Matheus Ribeiro da Silva Assis; Carmen Baur Vieira; Julia Monassa Fioretti; Mônica Simões Rocha; Pedro Ivo Neves de Almeida; Marize Pereira Miagostovich; Tulio Machado Fumian (Food and Environmental Virology, 2016)

Distribution of infectious bronchitis virus strains in different organs and evidence of vertical transmission in natural infection - Claiton Gonçalves Pereira; Giuliana Loreto Saraiva; Pedro Marcus Pereira Vidigal; Juliana Lopes Rangel Fietto; Gustavo Costa Bressan; Maria Aparecida Scatamburlo Moreira; Márcia Rogéria de Almeida; Abelardo Silva Júnior (Archives of Virology, 2016)

Culture‐independent characterization of novel psychrophilic magnetotactic cocci from Antarctic marine sediments - Fernanda Abreu; Ana Carolina; V. Araujo; Pedro Leão; Karen Tavares Silva; Fabíola Marques de Carvalho; Oberdan de Lima Cunha; Luiz Gonzaga Almeida; Corey Geurink; Marcos Farina; Daniel Rodelli; Luigi Jovane; et al. (Environmental Microbiology, 2016)
Summary Magnetotactic bacteria (MTB) are a heterogeneous group of ubiquitous aquatic microorganisms capable of biomineralizing nano‐sized, membrane‐bound, magnetic iron‐rich mineral particles called magnetosomes. MTB are found in chemically‐stratified aquatic sediments and/or water columns with a wide range of salinities, moderate to high temperatures, and pH varying from neutral to strongly alkaline. MTB from very cold environments have not been investigated to any great degree and here we characterize MTB from the low temperature Antarctic maritime region. Sediment samples were collected at nine sampling sites within Admiralty Bay, King George Island (62°23′S 58°27′W) from 2009 to 2013. Samples from five sites contained MTB and those from two of these sites contained large number of magnetotactic cocci that were studied using electron microscopy and molecular techniques. The magnetotactic cocci contained magnetosomes either arranged as two or four chains or as a disorganized cluster. The crystalline habit and composition of all magnetosomes analyzed with high‐resolution transmission electron microscopy and energy dispersive X‐ray microanalysis were consistent with elongated prismatic crystals of magnetite (Fe 3 O 4 ). The retrieved 16S rRNA gene sequences from magnetically‐enriched magnetotactic cocci clustered into three distinct groups affiliated with the Alphaproteobacteria class of the Proteobacteria . Novel sequences of each phylogenetic cluster were confirmed using fluorescent in situ hybridization. Metagenomic data analysis of magnetically‐enriched magnetotactic cocci revealed the presence of mam genes and MTB‐specific hypothetical protein coding genes. Sequence homology and phylogenetic analysis indicated that predicted proteins are related to those of cultivated alphaproteobacterial MTB. The consistent and continuous low temperature of the sediment where the magnetotactic cocci are present (always below 1°C) suggests that these MTB from maritime Antarctica are psychrophiles. Moreover, similar morphotypes and 16S gene sequences were retrieved from samples collected from different sites from maritime Antarctica for several years suggesting that these new strains of MTB are indigenous members of Antarctic microbiota.

Persistence of a dominant bovine lineage of group B S treptococcus reveals genomic signatures of host adaptation - Alexandre Almeida; Cinthia Alves‐Barroco; Elisabeth Sauvage; Ricardo Bexiga; Pedro Albuquerque; Fernando Tavares; Ilda Santos‐Sanches; Philippe Glaser (Environmental Microbiology, 2016)
Summary Group B Streptococcus (GBS) is a host‐generalist species, most notably causing disease in humans and cattle. However, the differential adaptation of GBS to its two main hosts, and the risk of animal to human infection remain poorly understood. Despite improvements in control measures across Europe, GBS is still one of the main causative agents of bovine mastitis in Portugal. Here, by whole‐genome analysis of 150 bovine GBS isolates we discovered that a single CC61 clone is spreading throughout Portuguese herds since at least the early 1990s, having virtually replaced the previous GBS population. Mutations within an iron/manganese transporter were independently acquired by all of the CC61 isolates, underlining a key adaptive strategy to persist in the bovine host. Lateral transfer of bacteriocin production and antibiotic resistance genes also underscored the contribution of the microbial ecology and genetic pool within the bovine udder environment to the success of this clone. Compared to strains of human origin, GBS evolves twice as fast in bovines and undergoes recurrent pseudogenizations of human‐adapted traits. Our work provides new insights into the potentially irreversible adaptation of GBS to the bovine environment.

Are Polyphenols Strong Dietary Agents Against Neurotoxicity and Neurodegeneration? - Susana Almeida; Marco G. Alves; Mário Sousa; Pedro F. Oliveira; Branca M. Silva (Neurotoxicity Research, 2016)

Glyphosate sub-lethal toxicity to non-target organisms occurring in Jatropha curcas plantations in Brazil - Althiéris Souza de Saraiva; Renato Almeida Sarmento; Marçal Pedro-Neto; Adenir Vieira Teodoro; Eduardo Andrea Lemus Erasmo; Diana Cléssia Vieira Belchior; Emiliano Brandão de Azevedo (Experimental and Applied Acarology, 2016)

Evidences for multiple remagnetization of Proterozoic dykes from Iguerda inlier (Anti-Atlas Belt, Southern Morocco) - Marta Neres; Pedro F. Silva; Moha Ikenne; Sofia Martins; Ahmid Hafid; João Mata; Francisco Almeida; Nasrrddine Youbi; Moulay A. Boumehdi (Studia Geophysica et Geodaetica, 2016)

Population ecology of the sea lamprey (Petromyzon marinus) as an invasive species in the Laurentian Great Lakes and an imperiled species in Europe - Michael J. Hansen; Charles P. Madenjian; Jeffrey W. Slade; Todd B. Steeves; Pedro R. Almeida; Bernardo R. Quintella (Reviews in Fish Biology and Fisheries, 2016)

How Natural Product Research has Contributed to Oral Care Product Development? A Critical View - Irlan Almeida Freires; Pedro Luiz Rosalen (Pharmaceutical Research, 2016)

Numerical Simulation of Soil Water Dynamics Under Stationary Sprinkler Irrigation With Mohid‐Land - Lucian Simionesei; Tiago B. Ramos; David Brito; Eduardo Jauch; Pedro C. Leitão; Carina Almeida; Ramiro Neves (Irrigation and Drainage, 2016)
Water distribution in sprinkler irrigation systems remains one of the most challenging problems in irrigation water management. Due to lack of water distribution uniformity, parts of a field may be over‐irrigated while others may be under‐irrigated, thus affecting root water and nutrient uptake and crop yield. The objective of this paper was to show the capabilities of the MOHID‐Land model in simulating soil water dynamics and maize growth under a stationary sprinkler irrigation system with low water distribution uniformity (56%). A 3D simulation domain (28 × 26 × 1 m) was defined to consider different water application rates at the soil surface and the variability of the soil hydraulic properties (two soil types). The model was able to take into account the effect of water distribution and soil variability on soil water content and fluxes, root water uptake reductions due to water stress, soil evaporation, leaf area index and total dry biomass. The resulting soil water balance revealed that irrigation inputs were lower (329 mm) than those theoretically defined to fulfil crop water requirements when the variable‐rate application of water was not considered (540 mm). Consequently, the range of variation of soil water stress in the simulation domain was relatively large (between 1 and 64%). MOHID‐Land has thus the potential of becoming an important tool for precision irrigation by focusing on site‐specific irrigation and crop management rather than the current field unit approach. Copyright © 2016 John Wiley & Sons, Ltd.

Development of an autonomous system for integrated marine monitoring - Magalhães Catarina; Mucha Ana Paula; Carvalho Maria; Ribeiro Hugo; Almeida Cristina; Azevedo Isabel; Ramos Sandra; Borges Teresa; Leandro Sérgio; Dos Santos Antonina; Silva Alexandra; Bartilotti Cátia; et al. (Frontiers in Marine Science, 2016)

Temporal and age-related dietary variations in a large population of yellow-legged gulls Larus michahellis: implications for management and conservation - Hany Alonso; Ana Almeida; José Pedro Granadeiro; Paulo Catry (European Journal of Wildlife Research, 2015)

Eucalyptus dunnii Maiden plant regeneration via shoot organogenesis on a new basal medium based on the mineral composition of young stump shoots - Gustavo Pedro Javier Oberschelp; Antônio Natal Gonçalves; Eveline Calderan Meneghetti; Érika Mendes Graner; Marcílio de Almeida (In Vitro Cellular & Developmental Biology - Plant, 2015)

Endophytic bacterial communities associated with two explant sources of Eucalyptus benthamii Maiden & Cambage - Natalia Pimentel Esposito-Polesi; Pedro Avelino Maia de Andrade; Cristina Vieira de Almeida; Fernando Dini Andreote; Marcílio de Almeida (World Journal of Microbiology and Biotechnology, 2015)

A porcine circovirus-2 mutant isolated in Brazil contains low-frequency substitutions in regions of immunoprotective epitopes in the capsid protein - Rafael Locatelli Salgado; Pedro Marcus Pereira Vidigal; Natalia F. Gonzaga; Luiz F. L. de Souza; Marcelo D. Polêto; Thiago Souza Onofre; Monique R. Eller; Carlos Eduardo Real Pereira; Juliana L. R. Fietto; Gustavo C. Bressan; Roberto M. C. Guedes; Márcia R. Almeida; et al. (Archives of Virology, 2015)

A population genomics insight into the Mediterranean origins of wine yeast domestication - Pedro Almeida; Raquel Barbosa; Polona Zalar; Yumi Imanishi; Kiminori Shimizu; Benedetta Turchetti; Jean‐Luc Legras; Marta Serra; Sylvie Dequin; Arnaud Couloux; Julie Guy; Douda Bensasson; et al. (Molecular Ecology, 2015)
The domestication of the wine yeast Saccharomyces cerevisiae is thought to be contemporary with the development and expansion of viticulture along the Mediterranean basin. Until now, the unavailability of wild lineages prevented the identification of the closest wild relatives of wine yeasts. Here, we enlarge the collection of natural lineages and employ whole‐genome data of oak‐associated wild isolates to study a balanced number of anthropic and natural S. cerevisiae strains. We identified industrial variants and new geographically delimited populations, including a novel Mediterranean oak population. This population is the closest relative of the wine lineage as shown by a weak population structure and further supported by genomewide population analyses. A coalescent model considering partial isolation with asymmetrical migration, mostly from the wild group into the Wine group, and population growth, was found to be best supported by the data. Importantly, divergence time estimates between the two populations agree with historical evidence for winemaking. We show that three horizontally transmitted regions, previously described to contain genes relevant to wine fermentation, are present in the Wine group but not in the Mediterranean oak group. This represents a major discontinuity between the two populations and is likely to denote a domestication fingerprint in wine yeasts. Taken together, these results indicate that Mediterranean oaks harbour the wild genetic stock of domesticated wine yeasts.

Morphology, ultrastructure and mineral uptake is affected by copper toxicity in young plants of Inga subnuda subs. luschnathiana (Benth.) T.D. Penn - Tielle Abreu de Freitas; Marcel Giovanni Costa França; Alex-Alan Furtado de Almeida; Sérgio José Ribeiro de Oliveira; Raildo Mota de Jesus; Vânia Lima Souza; José Victor dos Santos Silva; Pedro Antônio Mangabeira (Environmental Science and Pollution Research, 2015)

Global DNA Methylation Levels During the Development of Nodule Cluster Cultures and Assessment of Genetic Fidelity of In Vitro-Regenerated Pineapple Plants (Ananas comosus var. comosus) - Ramon Felipe Scherer; Hugo Pacheco de Freitas Fraga; Gustavo Ferrero Klabunde; Dorival Almeida da Silva; Miguel Pedro Guerra (Journal of Plant Growth Regulation, 2015)

Light-emitting diodes (LED) increase the stomata formation and chlorophyll content in Musa acuminata (AAA) ‘Nanicão Corupá’ in vitro plantlets - Leila do Nascimento Vieira; Hugo Pacheco de Freitas Fraga; Karina Goulart dos Anjos; Catarina Corrêa Puttkammer; Ramon Felipe Scherer; Dorival Almeida da Silva; Miguel Pedro Guerra (Theoretical and Experimental Plant Physiology, 2015)

Molecular, biochemical, morphological and ultrastructural responses of cacao seedlings to aluminum (Al3+) toxicity - Nicolle Moreira de Almeida; Alex-Alan Furtado de Almeida; Pedro Antonio Oliveira Mangabeira; Dário Ahnert; Graciele Santos Monteiro Reis; Andressa Vieira de Castro (Acta Physiologiae Plantarum, 2015)

Hepatic UDP-glucuronosyltransferase enzyme activity decreased during salt acclimation of sea lamprey juveniles from Minho river basin - Candeias Marta; Alves-Pereira Isabel; Lança Maria; Ferreira Ana; Quintella Bernardo; Almeida Pedro; Ferreira Rui (Frontiers in Marine Science, 2015)

Movement patterns of Mediterranean moray and European conger in a coastal MPA - Silva Ana Filipa; Quintella Bernardo; Pereira Tadeu; Belo Ana Filipa; Costa José; Almeida Pedro (Frontiers in Marine Science, 2015)

Evaluating a vertical slot fishway in the recolonization of upstream stretch of River Mondego that was not available to sea lamprey - Pereira Esmeralda; Quintella Bernardo; Mateus Catarina; Alexandre Carlos; Cardoso Gabriela; Belo Ana; Telhado Ana; Quadrado Maria; De Almeida Pedro (Frontiers in Marine Science, 2015)

Structural lipid changes and NKA activity of gill cells´ basolateral membranes as response to increasing salinity and atrazine stressors in sea lamprey (Petromyzon marinus, L.) juveniles - Lança Maria João; Machado Maria; Candeias Marta; Ferreira Rui; Alves-Pereira Isabel; Ferreira Ana Filipa; Quintella Bernardo; R. Almeida Pedro (Frontiers in Marine Science, 2015)

Monitoring anadromous fish populations in a context of habitat fragmentation and commercial exploitation - Cardoso Gabriela; Quintella Bernardo; Mateus Catarina; Alexandre Carlos; Belo Ana; Pereira Esmeralda; Telhado Ana; Quadrado Maria; De Almeida Pedro (Frontiers in Marine Science, 2015)

Effects of flow regulation in the life-cycles of a Mediterranean cyprinid species, the Iberian chub (Squalius carolitertii Doadrio, 1988) - Alexandre Carlos; Ferreira Teresa; De Almeida Pedro (Frontiers in Marine Science, 2015)

Changes in the fish community structure after the implementation of Marine Protected Areas in the south western coast of Portugal - Pereira Tadeu; Manique Joana; Quintella Bernardo; Castro Nuno; Almeida Pedro; Costa José (Frontiers in Marine Science, 2015)

A review of plant–pharmaceutical interactions: from uptake and effects in crop plants to phytoremediation in constructed wetlands - Pedro N. Carvalho; M. Clara P. Basto; C. Marisa R. Almeida; Hans Brix (Environmental Science and Pollution Research, 2014)

Convergent evolution of IL-6 in two leporids (Oryctolagus and Pentalagus) originated an extended protein - Fabiana Neves; Joana Abrantes; Ana Pinheiro; Tereza Almeida; Paulo P. Costa; Pedro J Esteves (Immunogenetics, 2014)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Effects of lead on anatomy, ultrastructure and concentration of nutrients in plants Oxycaryum cubense (Poep. & Kunth) Palla: a species with phytoremediator potential in contaminated watersheds - Laize Queiroz Alves; Raildo Mota de Jesus; Alex-Alan Furtado de Almeida; Vânia Lima Souza; Pedro Antônio Oliveira Mangabeira (Environmental Science and Pollution Research, 2014)

Response to oxidative stress induced by cadmium and copper in tobacco plants (Nicotiana tabacum) engineered with the trehalose-6-phosphate synthase gene (AtTPS1) - Luisa Louro Martins; Miguel Pedro Mourato; Sergio Baptista; Rafaela Reis; Florbela Carvalheiro; André M. Almeida; Pedro Fevereiro; Ann Cuypers (Acta Physiologiae Plantarum, 2014)

Patterns of fish and crustacean community structure in a coastal lagoon system, Rio de Janeiro, Brazil - Wagner L.S. Fortes; Pedro H. Almeida-Silva; Luana Prestrelo; Cassiano Monteiro-Neto (Marine Biology Research, 2014)

Altered physiology, cell structure, and gene expression of Theobroma cacao seedlings subjected to Cu toxicity - Vânia L. Souza; Alex-Alan F. de Almeida; Jadiel de S. Souza; Pedro A. O. Mangabeira; Raildo M. de Jesus; Carlos P. Pirovani; Dário Ahnert; Virupax C. Baligar; Leandro L. Loguercio (Environmental Science and Pollution Research, 2014)

Activated sludge systems removal efficiency of veterinary pharmaceuticals from slaughterhouse wastewater - Pedro N. Carvalho; António Pirra; M. Clara P. Basto; C. Marisa R. Almeida (Environmental Science and Pollution Research, 2013)

Comparative Study of Organohalogen Contamination Between Two Populations of Eastern Atlantic Loggerhead Sea Turtles (Caretta caretta) - María Camacho; Luis D. Boada; Jorge Orós; Pedro López; Manuel Zumbado; Maira Almeida-González; Octavio P. Luzardo (Bulletin of Environmental Contamination and Toxicology, 2013)

Characterization of an insect-specific flavivirus (OCFVPT) co-isolated from Ochlerotatus caspius collected in southern Portugal along with a putative new Negev-like virus - Daniela Duque Ferreira; Shelley Cook; Ângela Lopes; António Pedro de Matos; Aida Esteves; Ana Abecasis; António Paulo Gouveia de Almeida; João Piedade; Ricardo Parreira (Virus Genes, 2013)

Crops and fodder: evidence for storage and processing activities in a functional area at the Roman settlement of Monte Mozinho (northern Portugal) - João Pedro Tereso; Pablo Ramil-Rego; Teresa Pires De Carvalho; Rubim Almeida-da-Silva; Filipe Costa Vaz (Vegetation History and Archaeobotany, 2013)

TDZ pulsing evaluation on the in vitro morphogenesis of peach palm - Érika Mendes Graner; Gustavo Pedro Javier Oberschelp; Gilvano Ebling Brondani; Katherine Derlene Batagin-Piotto; Cristina Vieira de Almeida; Marcílio de Almeida (Physiology and Molecular Biology of Plants, 2013)

Characterization of Optical System for Hemodynamic Multi-Parameter Assessment - Tânia Pereira; Inês Santos; Tatiana Oliveira; Pedro Vaz; Tobias Correia; Telmo Pereira; Helder Santos; Helena Pereira; Vânia Almeida; João Cardoso; Carlos Correia (Cardiovascular Engineering and Technology, 2013)

Conceptions on genetics in a group of college students - Patrícia Santana Correia; Pedro Vitiello; Maria Helena Cabral de Almeida Cardoso; Dafne Dain Gandelman Horovitz (Journal of Community Genetics, 2013)

Cognitive Deficits in Machado–Joseph Disease Correlate with Hypoperfusion of Visual System Areas - Pedro Braga-Neto; Lívia Almeida Dutra; José Luiz Pedroso; André C. Felício; Helena Alessi; Ruth F. Santos-Galduroz; Paulo Henrique F. Bertolucci; Mário Luiz V. Castiglioni; Rodrigo Affonseca Bressan; Griselda Esther Jara de Garrido; Orlando Graziani Povoas Barsottini; Andrea Jackowski (The Cerebellum, 2012)

Cerebellar Cognitive Affective Syndrome in Machado Joseph Disease: Core Clinical Features - Pedro Braga-Neto; José Luiz Pedroso; Helena Alessi; Lívia Almeida Dutra; André Carvalho Felício; Thaís Minett; Patrícia Weisman; Ruth F. Santos-Galduroz; Paulo Henrique F. Bertolucci; Alberto Alain Gabbai; Orlando Graziani Povoas Barsottini (The Cerebellum, 2012)

Coastal vulnerability assessment based on video wave run-up observations at a mesotidal, steep-sloped beach - Michalis Ioannis Vousdoukas; Dagmara Wziatek; Luis Pedro Almeida (Ocean Dynamics, 2012)

Compartmentalization and ultrastructural alterations induced by chromium in aquatic macrophytes - Pedro A. Mangabeira; Aluane S. Ferreira; Alex-Alan F. de Almeida; Valéria F. Fernandes; Emerson Lucena; Vânia L. Souza; Alberto J. dos Santos Júnior; Arno H. Oliveira; Marie F. Grenier-Loustalot; Fréderique Barbier; Delmira C. Silva (BioMetals, 2011)

Performance of intertidal topography video monitoring of a meso-tidal reflective beach in South Portugal - Michalis Ioannis Vousdoukas; Pedro Manuel Ferreira; Luis Pedro Almeida; Guillaume Dodet; Fotis Psaros; Umberto Andriolo; Rui Taborda; Ana Nobre Silva; Antonio Ruano; Óscar Manuel Ferreira (Ocean Dynamics, 2011)

Low breeding success and sharp population decline at the largest known Falkland skua colony - Paulo Catry; Ana Almeida; Miguel Lecoq; José Pedro Granadeiro; Rafael Matias (Polar Biology, 2011)

New insights on the origin of B chromosomes in Astyanax scabripinnis obtained by chromosome painting and FISH - Marcelo Ricardo Vicari; Helena Flávia de Mello Pistune; Jonathan Pena Castro; Mara Cristina de Almeida; Luiz Antonio Carlos Bertollo; Orlando Moreira-Filho; Juan Pedro M. Camacho; Roberto Ferreira Artoni (Genetica, 2011)

Sleep Disorders in Machado–Joseph Disease: Frequency, Discriminative Thresholds, Predictive Values, and Correlation with Ataxia-Related Motor and Non-Motor Features - José Luiz Pedroso; Pedro Braga-Neto; André Carvalho Felício; Lívia Almeida Dutra; William A. C. Santos; Gilmar Fernandes do Prado; Orlando Graziani Povoas Barsottini (The Cerebellum, 2011)

Comparing several equations that predict peak VO2 using the 20-m multistage-shuttle run-test in 8–10-year-old children - Xavier Melo; Helena Santa-Clara; José Pedro Almeida; Elvis Alvarez Carnero; Luís Bettencourt Sardinha; Paula Marta Bruno; Bo Fernhall (European Journal of Applied Physiology, 2011)

Complex size-dependent habitat associations in potamodromous fish species - José Maria Santos; Luís Reino; Miguel Porto; João Oliveira; Paulo Pinheiro; Pedro Raposo Almeida; Rui Cortes; Maria Teresa Ferreira (Aquatic Sciences, 2011)

Potential programming of dopaminergic circuits by early life stress - Ana-João Rodrigues; Pedro Leão; Miguel Carvalho; Osborne F. X. Almeida; Nuno Sousa (Psychopharmacology, 2011)

Morphophysiological responses and programmed cell death induced by cadmium in Genipa americana L. (Rubiaceae) - Vânia L. Souza; Alex-Alan F. de Almeida; Stella G. C. Lima; Júlio C. de M. Cascardo; Delmira da C. Silva; Pedro A. O. Mangabeira; Fábio P. Gomes (BioMetals, 2011)

Long-Term Trends in Intertidal and Subtidal Benthic Communities in Response to Water Quality Improvement Measures - Paula Chainho; Gilda Silva; Michael F. Lane; José L. Costa; Tadeu Pereira; Carla Azeda; Pedro R. Almeida; Inês Metelo; Maria J. Costa (Estuaries and Coasts, 2010)

Inhibition of Streptococcus mutans biofilm accumulation and development of dental caries in vivo by 7-epiclusianone and fluoride - Ramiro M. Murata; Luciana S. Branco-de-Almeida; Eliane M. Franco; Regiane Yatsuda; Marcelo H. dos Santos; Severino M. de Alencar; Hyun Koo; Pedro L. Rosalen (Biofouling, 2010)

The selective COX-2 inhibitor Etoricoxib reduces acute inflammatory markers in a model of neurogenic laryngitis but loses its efficacy with prolonged treatment - Manuel Lima-Rodrigues; Nuno Lamas; Ana Valle-Fernandes; Andrea Cruz; Artur Vieira; Pedro Oliveira; Jorge Pedrosa; António G. Castro; Rui M. Reis; Fátima Baltazar; Armando Almeida (Inflammation Research, 2010)

Physical and mechanical characterization of phyllites and metagreywackes in central Portugal - Pedro Santarém Andrade; António Almeida Saraiva (Bulletin of Engineering Geology and the Environment, 2010)

Prevalence of antimicrobial resistance and molecular characterization of tetracycline resistance mediated by tet(M) and tet(L) genes in Enterococcus spp. isolated from food in Southern Brazil - Ana Paula Guedes Frazzon; Bianca Almeida Gama; Vanessa Hermes; Christine Garcia Bierhals; Rebeca Inhoque Pereira; Arthur Gomes Guedes; Pedro Alves d’Azevedo; Jeverson Frazzon (World Journal of Microbiology and Biotechnology, 2010)

Spatial Pattern and Fine-Scale Genetic Structure Indicating Recent Colonization of the Palm Euterpe edulis in a Brazilian Atlantic Forest Fragment - Fábio de Almeida Vieira; Dulcinéia de Carvalho; Pedro Higuchi; Evandro Luiz Mendonça Machado; Rubens Manoel dos Santos (Biochemical Genetics, 2010)

Biotic and abiotic factors affecting the δ 13 C of soil respired CO 2 in a Mediterranean oak woodland† - Kadmiel Maseyk; Lisa Wingate; Ulli Seibt; Jaleh Ghashghaie; Camille Bathellier; Pedro Almeida; Raquel Lobo de Vale; Joao S. Pereira; Dan Yakir; Maurizio Mencuccini (Isotopes in Environmental and Health Studies, 2009)

Metal levels in sediments from the Minho estuary salt marsh: a metal clean area? - Pedro A. Reis; José C. Antunes; C. Marisa R. Almeida (Environmental Monitoring and Assessment, 2009)

Spartina maritima (cordgrass) rhizosediment extracellular enzymatic activity and its role in organic matter decomposition processes and metal speciation - Bernardo Duarte; Pedro R. Almeida; Isabel Caçador (Marine Ecology, 2009)
Seasonal monitoring was carried out to investigate the influence of extracellular enzymatic activity (EEA) on metal speciation and organic matter cycling in the rhizosediment of Spartina maritima . Heavy metal speciation was achieved by the Tessier scheme, and showed a similar pattern of variation of the organic‐bound fraction, indicating a decomposition process in progress. Both humic acid and organic matter showed the same seasonal pattern. The basal respiration of the rhizosediments also presented a similar seasonal pattern, indicating a microbial degradation of organic matter. The high organic‐bound fraction found in the summer gradually decreased towards the winter. This decrease was found to be related to the increase of activity of peroxidase, β‐ N ‐acetylglucosaminidase and protease. Also the activity of sulphatase was found to be related to the depletion on the exchangeable fraction, probably due to sulphide formation and consequent mobilization. The results show an interaction between several microbial activities, affecting metal speciation.

Evaporation and carbonic anhydrase activity recorded in oxygen isotope signatures of net CO 2 fluxes from a Mediterranean soil - LISA WINGATE; ULLI SEIBT; KADMIEL MASEYK; JÉRÔME OGÉE; PEDRO ALMEIDA; DAN YAKIR; JOAO S. PEREIRA; MAURIZIO MENCUCCINI (Global Change Biology, 2008)
The oxygen stable isotope composition ( δ 18 O) of CO 2 is a valuable tool for studying the gas exchange between terrestrial ecosystems and the atmosphere. In the soil, it records the isotopic signal of water pools subjected to precipitation and evaporation events. The δ 18 O of the surface soil net CO 2 flux is dominated by the physical processes of diffusion of CO 2 into and out of the soil and the chemical reactions during CO 2 –H 2 O equilibration. Catalytic reactions by the enzyme carbonic anhydrase, reducing CO 2 hydration times, have been proposed recently to explain field observations of the δ 18 O signatures of net soil CO 2 fluxes. How important these catalytic reactions are for accurately predicting large‐scale biosphere fluxes and partitioning net ecosystem fluxes is currently uncertain because of the lack of field data. In this study, we determined the δ 18 O signatures of net soil CO 2 fluxes from soil chamber measurements in a Mediterranean forest. Over the 3 days of measurements, the observed δ 18 O signatures of net soil CO 2 fluxes became progressively enriched with a well‐characterized diurnal cycle. Model simulations indicated that the δ 18 O signatures recorded the interplay of two effects: (1) progressive enrichment of water in the upper soil by evaporation, and (2) catalytic acceleration of the isotopic exchange between CO 2 and soil water, amplifying the contributions of ‘atmospheric invasion’ to net signatures. We conclude that there is a need for better understanding of the role of enzymatic reactions, and hence soil biology, in determining the contributions of soil fluxes to oxygen isotope signals in atmospheric CO 2 .

Estimating the joint roughness coefficient of discontinuities found in metamorphic rocks - Pedro Santarém Andrade; António Almeida Saraiva (Bulletin of Engineering Geology and the Environment, 2008)

Mobility of metals in salt marsh sediments colonised by Spartina maritima (Tagus estuary, Portugal) - Rosa Reboreda; Isabel Caçador; Sílvia Pedro; Pedro Raposo Almeida (Hydrobiologia, 2008)

Vertebrate dispersal syndromes along the Atlantic forest: broad‐scale patterns and macroecological correlates - Mário Almeida‐Neto; Flávia Campassi; Mauro Galetti; Pedro Jordano; Ary Oliveira‐Filho (Global Ecology and Biogeography, 2008)
Aim To assess the geographical variation in the relative importance of vertebrates, and more specifically of birds and mammals, as seed dispersal agents in forest communities, and to evaluate the influence of geographical and climatic factors on the observed trends. Location One hundred and thirty‐five forest communities in the Brazilian Atlantic forest. Methods We collected data on dispersal modes for 2292 woody species. By combining species × site with species × trait matrices, we obtained the percentages of endozoochory, ornithochory, mastozoochory and the mean fruit diameter for the local forest communities. We used Spearman's correlation to assess bivariate relationships between variables. Subsequently, we performed paired t‐ tests to verify if variations in frequency of dispersal modes and mean fruit diameter were influenced by altitude or temperature. Then, we applied multiple linear regressions to evaluate the effect of geographical and climatic variables on variation in the relative frequency of dispersal modes and mean fruit diameter across communities. Results We found no consistent latitudinal or longitudinal trend in the percentage of vertebrate‐dispersed species, neither bird‐ nor mammal‐dispersed species along the Atlantic forest. Endozoochory was affected chiefly by annual mean rainfall, increasing towards moister sites. Forest communities located at higher altitudes had a higher percentage of bird‐dispersed species. Even when sites with identical values of annual mean temperature were compared, altitude had a positive effect on ornithochory. Conversely, we found a higher percentage of mammal‐dispersed species in warmer forests, even when locations at the same altitudinal belts were contrasted. Fruit diameter was clearly related to altitude, decreasing towards higher elevations. Main conclusions This is the first analysis of a large data set on dispersal syndromes in tropical forest communities. Our findings support the hypotheses that: (1) geographical variation in the relative number of fleshy fruit species is mainly driven by moisture conditions and is relatively independent of geographical location, and (2) broad‐scale trends in fruit size correspond to geographical variation in the relative importance of mammals and birds as seed dispersal agents at the community level.

Genetic diversity evolution through participatory maize breeding in Portugal - Maria Carlota Vaz Patto; Pedro Manuel Moreira; Nuno Almeida; Zlatko Satovic; Silas Pego (Euphytica, 2008)

Comparative ecology of the European eel, Anguilla anguilla (L., 1758), in a large Iberian river - José Lino Costa; Isabel Domingos; Carlos A. Assis; Pedro R. Almeida; Francisco Moreira; Eric Feunteun; Maria José Costa (Environmental Biology of Fishes, 2008)

A Sterol-Like Odorant in the Urine of Mozambique Tilapia Males Likely Signals Social Dominance to Females - Eduardo N. Barata; Jared M. Fine; Peter C. Hubbard; Olinda G. Almeida; Pedro Frade; Peter W. Sorensen; Adelino V. M. Canário (Journal of Chemical Ecology, 2008)

Trehalose and its applications in plant biotechnology - André M. Almeida; Luís A. Cardoso; Dulce M. Santos; José M. Torné; Pedro S. Fevereiro (In Vitro Cellular & Developmental Biology - Plant, 2007)

Electroporation of maize embryogenic calli with the trehalose-6-phosphate synthase gene from Arabidopsis thaliana - André M. Almeida; Enrique Villalobos; Susana S. Araújo; Luis A. Cardoso; Dulce M. Santos; Maria A. Santos; Pedro S. Fevereiro; José M. Torné (Acta Physiologiae Plantarum, 2007)

Introduction - Pedro R. Almeida; Bernardo R. Quintella; Maria J. Costa; Andrew Moore (Hydrobiologia, 2007)

Sea lamprey (Petromyzon marinus L.) spawning migration in the Vouga river basin (Portugal): poaching impact, preferential resting sites and spawning grounds - N. O. Andrade; B. R. Quintella; J. Ferreira; S. Pinela; I. Póvoa; S. Pedro; P. R. Almeida (Hydrobiologia, 2007)

Evolutionary history of lamprey paired species Lampetra fluviatilis (L.) and Lampetra planeri (Bloch) as inferred from mitochondrial DNA variation - RUTE ESPANHOL; PEDRO R. ALMEIDA; M. JUDITE ALVES (Molecular Ecology, 2007)
A remarkable trend in the evolution of lampreys is the occurrence in most genera of ‘paired species’, in which the parasitic anadromous lampreys are believed to have given rise to nonparasitic freshwater resident populations. The present work examines the phylogeography of the European paired species Lampetra fluviatilis and Lampetra planeri , in an attempt to elucidate species pair evolutionary history. We studied sequence variation in cytochrome b and ATPase 6, 8 mitochondrial genes in 63 individuals from 21 localities of the paired species throughout their distribution range. Results from the phylogenetic and nested clade analyses were largely consistent, suggesting the existence of three major evolutionary lineages: lineage I and possibly lineage II are widespread throughout Europe, while the most ancestral lineage III is apparently restricted to the Iberian Peninsula. The high genetic diversity observed in the Iberian Peninsula is probably the result of refugial persistence and subsequent accumulation of variation over several ice ages, whereas the low levels of genetic diversity observed in central and northern Europe should reflect a rapid postglacial colonization. Results suggest that L. planeri originated within at least two distinct evolutionary lineages, rejecting the single origin hypothesis. The observed lack of taxa monophyly within lineage I may be the result of ongoing gene flow if the two taxa are alternate life‐history forms of a single species. However, structure within lineage I is also consistent with the hypothesis of divergence of taxa after postglacial dispersion (around 2000 generations ago) with incomplete lineage sorting. Further testing of the alternative hypotheses is warranted.

Responses to water withdrawal of tobacco plants genetically engineered with the AtTPS1 gene: a special reference to photosynthetic parameters - André M. Almeida; Anabela B. Silva; Susana S. Araújo; Luís A. Cardoso; Dulce M. Santos; José M. Torné; Jorge M. Silva; Matthew J. Paul; Pedro S. Fevereiro (Euphytica, 2007)

Structure and Dynamics of a Benthic Invertebrate Community in an Intertidal Area of the Tagus Estuary, Western Portugal: A Six Year Data Series - Gilda Silva; José Lino Costa; Pedro Raposo de Almeida; Maria José Costa (Hydrobiologia, 2006)

Transformation of tobacco with an Arabidopsis thaliana gene involved in trehalose biosynthesis increases tolerance to several abiotic stresses - André M. Almeida; Enrique Villalobos; Susana S. Araújo; Barbara Leyman; Patrick Van Dijck; Luís Alfaro-Cardoso; Pedro S. Fevereiro; José M. Torné; Dulce M. Santos (Euphytica, 2005)

Effects of soil flooding on leaf gas exchange and growth of two neotropical pioneer tree species - Marcelo Schramm Mielke; Alex-Alan Furtado De Almeida; Fábio Pinto Gomes; Pedro Antonio Oliveira Mangabeira; Delmira Da Costa Silva (New Forests, 2005)

Pharmacokinetic?pharmacodynamic interaction between BIA 3-202, a novel COMT inhibitor, and levodopa/benserazide - Pedro Silveira; Manuel Vaz-da-Silva; Luis Almeida; Joana Maia; Amilcar Falco; Ana Loureiro; Leonel Torro; Rita Machado; Lyndon Wright; Patrcio Soares-da-Silva (European Journal of Clinical Pharmacology, 2003)